Natural Disasters and Rehabilitation: Post‐Disaster Aid, Corruption, Misallocation, and Mistargeting - Ahmad, Muhammad Irshad; Shen, Qiong; Boota, Muhammad Waseem; Liu, Ruifeng; Ma, Hengyun (Sustainable Development, 2025)
ABSTRACT The increasing frequency of natural disasters, such as floods, droughts, and tsunamis, has made vulnerable communities less resilient, pushing them toward long‐term poverty and food insecurity. Effective post‐disaster rehabilitation is critical to restoring livelihoods, infrastructure, and food security. However, challenges such as corruption, misallocation, and mistargeting undermine post‐disaster aid programs. This study systematically reviews 86 peer‐reviewed articles (1990–2023) using the preferred reporting items for systematic reviews and meta‐analyses (PRISMA) protocol to investigate aid inefficiencies in disaster recovery. The findings reveal that aid often fails to reach the most affected communities, being diverted to unaffected areas due to political influence and local elites, exacerbating inequalities. Corruption further hampers institutional performance and long‐term disaster resilience efforts. The study calls for transparent, accountable, and inclusive strategies for aid distribution, aligning with SDG 10 (reduced inequalities) and SDG 11 (sustainable cities and communities). Future research should focus on gender‐sensitive strategies, local governance, and technological innovations to enhance aid transparency and effectiveness.
Keywords: Scopus_Alert_12_Septembre_2025

Market-based instruments to fund nature-based solutions for flood risk management can disproportionately benefit affluent areas - Hill, Bartholomew; Marjoribanks, Tim; Moore, Harriet; Bosher, Lee; Gussy, Mark (Communications Earth & Environment, 2025)
Abstract Market-based instruments, including competitive tenders, are central to funding global environmental restoration and management projects. Recently, tenders have been utilised to fund Nature-based Solutions schemes for Natural Flood Management, with the explicit purpose of achieving co-benefits; flood management and reducing inequities. While multiple studies consider the efficacy of Nature-based Solutions for tackling inequities, no prior research has quantified whether the resource allocation for these projects has been conducted equitably. We analyse two national natural flood management programmes funded through competitive tenders in England to explore who benefits by considering the characteristics of projects, including socio-economic, geographical (e.g. rurality) and flood risk dynamics. Our results suggest that inequity occurs at both the application and funding stages of Nature-based Solutions projects for flood risk management. This reflects wider international challenges of using market-based instruments for environmental resource allocation. Competitive tenders have the potential to undermine the equitable benefits of Nature-based Solutions.
Keywords: Scopus_Alert_12_Septembre_2025

Integrative strategies for urban flood resilience and risk: A meta-analysis of policy, infrastructural, and ecosystem-based interventions - Wang, Shitao; Bi, Xuehao (Physics and Chemistry of the Earth, 2025)
Urban flooding, intensified by climate change and rapid urbanization, demands robust and operationally effective resilience strategies. However, empirical evidence on the comparative effectiveness of such strategies remains limited. This study presents the first meta-analytic synthesis evaluating urban flood resilience interventions across institutional, infrastructural, and socio-ecological domains. By synthesizing data from 29 peer-reviewed studies (2000–2024), this study applies standardized effect sizes (Cohen's d) and meta-regression models to assess the effectiveness of different strategies. Results reveal a substantial overall effect (pooled d = 2.96, 95 % CI: [1.92, 3.99]) with high heterogeneity (I2 = 93.8 %). Institutional mechanisms, such as policy coordination, regulatory frameworks, and risk governance, consistently show the strongest and most statistically significant impacts (d ≈ 2.96). Low Impact Development (LID) demonstrates limited, non-significant effects (d ≈ 0.08). The study introduces a novel hierarchical resilience framework spanning different dimensions and establishes an evidence-based typology of urban flood resilience strategies. These findings highlight the importance of integrated, multi-level governance and context-specific planning in enhancing urban flood resilience. The study findings provides critical insights for implementing resilience strategies in flood-prone urban areas, and support the formulation of adaptive and sustainable urban policies. © 2025
Keywords: Scopus_Alert_5_Septembre_2025

Predictive Modeling and Strategic Planning for Urban Flood Risk Mitigation - Mitali, Patel; Patel, Nishit; Modi, Kshitish; Patel, Samir (Communications in Computer and Information Science, 2026)
Urban flooding threatens Indian cities and is made worse by rapid urbanization, climate change and poor infrastructure. Severe flooding occurred in cities such as Mumbai, Chennai and Ahmedabad. This has caused huge economic losses and displacement. This study addresses the limitations of traditional flood forecasting methods. It has to contend with the complex dynamics of urban flooding. We offer a deep learning approach which uses the network Convolutional Neural Networks (CNN) and Long Short-Term Memory (LSTM) networks to improve flood risk prediction. Our CNN-LSTM model combines spatial data (water table, topography) and temporal data (historical model) to classify flood risk as low or high. This method includes collecting data pre-processing (MinMaxScaler, LabelEncoder) Modeling, Training and Evaluation. The results demonstrate the accuracy of flood risk predictions and provide insights into flexible strategies for urban flood management. This research highlights the role of data-driven approaches in improving urban planning to reduce flood risk in high-risk areas. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2026.
Keywords: Scopus_Alert_5_Septembre_2025

Interest Flooding Attacks in Named Data Networking and Mitigations: Recent Advances and Challenges - Ogunbunmi, Simeon; Chen, Yu; Zhao, Qi; Nagothu, Deeraj; Wei, Sixiao; Chen, Genshe; Blasch, Erik (Future Internet, 2025)
Named Data Networking (NDN) represents a promising Information-Centric Networking architecture that addresses limitations of traditional host-centric Internet protocols by emphasizing content names rather than host addresses for communication. While NDN offers advantages in content distribution, mobility support, and built-in security features, its stateful forwarding plane introduces significant vulnerabilities, particularly Interest Flooding Attacks (IFAs). These IFA attacks exploit the Pending Interest Table (PIT) by injecting malicious interest packets for non-existent or unsatisfiable content, leading to resource exhaustion and denial-of-service attacks against legitimate users. This survey examines research advances in IFA detection and mitigation from 2013 to 2024, analyzing seven relevant published detection and mitigation strategies to provide current insights into this evolving security challenge. We establish a taxonomy of attack variants, including Fake Interest, Unsatisfiable Interest, Interest Loop, and Collusive models, while examining their operational characteristics and network performance impacts. Our analysis categorizes defense mechanisms into five primary approaches: rate-limiting strategies, PIT management techniques, machine learning and artificial intelligence methods, reputation-based systems, and blockchain-enabled solutions. These approaches are evaluated for their effectiveness, computational requirements, and deployment feasibility. The survey extends to domain-specific implementations in resource-constrained environments, examining adaptations for Internet of Things deployments, wireless sensor networks, and high-mobility vehicular scenarios. Five critical research directions are proposed: adaptive defense mechanisms against sophisticated attackers, privacy-preserving detection techniques, real-time optimization for edge computing environments, standardized evaluation frameworks, and hybrid approaches combining multiple mitigation strategies. © 2025 by the authors.
Keywords: Scopus_Alert_5_Septembre_2025

Injectivity, Potential Wettability Alteration, and Mineral Dissolution in Low-Salinity Waterflood Applications: The Role of Salinity, Surfactants, Polymers, Nanomaterials, and Mineral Dissolution - Sarma, Hemanta K.; Awolayo, Adedapo N.; Olayiwola, Saheed O.; Fakir, Shasanowar H.; Belhaj, Ahmed F. (Processes, 2025)
Waterflooding, a key method for secondary hydrocarbon recovery, has been employed since the early 20th century. Over time, the role of water chemistry and ions in recovery has been studied extensively. Low-salinity water (LSW) injection, a common technique since the 1930s, improves oil recovery by altering the wettability of reservoir rocks and reducing residual oil saturation. Recent developments emphasize the integration of LSW with various recovery methods such as CO2 injections, surfactants, alkali, polymers, and nanoparticles (NPs). This article offers a comprehensive perspective on how LSW injection is combined with these enhanced oil recovery (EOR) techniques, with a focus on improving oil displacement and recovery efficiency. Surfactants enhance the effectiveness of LSW by lowering interfacial tension (IFT) and improving wettability, while ASP flooding helps reduce surfactant loss and promotes in situ soap formation. Polymer injections boost oil recovery by increasing fluid viscosity and improving sweep efficiency. Nevertheless, challenges such as fine migration and unstable flow persist, requiring additional optimization. The combination of LSW with nanoparticles has shown potential in modifying wettability, adjusting viscosity, and stabilizing emulsions through careful concentration management to prevent or reduce formation damage. Finally, building on discussions around the underlying mechanisms involved in improved oil recovery and the challenges associated with each approach, this article highlights their prospects for future research and field implementation. By combining LSW with advanced EOR techniques, the oil industry can improve recovery efficiency while addressing both environmental and operational challenges. © 2025 by the authors.
Keywords: Scopus_Alert_5_Septembre_2025

Copula-based joint distribution modelling of precipitation, temperature and humidity events in the assessments of agricultural risks, with a case study in Morocco - Latif, Shahid; El Ouadi, Ihssan; Ouarda, Taha B. M. J. (Stochastic Environmental Research and Risk Assessment, 2025)
The agriculture sector is profoundly impacted by the abiotic stresses in arid or semi-arid regions that experience extreme weather patterns related to temperature (T), precipitation (P), humidity (H), and other factors. This study adopts a flexible approach that incorporates the D-vine copula density to analyze trivariate (and bivariate) joint and conditional hazard risk. The methodology was applied to a case study in the Ait Ben Yacoub region of Morocco. Monthly series for T, H, and P were modeled using the Weibull-2P and Weibull-3P models, selected based on fitness statistics. The survival BB8 copula was best described as joint dependence for pair T–P, rotated BB8 270 degrees copula for T–H, while rotated Joe 270 degrees copula for P–H. The analysis of joint probability stress focused on both primary joint scenarios (for OR and AND-hazard conditions) and conditional return periods (RPs) for trivariate and bivariate case. Lower univariate RPs resulted in higher marginal quantiles for T and lower for H and P events. Lower trivariate (and bivariate) AND-joint RPs (or higher concurrence probabilities) were associated with higher T with lower P and H quantiles. The occurrence of trivariate (and bivariate) events was less frequent in the AND-joint case compared to the OR-joint case. The conditional joint RP of T (or T with P, or T with H) was significantly affected by different P (at 10th and 25th percentile) and H (at 5th and 25th percentile) (or P, or H) conditions. Lower conditional RPs of T (or T with H, or T with P) had resulted at given low P and H (or low P, or low H levels). In conclusion, the estimated risk statistics are vital for the study region, highlighting the need for effective adaptation and resilience planning in agriculture crop management.
Keywords: Infolettre_Septembre_2025

High-Resolution Daily XCH4 Prediction Using New Convolutional Neural Network Autoencoder Model and Remote Sensing Data - Awad, Mohamad M.; Homayouni, Saeid (Atmosphere, 2025)
Atmospheric methane (CH4) concentrations have increased to 2.5 times their pre-industrial levels, with a marked acceleration in recent decades. CH4 is responsible for approximately 30% of the global temperature rise since the Industrial Revolution. This growing concentration contributes to environmental degradation, including ocean acidification, accelerated climate change, and a rise in natural disasters. The column-averaged dry-air mole fraction of methane (XCH4) is a crucial indicator for assessing atmospheric CH4 levels. In this study, the Sentinel-5P TROPOMI instrument was employed to monitor, map, and estimate CH4 concentrations on both regional and global scales. However, TROPOMI data exhibits limitations such as spatial gaps and relatively coarse resolution, particularly at regional scales or over small areas. To mitigate these limitations, a novel Convolutional Neural Network Autoencoder (CNN-AE) model was developed. Validation was performed using the Total Carbon Column Observing Network (TCCON), providing a benchmark for evaluating the accuracy of various interpolation and prediction models. The CNN-AE model demonstrated the highest accuracy in regional-scale analysis, achieving a Mean Absolute Error (MAE) of 28.48 ppb and a Root Mean Square Error (RMSE) of 30.07 ppb. This was followed by the Random Forest (RF) regressor (MAE: 29.07 ppb; RMSE: 36.89 ppb), GridData Nearest Neighbor Interpolator (NNI) (MAE: 30.06 ppb; RMSE: 32.14 ppb), and the Radial Basis Function (RBF) Interpolator (MAE: 80.23 ppb; RMSE: 90.54 ppb). On a global scale, the CNN-AE again outperformed other methods, yielding the lowest MAE and RMSE (19.78 and 24.7 ppb, respectively), followed by RF (21.46 and 27.23 ppb), GridData NNI (25.3 and 32.62 ppb), and RBF (43.08 and 54.93 ppb).
Keywords: Infolettre_Septembre_2025

Optimizing ensemble learning for satellite-based multi-hazard monitoring and susceptibility assessment of landslides, land subsidence, floods, and wildfires - Razavi-Termeh, Seyed Vahid; Sadeghi-Niaraki, Abolghasem; Ali, Farman; Pradhan, Biswajeet; Choi, Soo-Mi (Scientific Reports, 2025)
The preparation of accurate multi-hazard susceptibility maps is essential to effective disaster risk management. Past studies have relied mainly on traditional machine learning models, but these models do not perform well for complex spatial patterns. To address this gap, this study uses two meta-heuristic algorithms (Genetic Algorithm (GA) and Particle Swarm Optimization (PSO)) to provide an optimized Random Forest (RF) model with better predictive ability. We focus on four significant hazards—landslides, land subsidence, wildfires, and floods—in Kurdistan Province, Iran, using Sentinel-1 and Sentinel-2 satellite imagery collected between 2015 and 2022. Furthermore, two models of RF-GA and RF-PSO were utilized to create multi-hazard susceptibility, which were evaluated using receiver operating characteristic (ROC) curves and area under the curve (AUC). The RF-GA algorithm achieved 91.1% accuracy for flood hazards, 83.8% for wildfires, and 99.1% for landslide hazards. In contrast, utilizing RF-PSO resulted in a 95.9% accuracy for land subsidence hazards. The combined RF-GA algorithm demonstrated superior accuracy to individual RF modeling techniques. Furthermore, eastern regions are more prone to floods and land subsidence, whereas western areas face more significant risks from landslides and wildfires. Additionally, floods and land subsidence exhibit a considerable correlation, impacting each other’s occurrence, while wildfires and landslides demonstrate interacting dynamics, influencing each other’s likelihood of occurrence. © The Author(s) 2025.

Editorial preface to special issue: Temporal and spatial patterns in Holocene floods under the influence of past global change, and their implications for forecasting “unpredecented” future events - Schulte, Lothar; Santisteban, Juan I.; Fuller, Ian C.; Ballesteros-Cánovas, Juan Antonio (Global and Planetary Change, 2025)
Floods constitute the most significant natural hazard to societies worldwide. Population growth and unchecked development have led to floodplain encroachment. Modelling suggests that climate change will regionally intensify the threat posed by future floods, with more people in harm's way. From a global change perspective, past flood events and their spatial-temporal patterns are of particular interest because they can be linked to former climate patterns, which can be used to guide future climate predictions. Millennial and centennial time series contain evidence of very rare extreme events, which are often considered by society as ‘unprecedented’. By understanding their timing, magnitude and frequency in conjunction with prevailing climate regime, we can better forecast their future occurrence. This Virtual Special Issue (VSI) entitled Temporal and spatial patterns in Holocene floods under the influence of past global change, and their implications for forecasting “unpredecented” future events comprises 14 papers that focus on how centennial and millennia-scale natural and documentary flood archives help improve future flood science. Specifically, documentation of large and very rare flood episodes challenges society's lack of imagination regarding the scale of flood disasters that are possible (what we term here, the “unknown unknowns”). Temporal and spatial flood behaviour and related climate patterns as well as the reconstruction of flood propagation in river systems are important foci of this VSI. These reconstructions are crucial for the provision of robust and reliable data sets, knowledge and baseline information for future flood scenarios and forecasting. We argue that it remains difficult to establish analogies for understanding flood risk during the current period of global warming. Most studies in this VSI suggest that the most severe flooding occurred during relatively cool climate periods, such as the Little Ice Age. However, flood patterns have been significantly altered by land use and river management in many catchments and floodplains over the last two centuries, thereby obscuring the climate signal. When the largest floods in instrumental records are compared with paleoflood records reconstructed from natural and documentary archives, it becomes clear that precedent floods should have been considered in many cases of flood frequency analysis and flood risk modelling in hydraulic infrastructure. Finally, numerical geomorphological analysis and hydrological simulations show great potential for testing and improving our understanding of the processes and factors involved in the temporal and spatial behaviour of floods. © 2025 The Authors

Effects of long-term wetland variations on flood risk assessments in the Yangtze River Basin - Guo, Ziying; Shi, Xiaogang; Zhang, Dingfan; Zhao, Qunshan (Environmental Impact Assessment Review, 2026)
Flooding is the most frequent natural disaster in the Yangtze River Basin (YRB), causing significant socio-economic damages. In recent decades, abundant wetland resources in the YRB have experienced substantial changes and played a significant role in strengthening the hydrological resilience to flood risks. However, wetland-related approaches remain underdeveloped for mitigating flood risks in the YRB due to the lack of considering long-term wetland effects in the flood risk assessment. Therefore, this study develops an wetland-related GIS-based spatial multi-index flood risk assessment model by incorporating the effects of wetland variations, to investigate the long-term implications of wetland variations on flood risks, to identify dominant flood risk indicators under wetland effects, and to provide wetland-related flood risk management suggestions. These findings indicate that wetlands in the Taihu Lake Basin, Wanjiang Plain, Poyang Lake Basin, and Dongting and Honghu Lake Basin could enhance flood control capacity and reduce flood risks in most years between 1985 and 2021 except years with extreme flood disasters. Wetlands in the Sichuan Basin have aggravated but limited impacts on flood risks. Precipitation in the Taihu Lake Basin and Poyang Lake Basin, runoff and vegetation cover in the Wanjiang Plain, GDP in the Taihu Lake Basin, population density in the Taihu lake Basin, Dongting and Honghu Lake Basin, and the Sichuan Basin are dominant flood risk indicators under wetland effects. Reasonably managing wetlands, maximizing stormwater storage capacity, increasing vegetation coverage in urbanized and precipitated regions are feasible suggestions for developing wetland-related flood resilience strategies in the YRB. © 2025 The Authors

Managing floods and droughts synergistically: A transformative governance approach - Sánchez, Ana Núñez; Koehler, Johanna; Van Loon, Anne F. (PLOS Water, 2025)
Floods and droughts cause large economic and environmental impacts and incalculable human suffering. Despite growing evidence of important synergies in their management, floods and droughts tend to be mostly managed in silos. The synergistic management of flood and drought risk is limited by the inability of current governance systems to change at the scope, depth and speed required to address the emerging challenges of climate change induced hydroclimatic risks. Building on the concept of continuous transformational change and combining key elements across sectoral governance frameworks, this paper proposes a transformative governance conceptual framework that enables national governments to work across silos in a whole of government approach to lead a whole of society effort to manage the whole hydroclimatic spectrum. Spain, a country with an advanced hydroclimatic risk management system, is presented as an illustrative example to explore the possible idiosyncrasies of implementing the proposed changes on the ground. © 2025 Núñez Sánchez et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.

Research on the Comprehensive Evaluation Model of Risk in Flood Disaster Environments - Yu, Yan; Zhou, Tianhua (Water (Switzerland), 2025)
Losses from floods and the wide range of impacts have been at the forefront of hazard-triggered disasters in China. Affected by large-scale human activities and the environmental evolution, China’s defense flood situation is undergoing significant changes. This paper constructs a comprehensive flood disaster risk assessment model through systematic analysis of four key factors—hazard (H), exposure (E), susceptibility/sensitivity (S), and disaster prevention capabilities (C)—and establishes an evaluation index system. Using the Analytic Hierarchy Process (AHP), we determined indicator weights and quantified flood risk via the following formula R = H × E × V × C. After we applied this model to 16 towns in coastal Zhejiang Province, the results reveal three distinct risk tiers: low (R < 0.04), medium (0.04 ≤ R ≤ 0.1), and high (R > 0.1). High-risk areas (e.g., Longxi and Shitang towns) are primarily constrained by natural hazards and socioeconomic vulnerability, while low-risk towns benefit from a robust disaster mitigation capacity. Risk typology analysis further classifies towns into natural, social–structural, capacity-driven, or mixed profiles, providing granular insights for targeted flood management. The spatial risk distribution offers a scientific basis for optimizing flood control planning and resource allocation in the district. © 2025 by the authors.
Keywords: Scopus_Alert_22_Aout_2025

Assessing Community Perception, Preparedness, and Adaptation to Urban Flood Risks in Malaysia - Kumaresen, Maniyammai; Teo, Fang Yenn; Selvarajoo, Anurita; Sivapalan, Subarna; Falconer, Roger A. (Water (Switzerland), 2025)
Urban flooding has significantly impacted the livelihoods of households and communities worldwide. It highlights the urgency of focusing on both flood preparedness and adaptation strategies to understand the community’s perception and adaptive capacity. This study investigates the levels of risk perception, flood preparedness, and adaptive capacity, while also exploring the inter-relationships among these factors within the context of urban flooding in Malaysia. A quantitative approach was employed, involving a structured questionnaire administered to residents in flood-prone urban areas across Greater Kuala Lumpur, Malaysia. A total of 212 responses were analysed using descriptive statistics, categorical index classification, and Spearman correlation analysis. The findings indicate that residents generally reported high levels of risk perception and preparedness, although adaptive capacity exhibited greater variability, with a mean score of 3.97 (SD = 0.64). Positive associations were found among risk perception, flood preparedness, and adaptive capacity. This study contributes to the existing knowledge by providing evidence on community resilience and highlighting key factors that can guide flood management policies and encourage adaptive planning at the community level. © 2025 by the authors.
Keywords: Scopus_Alert_22_Aout_2025

Identification of Critical Exposed Elements and Strategies for Mitigating Secondary Hazards in Flood-Induced Coal Mine Accidents - Yang, Xue; Liu, Chen; Pan, Langxuan; Su, Xiaona; He, Ke; Mao, Ziyu (Water (Switzerland), 2025)
Natech events, involving multi-hazard coupling and cascading effects, pose serious threats to coal mine safety. This paper addresses flood-induced Natech scenarios in coal mining and introduces a two-stage cascading analysis framework based on hazard systems theory. A tri-layered network—comprising natural hazards, exposed elements, and secondary hazards—models hazard propagation. In Stage 1, an improved adjacency information entropy algorithm with multi-hazard coupling coefficients identifies critical exposed elements. In Stage 2, Dijkstra’s algorithm extracts key risk transmission paths. A dual-dimensional classification method, based on entropy and transmission risk, is then applied to prioritize emergency responses. This method integrates the criticality of exposed elements with the risk levels associated with secondary disaster propagation paths. Case studies validate the framework, revealing: (1) Hierarchical heterogeneity in the network, with surface facilities and surrounding hydrological systems as central hubs; shaft and tunnel systems and surrounding geological systems are significantly affected by propagation from these core nodes, exhibiting marked instability. (2) Strong risk polarization in secondary hazard propagation, with core-node-originated paths being more efficient and urgent. (3) The entropy-risk classification enables targeted hazard control, improving efficiency. The study proposes chain-breaking strategies for precise, hierarchical, and timely emergency management, enhancing coal mine resilience to flood-induced Natech events. © 2025 by the authors.
Keywords: Scopus_Alert_22_Aout_2025

Response of Grain Yield to Extreme Precipitation in Major Grain-Producing Areas of China Against the Background of Climate Change—A Case Study of Henan Province - Sheng, Keding; Li, Rui; Zhang, Fengqiuli; Chen, Tongde; Liu, Peng; Hu, Yanan; Li, Bingyin; Song, Zhiyuan (Water (Switzerland), 2025)
Based on the panel data of daily meteorological stations and winter wheat yield in Henan Province from 2000 to 2023, this study comprehensively used the Mann–Kendall trend test, wavelet coherence analysis (WTC), and other methods to reveal the temporal and spatial evolution of extreme precipitation and its multi-scale stress mechanism on grain yield. The results showed the following: (1) Extreme precipitation showed the characteristics of ‘frequent fluctuation-gentle trend-strong spatial heterogeneity’, and the maximum daily precipitation in spring (RX1DAY) showed a significant uplift. The increase in rainstorm events (R95p/R99p) in the southern region during the summer is particularly prominent; at the same time, the number of consecutive drought days (CDDs > 15 d) in the middle of autumn was significantly prolonged. It was also found that 2010 is a significant mutation node. Since then, the synergistic effect of ‘increasing drought days–increasing rainstorm frequency’ has begun to appear, and the short-period coherence of super-strong precipitation (R99p) has risen to more than 0.8. (2) The spatial pattern of winter wheat in Henan is characterized by the three-level differentiation of ‘stable core area, sensitive transition zone and shrinking suburban area’, and the stability of winter wheat has improved but there are still local risks. (3) There is a multi-scale stress mechanism of extreme precipitation on winter wheat yield. The long-period (4–8 years) drought and flood events drive the system risk through a 1–2-year lag effect (short-period (0.5–2 years) medium rainstorm intensity directly impacted the production system). This study proposes a ‘sub-scale governance’ strategy, using a 1–2-year lag window to establish a rainstorm warning mechanism, and optimizing drainage facilities for high-risk areas of floods in the south to improve the climate resilience of the agricultural system against the background of climate change. © 2025 by the authors.
Keywords: Scopus_Alert_22_Aout_2025

Machine learning-based ensemble of Global climate models and trend analysis for projecting extreme precipitation indices under future climate scenarios - Kumar, G. Praveen; Dwarakish, G.S. (Environmental Monitoring and Assessment, 2025)
Monitoring changes in climatic extremes is vital, as they influence current and future climate while significantly impacting ecosystems and society. This study examines trends in extreme precipitation indices over an Indian tropical river basin, analyzing and ranking 28 Coupled Model Intercomparison Project Phase 6 (CMIP6) Global Climate Models (GCMs) based on their performance against India Meteorological Department (IMD) data. The top five performing GCMs were selected to construct multi-model ensembles (MMEs) using Machine Learning (ML) algorithms, Random Forest (RF), Support Vector Machine (SVM), Multiple Linear Regression (MLR), and the Arithmetic Mean. Statistical metrics reveal that the application of an RF model for ensembling performs better than other models. The analysis focused on six IMD-convention indices and eight indices recommended by the Expert Team on Climate Change Detection and Indices (ETCCDI). Future projections were examined for three timeframes: near future (2025–2050), mid-future (2051–2075), and far future (2076–2100) for SSP245 and SSP585 scenarios. Statistical trend analysis, the Mann-Kendall test, Sen’s Slope estimator, and Innovative Trend Analysis (ITA), were applied to the MME to assess variability and detect changes in extreme precipitation trends. Compared to SSP245, in the SSP585 scenario, Total Precipitation (PRCPTOT) shows a significant decreasing trend in the near future, mid-future, and far future and Moderate Rain (MR) shows a decreasing trend in the near future and far future of monsoon season. The findings reveal significant future trends in extreme precipitation, impacting Sustainable Development Goals (SDGs) achievement and providing crucial insights for sustainable water resource management and policy planning in the Kali River basin. © The Author(s), under exclusive licence to Springer Nature Switzerland AG 2025.
Keywords: Scopus_Alert_22_Aout_2025

The Paradigm Shift in Scientific Interest on Flood Risk: From Hydraulic Analysis to Integrated Land Use Planning Approaches - Franco, Ángela; García-Ayllón, Salvador (Water, 2025)
Floods are natural hazards that have the greatest socioeconomic impact worldwide, given that 23% of the global population live in urban areas at risk of flooding. In this field of research, the analysis of flood risk has traditionally been studied based mainly on approaches specific to civil engineering such as hydraulics and hydrology. However, these patterns of approaching the problem in research seem to be changing in recent years. During the last few years, a growing trend has been observed towards the use of methodology-based approaches oriented towards urban planning and land use management. In this context, this study analyzes the evolution of these research patterns in the field by developing a bibliometric meta-analysis of 2694 scientific publications on this topic published in recent decades. Evaluating keyword co-occurrence using VOSviewer software version 1.6.20, we analyzed how phenomena such as climate change have modified the way of addressing the study of this problem, giving growing weight to the use of integrated approaches improving territorial planning or implementing adaptive strategies, as opposed to the more traditional vision of previous decades, which only focused on the construction of hydraulic infrastructures for flood control.
Keywords: Scopus_Alert_22_Aout_2025

Quantifying the spatiotemporal dynamics of urban flooding susceptibility in the greater bay area under shared socio-economic pathways using the SD-PLUS-LightGBM framework - Zhou, Shiqi; Jia, Weiyi; Geng, Xiwen; Xu, Haowen; Diao, Haifeng; Liu, Zhiyu; Wang, Mo; Fu, Xiaoping; Wu, Yuwei; Qiao, Renlu; Wu, Zhiqiang (Resources, Conservation and Recycling, 2025)
Urbanization and climate change keep intensifying extreme rainfall events. Previous studies have explored urban flood susceptibility, yet a comprehensive approach that unifies these perspectives has remained underdeveloped. This study established a holistic framework using the SD-PLUS-LightGBM model with multiple variables under three SSP-RCP scenarios to predict spatial-temporal dynamics of flood susceptibility in the Greater Bay Area between 2030 and 2050. Compared with traditional models, LightGBM established superior predictive accuracy and operational reliability for urban flood susceptibility mapping. The results indicated a non-linear expansion of high-susceptibility zones, with SSP5–8.5 projections showing a two-fold increase in vulnerable areas by 2050 relative to 2020 baselines. Regions experiencing pronounced susceptibility transitions were expected to grow significantly (0.23 % of the total area), concentrated in historic urban cores and peri‑urban interfaces. This study offered an in-depth approach to stormwater management along with targeted recommendations for sustainable urban planning and design. © 2025
Keywords: Scopus_Alert_15_Aout_2025

Comparative assessment of flood risk to critical infrastructure: The case of Utah, USA - Clark, Austin S.; Collins, Tim (International Journal of Disaster Risk Reduction, 2025)
During and after a disaster, selected services and systems are needed to recover and maintain important functions of society. These are deemed critical infrastructure (CI). When these services are disrupted due to the impacts of a disaster, response and recovery may be slowed or halted. As flooding events are occurring more often across larger geographic extents, advancing methods for assessing risks of flooding to CI is vital. We use Utah, USA as a case study to demonstrate a novel, transferable approach for assessing fine-scale flood risks to CI across large geographic areas. Specifically, our assessment approach integrates high-resolution building footprints of schools, first responder facilities, and hospitals, and flood risk maps from a state-of-the-art big data flood model and the U.S. Federal Emergency Management Agency (FEMA). We show that 94 CI facilities across Utah are at risk of severe flooding, and that those risks to CI are almost entirely overlooked by FEMA flood risk maps. Though nearly every CI building is located outside of FEMA flood zones, FEMA maps inaccurately and incompletely represent flood risks, indicating that future flood risk assessment approaches should use flood risk maps from other sources. The approach we introduce can be used to assess flood risks to CI elsewhere, and case study results can be applied to inform flood risk reduction efforts in Utah. © 2025 Elsevier Ltd
Keywords: Scopus_Alert_15_Aout_2025

Multi-Criteria Decision Analysis for Managed Aquifer Recharge (MAR): A Flood-Responsive Approach in Milpa Alta, Mexico City - Areu-Rangel, Omar S.; Singh, Amrie; Bonasia, Rosanna (Environmental Quality Management, 2025)
Milpa Alta, located southeast of Mexico City, is a key region for environmental sustainability due to its volcanic soil, biodiversity, and critical role in aquifer recharge, which supports the city's water supply. However, rapid urbanization has severely impacted the area, causing reduced vegetation cover, increased runoff, and diminished groundwater recharge, which intensify flooding, soil erosion, and water scarcity. This study aims to identify optimal sites for managed aquifer recharge (MAR) structures in Milpa Alta through a multi-criteria analysis incorporating criteria such as topography, land use, proximity to urban areas, and drainage networks. Uniquely, hydraulic simulations of flood scenarios were integrated into the analysis to improve the precision of site selection. Geographic information systems (GIS) were used to assess and combine these criteria, providing a spatial evaluation of suitability. Results indicate that the central and northern regions of Milpa Alta, particularly around San Francisco Tecoxpa and San Antonio Tecómitl, are most suitable for MAR implementation due to their permeable soils, gentle slopes, and proximity to agricultural lands and drainage networks. These MAR structures can enhance groundwater recharge and mitigate flood risks during extreme rainfall events, with the potential to capture up to 300,000 m3 of surface runoff during a single high-intensity storm event. Despite its strengths, the study acknowledges limitations such as the absence of detailed water quality analyses and the need for sensitivity testing of the criteria weighting. This research provides an innovative approach to MAR site selection by integrating flood simulations, offering a replicable model for similar regions. Successful implementation of MAR in Milpa Alta requires addressing water quality concerns, engaging stakeholders, and ensuring compliance with regulatory frameworks. The findings emphasize MAR's potential to balance urbanization pressures with sustainable water management and flood mitigation strategies in Mexico City's rapidly developing areas. © 2025 Wiley Periodicals LLC.
Keywords: Scopus_Alert_15_Aout_2025

HyEco: A hybrid hydrodynamic-cum-ecological modelling framework to demystify flood and human-health risks over flood-prone metropolis - Deopa, Rahul; Mohanty, Mohit Prakash (Water Research X, 2025)
Urban flooding, exacerbated by climate change and unregulated urbanization, poses significant risks to the built environment. In addition to physical damage, floodwaters often mobilize a hazardous mix of untreated sewage, industrial effluents, and undesirable pollutants, leading to severe microbial contamination in the floodwaters. This study introduces “HyEco”-an integrated framework comprising high-fidelity 3-way coupled hydrodynamic and ecological modelling with an aim to capture the “unhidden tangible flood risks” and “hidden intangible public-health risks” in tandem. Focusing on Delhi, India, a densely populated metropolis prone to recurrent urban flooding and associated health crises, the framework simulates the 2023 mega-flood event. Results show that approximately 63.5 % of the region is categorized under ‘high’ to ‘very high’ flood risk zones, with over 20 % of these areas housing around 15 % of the city's dense population. The hydrodynamic model outputs were forced into the ecological model to simulate the fate and transport of microbial contamination in floodwaters. Escherichia coli concentrations ranged from 772,868 to 790,000 MPN/100 mL, far exceeding established safety thresholds. A Quantitative Microbial Risk Assessment (QMRA) reveals elevated infection probabilities, particularly among children, with risks up to 2.60×10⁻³ under repeated exposure and 8.38×10⁻⁴ to 8.57×10⁻⁴ for pedestrian splash exposures. Unlike prior approaches that examine flood and microbial risks in isolation or depend on static datasets, HyEco overcomes key methodological gaps by dynamically integrating flood and microbial processes at high spatio-temporal resolution. The HyEco framework offers a scalable and actionable tool for integrated flood risk management and climate-resilient public health planning. © 2025
Keywords: Scopus_Alert_15_Aout_2025

Entendre et comprendre les expériences de désastre par la recherche narrative - Leclerc, Typhaine; Lessard, Lily; Saint-Charles, Johanne (Intervention, 2024)
Les événements météorologiques extrêmes (EME) et les désastres qu’ils entrainent provoquent des conséquences psychosociales qui sont modulées en fonction de différents facteurs sociaux. On constate aussi que les récits médiatiques et culturels qui circulent au sujet des EME ne sont pas représentatifs de l’ensemble des expériences de personnes sinistrées : celles qui en subissent les conséquences les plus sévères tendent aussi à être celles qu’on « entend » le moins dans l’espace public. Ces personnes sont ainsi susceptibles de vivre de l’injustice épistémique, ce qui a des effets délétères sur le soutien qu’elles reçoivent. Face à ces constats s’impose la nécessité de mieux comprendre la diversité des expériences d’EME et d’explorer des stratégies pour soutenir l’ensemble des personnes sinistrées dans leur rétablissement psychosocial. Cet article soutient que la recherche narrative peut contribuer à répondre à ces objectifs. En dépeignant des réalités multiples, la recherche narrative centrée sur les récits de personnes sinistrées présente aussi un intérêt significatif pour l’amélioration des pratiques d’intervention en contexte de désastre. , Extreme weather events (EWE) and their resulting disasters cause psychosocial consequences that are moderated by different social factors. Media and cultural accounts of EWEs do not represent the full range of disaster survivor experiences, that is, those who experienced the most severe consequences also tend to be those least “heard” in the public arena. These people are therefore most likely to experience forms of epistemic injustice that negatively impact the support offered to cope with disaster. Considering these findings, there is a need to better understand the diversity of EWE experiences and explore strategies for supporting all disaster survivors in their psychosocial recovery. This article argues that narrative research can help meet these needs. By portraying the multiple realities of people affected by EWEs, narrative research focusing on the stories of disaster survivors is also of significant interest for improving intervention practices in this context.

Enhancing Research-to-Operations in Hydrological Forecasting: Innovations across Scales and Horizons - Pechlivanidis, Ilias G.; Du, Yiheng; Bennett, James; Boucher, Marie-Amélie; Chang, Annie Y. Y.; Crochemore, Louise; Dasgupta, Antara; Di Baldassarre, Giuliano; Luterbacher, Jürg; Pappenberger, Florian; Ramos, Maria-Helena; Slater, Louise; et al. (Bulletin of the American Meteorological Society, 2025)
Abstract Over the past 20 years, the Hydrological Ensemble Prediction Experiment (HEPEX) international community of practice has advanced the science and practice of hydrological ensemble prediction and its application in impact- and risk-based decision-making, fostering innovations through cutting-edge techniques and data that enhance water-related sectors. Here, we present insights from those 20 years on the key priorities for (co)creating broadly applicable hydrological forecasting systems that add value across spatial scales and time horizons. We highlight the advancement of hydrological forecasting chains through rigorous data management that incorporates diverse, high-quality data sources, data assimilation techniques, and the application of artificial intelligence (AI) to improve predictive accuracy. HEPEX has played a critical role in enhancing the reliability of water resources and water-related risk management globally by standardizing ensemble forecasting. This effort complements HEPEX’s broader initiative to strengthen research to operations, making innovative forecasting solutions both practical and accessible. Additionally, efforts have been made toward supporting the United Nations Early Warnings for All initiative through developing robust and reliable early warning systems by means of global training, education and capacity development, and the sharing of technology. Finally, we note that the integration of advanced science, user-centric methods, and global collaboration can provide a solid framework for improving the prediction and management of hydrological extremes, aligning forecasting systems with the dynamic needs of water resource and risk management in a changing climate. To effectively meet future demands, it is crucial to accelerate the integration of innovative science within operational frameworks, fostering adaptable and resilient hydrological forecasting systems globally.
Keywords: Infolettre_Ete_2025

The Needs, Challenges, and Priorities for Advancing Global Flood Research - Samadi, Vidya; Fowler, Hayley J.; Lamond, Jessica; Wagener, Thorsten; Brunner, Manuela; Gourley, Jonathan; Moradkhani, Hamid; Popescu, Ioana; Wasko, Conrad; Wright, Daniel; Wu, Huan; Zhang, Ke; et al. (WIREs Water, 2025)
ABSTRACT In recent years, numerous flood events have caused loss of life, widespread disruption, and damage across the globe. These devastating impacts highlight the importance of a better understanding of flood generating processes, their impacts, and their variability under climate and landscape changes. Here, we argue that the ability to better model flooding is underpinned by the grand challenge of understanding flood generation mechanisms and potential impacts. To address this challenge, the World Meteorological Organization‐Global Energy and Water Exchanges (GEWEX) Hydrometeorology Panel (GHP) aims to establish a Global Flood Crosscutting project to propagate flood modeling and research knowledge across regions and to synthesize results at the global scale. This paper outlines a framework for understanding the dynamics and impacts of runoff generation processes and a rationale for the role of a Global Flood Crosscutting project to address these challenges. Within this Global Flood Crosscutting project, we will establish a common terminology and methods to enable the global research community to exchange knowledge and experiences, and to design experiments toward developing actionable recommendations for more effective flood management practices and policies for improved resilience. This harmonization of rich perspectives across disciplines will foster the co‐production of knowledge primed to advance flood research, particularly in the current period of heightened climate variability and rapid change. It will create a new transdisciplinary paradigm for flood science, wherein different dimensions of mechanistic understanding and processes are rigorously considered alongside socioeconomic impacts, early warning communications, and longer‐term adaptation to alleviate flood risks in society.
Keywords: Infolettre_Ete_2025

Full-scale characterization of the effects of a bioretention system on water quality and quantity following the replacement of a mixed stormwater and combined sewer system - Le Cauchois, Pia; Doucet, Samuel; Bouattour, Ons; McQuaid, Natasha; Beral, Henry; Kõiv-Vainik, Margit; Bichai, Françoise; McCarthy, David; St-Laurent, Julien; Dagenais, Danielle; Bennekrela, Nesrine; Guerra, Juan; et al. (Blue-Green Systems, 2025)
ABSTRACT Urbanization is leading to more frequent flooding as cities have more impervious surfaces and runoff exceeds the capacity of combined sewer systems. In heavy rainfall, contaminated excess water is discharged into the natural environment, damaging ecosystems and threatening drinking water sources. To address these challenges aggravated by climate change, urban blue-green water management systems, such as bioretention cells, are increasingly being adopted. Bioretention cells use substrate and plants adapted to the climate to manage rainwater. They form shallow depressions, allowing infiltration, storage, and gradual evacuation of runoff. In 2018, the City of Trois-Rivières (Québec, Canada) installed 54 bioretention cells along a residential street, several of which were equipped with access points to monitor performance. Groundwater quality was monitored through the installation of piezometers to detect potential contamination. This large-scale project aimed to improve stormwater quality and reduce sewer flows. The studied bioretention cells reduced the flow and generally improved water quality entering the sewer system, as well as the quality of stormwater, with some exceptions. Higher outflow concentrations were observed for contaminants such as manganese and nitrate. The results of this initiative provide useful recommendations for similar projects for urban climate change adaptation.
Keywords: Infolettre_Ete_2025

The Impact of Flood Adaptation Measures on Affected Population’s Mental Health: A mixed method Scoping Review - El-Mousawi, Fatima; Ortiz, Ariel Mundo; Berkat, Rawda; Nasri, Bouchra (Cold Spring Harbor Laboratory, 2023)
AbstractThe frequency and severity of floods has increased in different regions of the world due to climate change. Although the impact of floods on human health has been extensively studied, the increase in the segments of the population that are likely to be impacted by floods in the future makes it necessary to examine how adaptation measures impact the mental health of individuals affected by these natural disasters. The goal of this scoping review is to document the existing studies on flood adaptation measures and their impact on the mental health of affected populations, in order to identify the best preventive strategies as well as limitations that deserve further exploration. This study employed the methodology of the PRISMA-ScR extension for scoping reviews to systematically search the databases Medline and Web of Science to identify studies that examined the impact of adaptation measures on the mental health of flood victims. The database queries resulted in a total of 857 records from both databases. Following two rounds of screening, 9 studies were included for full-text analysis. Most of the analyzed studies sought to identify the factors that drive resilience in flood victims, particularly in the context of social capital (6 studies), whereas the remaining studies analyzed the impact of external interventions on the mental health of flood victims, either from preventive or post-disaster measures (3 studies). There is a very limited number of studies that analyze the impact of adaptation measures on the mental health of populations and individuals affected by floods, which complicates the generalizability of their findings. There is a need for public health policies and guidelines for the development of flood adaptation measures that adequately consider a social component that can be used to support the mental health of flood victims.

Éduquer aux risques dès l’école primaire: de la représentation à la conscientisation - Julien, Marie-Pierre; Bédouret, David; Chalmeau, Raphaël; Mainar, Christine Vergnolle; Léna, Jean-Yves; Calvet, Anne (VertigO - la revue électronique en sciences de l'environnement, 2021)
Le territoire de la vallée du Gave de Gavarnie a connu un épisode d’inondation/crue particulièrement catastrophique en 2013, ayant entrainé de forts dégâts matériels et des pertes humaines. Dans ce contexte, la culture du risque est un enjeu tant pour les acteurs de la gestion de ce territoire que pour les citoyens, d’autant plus que les risques présents y sont multiples (avalanches, glissements de terrain et séismes). Dans cette perspective, l’école peut jouer un rôle déterminant à travers la mise en place de projets d’éducations au(x) risque(s). Ce type d’éducation doit commencer par la perception et la conscience du (des) risque(s), rendues possibles par le vécu et/ou par la culture du groupe dans lequel l’élève vit. Cette étude a pour objectif d’examiner les représentations et la perception du risque des élèves d’une école élémentaire française située sur une commune fortement impactée par cette crue, et l’évolution de ces représentations et cette perception un an après la mise en œuvre du projet éducatif. Les résultats montrent une représentation plurielle du risque par les élèves avec des différences entre classes. La classe de CP-CE (enfants âgés de 6 à 8 ans) associe essentiellement le risque à l’aléa naturel (avalanche, inondation…) alors que les élèves en CM (enfants âgés de 9 à 10 ans) sont centrés sur ce qui pourrait leur arriver (accident, maladie…). Le risque inondation/crue est dans un premier temps très peu évoqué dans les représentations des élèves, mais lorsque les activités pédagogiques permettent de contextualiser cette notion sur leur territoire, il est alors plus fortement perçu.

Investigating incomplete mixing models in cross junctions under real-world conditions of water distribution networks - Yousefian, Reza; Duchesne, Sophie; Schwarz, Pierre-Olivier (Water Supply, 2024)
Questions have been raised about the correctness of water quality models with complete mixing assumptions in cross junctions of water distribution systems. Recent developments in the mixing phenomenon within cross junctions of water distribution networks (WDNs) have heightened the need for evaluating the existing incomplete mixing models under real-world conditions. Therefore, in this study, two cross junctions with pipe diameters of 100 Â 100 Â 100 Â 100 mm and 150 Â 150 Â 150 Â 150 mm were employed in laboratory experiments to evaluate six existing incomplete mixing models for 25 ﬂow rate scenarios ranging between 1.5 and 3.0 L/s. It was observed that within the same ﬂow rate scenario, the degree of mixing in a cross junction with a pipe relative roughness of 6.00 Â 10À5 (pipe diameter of 25 mm) was higher than that in a cross junction with a pipe relative roughness of 3.00 Â 10À5 (pipe diameter of 50 mm) and smaller. Considering the real-world size of pipes in evaluating the incomplete mixing models showed that two incomplete mixing models, AZRED and the one by Shao et al., had the best accordance with the results of the laboratory experiments.

Integration of Incomplete Mixing at Junctions of Water Distribution Networks in Contamination Source Identification Tools - Yousefian, Reza; Émond, Laurent; Duchesne, Sophie (Journal of Water Resources Planning and Management, 2025)
The water quality models used in contamination source identification (CSI) tools assume complete mixing at the junctions of drinking water distribution networks. Two extensions of the contamination status algorithm (CSA)—a CSI tool that employs water quality models in a reverse-time manner—were accordingly developed in this study, one assuming complete mixing (CSA-CMX) and the other assuming incomplete mixing (CSA-IMX) at cross-junctions. Both algorithms identified contamination sources based on the results of grab sampling at iteratively suggested locations. The performances of CSA-CMX and CSA-IMX were evaluated through laboratory experiments using three contamination identification problems: CSA-IMX identified the contamination source in all three problems, whereas CSA-CMX identified the contamination source in only one. Furthermore, the specificity (i.e., the ability to distinguish the real contamination source from other possible contamination sources) was higher for CSA-IMX than for CSA-CMX in two of the three problems. Therefore, the incomplete mixing assumption was confirmed to be a crucial factor in CSI tools.

Evaluating real-time control of stormwater drainage network and green stormwater infrastructure for enhancing flooding resilience under future rainfall projections - Li, Jiada; Burian, Steven J. (Resources, Conservation and Recycling, 2023)
Traditional stormwater control measures are designed to handle system loadings induced by fixed-size storm events. However, climate change is predicted to alter the frequency and intensity of flooding events, stimulating the need to explore another more adaptive flooding solution like real-time control (RTC). This study assesses the performance of RTC to mitigate impacts of climate change on urban flooding resilience. A simulated, yet realistic, urban drainage system in Salt Lake City, Utah, USA, shows that RTC improves the flooding resilience by up to 17% under climatic rainfall changes. Compared with green stormwater infrastructure (GSI), RTC exhibits a lower resistibility, lower flooding failure level, and higher recovery rate in system performance curves. Results articulate that keeping RTC's performance consistent under ‘back-to-back’ storms requires a tradeoff between upstream dynamical operation and downstream flooding functionality loss. This research suggests that RTC provides a path towards smart and resilient stormwater management strategy.

Adaptation of Dual Drainage to Control Flooding and Enhance Combined Sewer Systems in Highly Urbanized Areas - Ossa Ossa, Juan Esteban; Duchesne, Sophie; Pelletier, Geneviève (2024)
Combined sewer surcharges in densely urbanized areas have become more frequent due to the expansion of impervious surfaces and intensified precipitation caused by climate change. These surcharges can generate system overflows, causing urban flooding and pollution of urban areas. This paper presents a novel methodology to mitigate sewer system surcharges and control surface water. In this methodology, flow control devices and urban landscape retrofitting are proposed as strategies to reduce water inflow into the sewer network and manage excess water on the surface during extreme rainfall events. For this purpose, a 1D/2D dual drainage model was developed for two case studies located in Montreal, Canada. Applying the proposed methodology to these two sites led to a reduction of the volume of wastewater overflows by 100% and 86%, and a decrease in the number of surface overflows by 100% and 71%, respectively, at the two sites for a 100-year return period 3-h Chicago design rainfall. It also controlled the extent of flooding, reduced the volume of uncontrolled surface floods by 78% and 80% and decreased flooded areas by 68% and 42%, respectively, at the two sites for the same design rainfall.

Flood inundation modeling in ungauged basins using Unmanned Aerial Vehicles imagery - Yavari, Adel; Homayouni, Saeid; Oubennaceur, Khalid; Chokmani, Karem (Earth Observation and Geomatics Engineering, 2020)
This paper presents a new framework for floodplain inundation modeling in an ungauged basin using unmanned aerial vehicles (UAVs) imagery. This method is based on the integrated analysis of high-resolution ortho-images and elevation data produced by the structure from motion (SfM) technology. To this end, the Flood-Level Marks (FLMs) were created from high-resolution UAV ortho-images and compared to the flood inundated areas simulated using the HEC-RAS hydraulic model. The flood quantiles for 25, 50, 100, and 200 return periods were then estimated by synthetic hydrographs using the Natural Resources Conservation Service (NRCS). The proposed method was applied to UAV image data collected from the Khosban village, in Taleghan County, Iran, in the ungauged sub-basin of the Khosban River. The study area is located along one kilometre of the river in the middle of the village. The results showed that the flood inundation areas modeled by the HEC-RAS were 33%, 19%, and 8% less than those estimated from the UAV’s FLMs for 25, 50, and 100 years return periods, respectively. For return periods of 200 years, this difference was overestimated by more than 6%, compared to the UAV’s FLM. The maximum flood depth in our four proposed scenarios of hydraulic models varied between 2.33 to 2.83 meters. These analyses showed that this method, based on the UAV imagery, is well suited to improve the hydraulic modeling for seasonal inundation in ungauged rivers, thus providing reliable support to flood mitigation strategies

A PCA spatial pattern based artificial neural network downscaling model for urban flood hazard assessment - Carreau, J.; Guinot, V. (Advances in Water Resources, 2021)

Impacts et coûts indirects des stresseurs secondaires sur la santé biopsychosociale des sinistrés des inondations de 2019 - Maltais, Danielle; Bourdeau-Brien, Michaël; Gilbert, Simon; Normandin, Julie-Maude; Tchassem Pinlap, Jonas; Généreux, Mélissa; Landaverde, Elsa; Boudreault, Mathieu (2023)
Les inondations de 2017 et 2019 au Québec ont affecté respectivement 293 et 240 municipalités. Ces inondations ont généré une cascade d’évènements stressants (stresseurs primaires et secondaires) qui ont eu des effets sur la santé mentale de la population et retardé le processus de rétablissement des individus. Cette période de rétablissement peut s’échelonner sur plusieurs mois voire plusieurs années. Cette étude s’inscrit dans la spécificité de la recherche mixte mise de l’avant à travers trois stratégies de recherche, réalisées de façon séquentielle : 1) sondage populationnelle réalisé auprès de 680 personnes, 2) analyse de documents produits par les organisations participant au processus de rétablissement social des sinistrés, ou sur des analyses externes portant sur ces interventions de rétablissement et 3) entrevues semi-dirigées auprès de 15 propriétaires occupants ayant complété une demande d’indemnisation à la suite des inondations de 2019 et auprès de 11 professionnels et gestionnaires participant au processus de rétablissement social. Les entrevues semi-dirigées et les questionnaires complétés par les personnes sinistrées lors des inondations de 2019 démontrent que les principales sources de stress ayant des impacts sur la santé et le bien-être des répondants sont : 1) l’absence d’avertissement et la vitesse de la montée des eaux; 2) l’obligation de se relocaliser et la peur d’être victime de pillage; 3) le manque de solidarité et d’empathie de la part de certains employés du MSP; 4) la gestion des conflits familiaux; 5) la gestion de problèmes de santé nouveaux ou préexistants; 6) la complexité des demandes d’indemnisation; 7) la lourdeur et les délais des travaux de nettoyage ou de restauration; 8) les indemnités inférieures aux coûts engendrés par l’inondation; 9) les pertes matérielles subies, particulièrement ceux d’une valeur de plus de 50 000 $; et 10) la diminution anticipée de la valeur de sa résidence. À cela s’ajoute l’insatisfaction à l’égard du programme d’indemnisation du gouvernement du Québec (PGIAF) qui fait plus que doubler la prévalence des symptômes de stress post-traumatique. Les inondations entraînent également une perte de satisfaction ou de bien-être statistiquement significative. La valeur monétaire de cette perte de jouissance peut être exprimée en équivalent salaires. En moyenne, cette diminution du bien-être équivaut à une baisse de salaire de 60 000$ pour les individus ayant vécu une première inondation et à 100 000$ pour les individus ayant vécu de multiples inondations. Ces résultats suggèrent que les coûts indirects et intangibles représentent une part importante des dommages découlant des inondations. Ce projet de recherche vise également à analyser l’application du PGIAF et son influence sur les stresseurs vécus par les sinistrés dans le contexte de la pandémie de COVID-19. La principale recommandation de cette étude repose sur une analyse de documents, un sondage populationnel et des entrevues semi-dirigées. Ainsi, s’attaquer à la réduction de principaux stresseurs nécessite 1) d’améliorer la gouvernance du risque d’inondation, 2) d’intensifier la communication et le support aux sinistrés, et 3) de revoir les mécanismes d’indemnisation existants.

Trajectoires et visées de l'hydrogéomorphologie au Québec - Buffin‐Bélanger, Thomas; Lachapelle, Félix; Biron, Pascale; Boivin, Maxime (Canadian Geographies / Géographies canadiennes, 2024)
Résumé L'hydrogéomorphologie étudie la dynamique des rivières en se concentrant sur les interactions liant la structure des écoulements, la mobilisation et le transport des sédiments et les morphologies qui caractérisent les cours d'eau et leur bassin‐versant. Elle offre un cadre d'analyse et des outils pour une meilleure intégration des connaissances sur la dynamique des rivières pour la gestion des cours d'eau au sens large, et plus spécifiquement, pour leur restauration, leur aménagement et pour l'évaluation et la prévention des risques liés aux aléas fluviaux. Au Québec, l'hydrogéomorphologie émerge comme contribution significative dans les approches de gestion et d'évaluation du risque et se trouve au cœur d'un changement de paradigme dans la gestion des cours d'eau par lequel la restauration des processus vise à augmenter la résilience des systèmes et des sociétés et à améliorer la qualité des environnements fluviaux. Cette contribution expose la trajectoire de l'hydrogéomorphologie au Québec à partir des publications scientifiques de géographes du Québec et discute des visées de la discipline en recherche et en intégration des connaissances pour la gestion des cours d'eau . , Abstract Hydrogeomorphology studies river dynamics, focusing on the interactions between flow structure, sediment transport, and the morphologies that characterize rivers and their watersheds. It provides an analytical framework and tools for better integrating knowledge of river dynamics into river management in the broadest sense, and more specifically, into river restoration as well as into the assessment and prevention of risks associated with fluvial hazards. In Quebec, hydrogeomorphology is emerging as a significant contribution to risk assessment and management approaches, and is at the heart of a paradigm shift in river management whereby process restoration aims to increase the resilience of fluvial systems and societies, and improve the quality of fluvial environments. This contribution outlines the trajectory of hydrogeomorphology in Quebec, based on scientific publications by Quebec geographers, and discusses the discipline's aims in research and knowledge integration for river management . , Messages clés Les géographes du Québec ont contribué fortement au développement des connaissances et outils de l'hydrogéomorphologie. L'hydrogéomorphologie a évolué d'une science fondamentale à une science où les connaissances fondamentales sont au service de la gestion des cours d'eau. L'hydrogéomorphologie et le cortège de connaissances et d'outils qu'elle promeut font de cette discipline une partenaire clé pour une gestion holistique des cours d'eau.

Societal drivers for the integration of hydrogeomorphology and human benefits in river restoration projects - Gariépy‐Girouard, Étienne; Buffin‐Bélanger, Thomas; Biron, Pascale M. (River Research and Applications, 2025)
Abstract Integrating hydrogeomorphological (HGM) principles into the restoration of degraded rivers can achieve sustainable results and provide various human benefits. HGM principles mainly involve understanding the context and processes that shape a fluvial system before any intervention, in order to support its dynamism and to align with its potential functioning and uses. Despite recent management approaches inspired by HGM principles, most restoration projects carried out in Quebec (Canada) are not process‐based and target specific one‐dimensional objectives. Although there is an overall lack of post‐project monitoring, several projects appear to have failed or had mixed success. This research aims to shed light on the diversity of societal drivers behind river restoration projects and to examine how they influence the integration of HGM principles and human benefits. Four restoration projects were characterized through participant observation and interviews with the organizations running them. Representatives of two ministries involved in river restoration and management were also interviewed. The results show that projects were mainly shaped by public acceptance disregarding HGM principles, which can lead to poorly‐informed action. Project funding and stakeholders' expertise have also challenged project implementation and played a key role in defining their objectives. The addition of these components improve the current analytical frameworks for identifying river restoration objectives. Depending on specific sociocultural, political and legislative contexts, funding programs and stakeholders' expertise may either facilitate or restrict the integration of HGM principles and human benefits in the projects. Recognizing these key drivers reframes river restoration as a fundamentally social activity and enlightens how they could impel innovative approaches towards more sustainable results.

Flood Risk Management via Risk Communication, Cognitive Appraisal, Collective Efficacy, and Community Action - Lin, Carolyn A. (Sustainability, 2023)
Climate change and more frequent severe storms have caused persistent flooding, storm surges, and erosion in the northeastern coastal region of the United States. These weather-related disasters have continued to generate negative environmental consequences across many communities. This study examined how coastal residents’ exposure to flood risk information and information seeking behavior were related to their threat appraisal, threat-coping efficacy, and participation in community action in the context of building social resilience. A random sample of residents of a coastal community in the Northeastern United States was selected to participate in an online survey (N = 302). Key study results suggested that while offline news exposure was weakly related to flood vulnerability perception, online news exposure and mobile app use were both weakly associated with flood-risk information seeking. As flood vulnerability perception was strongly connected to flood severity perception but weakly linked to lower self-efficacy beliefs, flood severity perception was weakly and moderately associated with response-efficacy beliefs and information seeking, respectively. Furthermore, self-efficacy beliefs, response efficacy beliefs, and flood-risk information seeking were each a weak or moderate predictor of collective efficacy beliefs. Lastly, flood risk information-seeking was a strong predictor and collective efficacy beliefs were a weak predictor of community action for flood-risk management. This study tested a conceptual model that integrated the constructs from risk communication, information seeking, and protection motivation theory. Based on the modeling results reflecting a set of first-time findings, theoretical and practical implications are discussed.

The role of public relations in building community resilience to natural disasters: perspectives from Sri Lanka and New Zealand - Dharmasena, M. K. Gayadini Imesha; Toledano, Margalit; Weaver, C. Kay (Journal of Communication Management, 2020)
The paper identifies a role for public relations in disaster management by analysing disaster and communication managers' understanding of community resilience and their use of communication in the context of two different cultural environments.,The research study comprised 51 in-depth qualitative interviews with disaster managers in Sri Lanka and New Zealand, which were thematically analysed using the software programme NVivo 10.,The study identified cultural differences in Sri Lanka and New Zealand that impact on how managers' communicate in natural disaster situations. The findings indicated that public relations’ understanding of communities’ cultures, their communication, networking and lobbying skills could further enhance the effectiveness of efforts to build community resilience to disasters.,Nations are complex multicultural realities; the findings cannot be generalized to make claims about how natural disasters are managed in different national contexts.,The paper identifies the unrealized potential of public relations’ expertise in communication, community relations, networking and lobbying to contribute to building community resilience to natural disasters.,By supporting efforts to build community resilience to disasters, public relations practitioners can contribute to social well-being in times of catastrophic natural disasters.,The paper adds an innovative perspective to public relations crisis literature by identifying the potential contribution of public relations’ concepts and practices to build community resilience to natural disasters. It demonstrates how sociocultural differences may affect disaster communication strategies.

Lessons learned from the NSERC Canadian FloodNet on improving flood forecasting systems and management capacity - Xenopoulos, Marguerite; Coulibaly, Paulin; Anctil, Francois; Burn, Donald; Nguyen, Van-Thanh-Van (AGU Fall Meeting Abstracts, 2021)
In Canada, floods are the most common largely distributed hazard to life, property, the economy, water systems, and the environment costing the Canadian economy billions of dollars. Arising from this is FloodNet: a transdisciplinary strategic research network funded by Canadas Natural Sciences and Engineering Research Council, as a vehicle for a concerted nation-wide effort to improve flood forecasting and to better assess risk and manage the environmental and socio-economic consequences of floods. Four themes were explored in this network which include 1) Flood regimes in Canada; 2) Uncertainty of floods; 3) Development of a flood forecasting and early warning system and 4) Physical, socio-economic and environmental effects of floods. Over the years a range of statistical, hydrologic, modeling, and economic and psychometric analyses were used across the themes. FloodNet has made significant progress in: assessing spatial and temporal variation of extreme events; updating intensity-duration-frequency (IDF) curves; improving streamflow forecasting using novel techniques; development and testing of a Canadian adaptive flood forecasting and early warning system (CAFFEWS); a better understanding of flood impacts and risk. Despite these advancements FloodNet ends at a time when the World is still grappling with severe floods (e.g., Europe, China, Africa) and we report on several lessons learned. Mitigating the impact of flood hazards in Canada remains a challenging task due to the countrys varied geography, environment, and jurisdictional political boundaries. Canadian technical guide for developing IDF relations for infrastructure design in the climate change context has been recently updated. However, national guidelines for flood frequency analyses are needed since across the country there is not a unified approach to flood forecasting as each jurisdiction uses individual models and procedures. From the perspective of risk and vulnerability, there remains great need to better understand the direct and indirect impacts of floods on society, the economy and the environment.

Development of interactive diagnostic tools and metrics for the socio-economic consequences of floods - Parent, Annie-Claude; Fournier, Frédéric; Anctil, François; Morse, Brian; Baril-Boyer, Jean-Philippe; Marceau, Pascal (2021)
Spring floods have generated colossal damages to residential areas in the Province of Quebec, Canada, in 2017 and 2019. Government authorities need accurate modelling of the impact of theoretical floods in order to prioritize pre-disaster mitigation projects to reduce vulnerability. They also need accurate modelling of forecasted floods in order to direct emergency responses. We present a governmental-academic collaboration that aims at modelling flood impact for both theoretical and forecasted flooding events over all populated river reaches of meridional Quebec. The project, funded by the ministère de la Sécurité publique du Québec (Quebec ministry in charge of public security), consists in developing a diagnostic tool and methods to assess the risk and impacts of flooding. Tools under development are intended to be used primarily by policy makers. The project relies on water level data based on the hydrological regimes of nearly 25,000 km of rivers, on high-precision digital terrain models, and on a detailed database of building footprints and characterizations. It also relies on 24h and 48h forecasts of maximum flow for the subject rivers. The developed tools integrate large data sets and heterogeneous data sources and produce insightful metrics on the physical extent and costs of floods and on their impact on the population. The software also provides precise information about each building affected by rising water, including an estimated cost of the damages and impact on inhabitants.

Disaster disparities and differential recovery in New Orleans - Finch, Christina; Emrich, Christopher T.; Cutter, Susan L. (Population and Environment, 2010)
The historical disparities in the socio-demographic structure of New Orleans shaped the social vulnerability of local residents and their responses to Hurricane Katrina and its aftermath. These disparities, derived from race, class, gender, and age differences, have resulted in the uneven impact of the catastrophe on various communities in New Orleans, and importantly, their ability to recover. This article examines how the pre-existing social vulnerabilities within New Orleans interacted with the level of flood exposure to produce inequities in the socio-spatial patterns of recovery. Utilizing a combination of statistical and spatial approaches, we found a distinct geographic pattern to the recovery suggesting that the social burdens and impacts from Hurricane Katrina are uneven—the less flooded and less vulnerable areas are recovering faster than tracts with more vulnerable populations and higher levels of flooding. However, there is a more nuanced story, which suggests that it is neighborhoods in the mid-range of social vulnerability where recovery is lagging. While private resources and government programs help groups in the high and low categories of social vulnerability, the middle group shows the slowest rates of recovery. Further, it appears that the congressionally funded State of Louisiana Road Home Program (designed to provide compensation to Louisiana’s homeowners who suffered impacts by Hurricanes Katrina and Rita for the damage to their home) is not having a significant effect in stimulating recovery within the city.

Population Displacement and Housing Dilemmas Due to Catastrophic Disasters - Levine, Joyce N.; Esnard, Ann-Margaret; Sapat, Alka (Journal of Planning Literature, 2007)
As Hurricane Katrina revealed, coastal communities have become far more vulnerable to tropical storms and the long-term displacement of residents. Yet, because the emergency management model presumes that recovery quickly follows response, governments focus only on short-term, localized displacement. However, long-term and long-distance displacement exposes a gray area between immediate shelter and permanent housing, along with concerns about vulnerability, housing availability, and land development. We begin this article by discussing the transition between response and recovery. We then review literature regarding social vulnerability, displacement, provision of temporary housing, households' return decisions, and disaster-driven land development and housing construction processes. We close with thoughts on future research to increase planners' understanding of the issues involved and to help them craft effective policies.

Coupling the maximum overlap discrete wavelet transform and long short-term memory networks for irrigation flow forecasting - Mouatadid, Soukayna; Adamowski, Jan F.; Tiwari, Mukesh K.; Quilty, John M. (Agricultural Water Management, 2019)

Disaster risk reduction and the limits of truisms: Improving the knowledge and practice interface - Nohrstedt, Daniel; Parker, Charles F.; von Uexkull, Nina; Mård, Johanna; Nyberg, Lars; Petrova, Kristina; Albrecht, Frederike; Göteman, Malin; Hileman, Jacob; Messori, Gabriele; Di Baldassarre, Giuliano (International journal of disaster risk reduction, 2021)
Abstract Action toward strengthened disaster risk reduction (DRR) ideally builds from evidence-based policymaking to inform decisions and priorities. This is a guiding principle for the Sendai Framework for Disaster Risk Reduction (SFDRR), which outlines priorities for action to reduce disaster risk. However, some of these practical guidelines conceal oversimplified or unsubstantiated claims and assumptions, what we refer to as “truisms”, which, if not properly addressed, may jeopardize the long-term goal to reduce disaster risks. Thus far, much DRR research has focused on ways to bridge the gap between science and practice while devoting less attention to the premises that shape the understanding of DRR issues. In this article, written in the spirit of a perspective piece on the state of the DRR field, we utilize the SFDRR as an illustrative case to identify and interrogate ten selected truisms, from across the social and natural sciences, that have been prevalent in shaping DRR research and practice. The ten truisms concern forecasting, loss, conflict, migration, the local level, collaboration, social capital, prevention, policy change, and risk awareness. We discuss central claims associated with each truism, relate those claims to insights in recent DRR scholarship, and end with suggestions for developing the field through advances in conceptualization, measurement, and causal inference.

Spatio-temporal analysis of rainfall trends in Chhattisgarh State, Central India over the last 115 years - Nema, Manish K.; Khare, Deepak; Adamowski, Jan; Chandniha, Surendra K. (Journal of Water and Land Development, 2018)
Abstract A quantitative and qualitative understanding of the anticipated climate-change-driven multi-scale spatio-temporal shifts in precipitation and attendant river flows is crucial to the development of water resources management approaches capable of sustaining and even improving the ecological and socioeconomic viability of rain-fed agricultural regions. A set of homogeneity tests for change point detection, non-parametric trend tests, and the Sen’s slope estimator were applied to long-term gridded rainfall records of 27 newly formed districts in Chhattisgarh State, India. Illustrating the impacts of climate change, an analysis of spatial variability, multi-temporal (monthly, seasonal, annual) trends and inter-annual variations in rainfall over the last 115 years (1901–2015 mean 1360 mm·y −1 ) showed an overall decline in rainfall, with 1961 being a change point year (i.e., shift from rising to declining trend) for most districts in Chhattisgarh. Spatio-temporal variations in rainfall within the state of Chhattisgarh showed a coefficient of variation of 19.77%. Strong inter-annual and seasonal variability in regional rainfall were noted. These rainfall trend analyses may help predict future climate scenarios and thereby allow planning of effective and sustainable water resources management for the region.

Multi-method Modeling Framework for Support of Integrated Water Resources Management - Nikolic, Vladimir V.; Simonovic, Slobodan P. (Environmental Processes, 2015)
The contemporary definition of integrated water resources management (IWRM) is introduced to promote a holistic approach in water engineering practices. IWRM deals with planning, design and operation of complex systems in order to control the quantity, quality, temporal and spatial distribution of water with the main objective of meeting human and ecological needs and providing protection from water related disasters. This paper examines the existing decision making support in IWRM practice, analyses the advantages and limitations of existing tools, and, as a result, suggests a generic multi-method modeling framework that has the main goal to capture all structural complexities of, and interactions within, a water resources system. Since the traditional tools do not provide sufficient support, this framework uses multi-method simulation technique to examine the codependence between water resources system and socioeconomic environment. Designed framework consists of (i) a spatial database, (ii) a traditional process-based model to represent the physical environment and changing conditions, and (iii) an agent-based spatially explicit model of socio-economic environment. The multi-agent model provides for building virtual complex systems composed of autonomous entities, which operate on local knowledge, possess limited abilities, affect and are affected by local environment, and thus, enact the desired global system behavior. Agent-based model is used in the presented work to analyze spatial dynamics of complex physical-social-economic-biologic systems. Based on the architecture of the generic multi-method modeling framework, an operational model for the Upper Thames River basin, Southwestern Ontario, Canada, is developed in cooperation with the local conservation authority. Six different experiments are designed by combining three climate and two socio-economic scenarios to analyze spatial dynamics of a complex physical-social-economic system of the Upper Thames River basin. Obtained results show strong dependence between changes in hydrologic regime, in this case surface runoff and groundwater recharge rates, and regional socio-economic activities.

Mapping SWE in near real time across a large territory using a particle filter - Odry, Jean; Boucher, Marie-Amélie; Lachance Cloutier, Simon; Turcotte, Richard; Saint-Louis, Pierre-Yves (2020)
In snow-prone regions, snowmelt is one of the main drivers of runoff. For operational flood forecasting and mitigation, the spatial distribution of snow water equivalent (SWE) in near real time is necessary. In this context, in situ observations of SWE provide a valuable information. Nonetheless, the high spatial variability of snowpack characteristics makes it necessary to implement some kind of snow modelling to get a spatially continuous estimation. Data assimilation is thus a useful approach to combine information from both observation and modeling in near real-time. For example, at the provincial government of Quebec (eastern Canada), the HYDROTEL Snowpack Model is applied on a daily basis over a 0.1 degree resolution mesh covering the whole province. The modelled SWE is corrected in real time by in situ manual snow survey which are assimilated using a spatial particles filter (Cantet et al., 2019). This assimilation method improves the reliability of SWE estimation at ungauged sites. The availability of manual snow surveys is however limited both in space and time. These measurements are conducted on a bi-weekly basis in a limited number of sites. In order to further improve the temporal and spatial observation coverage, alternative sources of data should be considered. In this research, it is hypothesized that data gathered by SR50 sonic sensors can be assimilated in the spatial particle filter to improve the SWE estimation. These automatic sensors provide hourly measurements of snow depth and have been deployed in Quebec since 2005. Beforehand, probabilistic SWE estimations were derived from the SR50 snow depth measurements using an ensemble of artificial neural networks (Odry et al. 2019). Considering the nature of the data and the conversion process, the uncertainty associated with this dataset is supposed larger than for the manual snow surveys. The objective of the research is to evaluate the potential interest of adding this lower-quality information in the assimilation framework. The addition of frequent but uncertain data in the spatial particle filter required some adjustments in term of assimilation frequency and particle resampling. A reordering of the particles was implemented to maintain the spatial coherence between the different particles. With these changes, the consideration of both manual snow surveys and SR50 data in the spatial particle filter reached performances that are comparable to the initial particle filter that combines only the model and manual snow survey for estimating SWE in ungauged sites. However, the addition of SR50 data in the particle filter allows for continuous information in time, between manual snow surveys. References: Cantet, P., Boucher, M.-A., Lachance-Coutier, S., Turcotte, R., Fortin, V. (2019). Using a particle filter to estimate the spatial distribution of the snowpack water equivalent. J. Hydrometeorol, 20. Odry, J., Boucher, M.-A., Cantet,P., Lachance-Cloutier, S., Turcotte, R., St-Louis, P.-Y. (2019). Using artificial neural networks to estimate snow water equivalent from snow depth. Canadian water ressources journal (under review)

Thermal exposure risk in different life stages of Chinook salmon in the Nechako River system, British Columbia - Oyinlola, Muhammed Alolade; Khorsandi, Mostafa; Mayer, Noa; Butler, Natalie; Wert, Jacey C. Van; Eliason, Erika J.; Arsenault, Richard; Brauner, Colin J.; Hinch, Scott G.; St-Hilaire, Andre (2024)
Abstract Climate change is affecting freshwater systems, leading to increased water temperatures, which is posing a threat to freshwater ecological communities. In the Nechako River, a water management program has been in place since the 1980s to maintain water temperatures at 20°C during the migration of Sockeye salmon. However, the program's effectiveness in mitigating the impacts of climate change on resident species like Chinook salmon's thermal exposure is uncertain. In this study, we utilised the CEQUEAU hydrological model and life stage-specific physiological data to evaluate the consequences of the current program on Chinook salmon's thermal exposure under two contrasting climate change and socio-economic scenarios (SSP2-4.5 and SSP5-8.5). The results indicate that the thermal exposure risk is projected to be above the optimal threshold for parr and adult life stages under both scenarios relative to the 1980s. These life stages could face an increase in thermal exposure ranging from up to 2 and 5 times by 2090s relative to the 1980s during the months they occurred under the SSP5-8.5 scenario, including when the program is active (July 20th to August 20th). Additionally, our study shows that climate change will result in a substantial rise in cumulative heat degree days, ranging from 1.9 to 5.8 times (2050s) and 2.9 to 12.9 times (2090s) in comparison to the 1980s under SSP5-8.5. Our study highlights the need for a holistic approach to review the current Nechako management plan and consider all species in the Nechako River system in the face of climate change.

Institutions and the losses from natural disasters - Raschky, Paul A. (Natural Hazards and Earth System Sciences, 2008)
Abstract. Natural hazards can be seen as a function of a specific natural process and human (economic) activity. Whereby the bulk of literature on natural hazard management has its focus on the natural process, an increasing number of scholars is emphasizing the importance of human activity in this context. Existing literature has identified certain socio-economic factors that determine the impact of natural disasters on society. The purpose of this paper is to highlight the effects of the institutional framework that influences human behavior by setting incentives and to point out the importance of institutional vulnerability. Results from an empirical investigation of large scale natural disasters between 1984 and 2004 show that countries with better institutions experience less victims and lower economic losses from natural disasters. In addition, the results suggest a non-linear relationship between economic development and economic disaster losses. The suggestions in this paper have implications for the discussion on how to deal with the adverse effects of natural hazards and how to develop efficient adaption strategies.

Human–water research: discussion of “guiding principles for hydrologists conducting interdisciplinary research and fieldwork with participants” - Thaler, Thomas (Hydrological Sciences Journal-journal Des Sciences Hydrologiques, 2022)
Rangecroft et al. provide an important and interesting paper on the challenges of interdisciplinary research and fieldwork with participants in water resource management. The paper shows the challenges of interaction between their research areas and demonstrates the importance of how a researcher interacts with their selected study sites. My key points reflect the use of different methodologies within social and natural sciences and across them as well as the main challenge of who has the power to influence the research directions. Research is not value-free and is highly influenced by one’s own training and knowledge, which needs to be addressed in the research activities. Finally, an option might be to move beyond interdisciplinary constraints and to work within a stronger transdisciplinary framework. Water research very much needs to interact with non-academic people to understand the challenges and possible solutions.

A comparative study of fuzzy logic-based models for groundwater quality evaluation based on irrigation indices - Vadiati, Meysam; Nalley, Deasy; Adamowski, Jan; Nakhaei, Mohammad; Asghari-Moghaddam, Asghar (Journal of Water and Land Development, 2019)
Abstract Groundwater quality modelling plays an important role in water resources management decision making processes. Accordingly, models must be developed to account for the uncertainty inherent in the modelling process, from the sample measurement stage through to the data interpretation stages. Artificial intelligence models, particularly fuzzy inference systems (FIS), have been shown to be effective in groundwater quality evaluation for complex aquifers. In the current study, fuzzy set theory is applied to groundwater-quality related decision-making in an agricultural production context; the Mamdani, Sugeno, and Larsen fuzzy logic-based models (MFL, SFL, and LFL, respectively) are used to develop a series of new, generalized, rule-based fuzzy models for water quality evaluation using widely accepted irrigation indices and hydrological data from the Sarab Plain, Iran. Rather than drawing upon physiochemical groundwater quality parameters, the present research employs widely accepted agricultural indices (e.g., irrigation criteria) when developing the MFL, SFL and LFL groundwater quality models. These newly-developed models, generated significantly more consistent results than the United States Soil Laboratory (USSL) diagram, addressed the inherent uncertainty in threshold data, and were effective in assessing groundwater quality for agricultural uses. The SFL model is recommended as it outperforms both MFL and LFL in terms of accuracy when assessing groundwater quality using irrigation indices.

Integrating Multiple Research Methods to Unravel the Complexity of Human‐Water Systems - Di Baldassarre, Giuliano; Cloke, Hannah; Lindersson, Sara; Mazzoleni, Maurizio; Mondino, Elena; Mård, Johanna; Odongo, Vincent; Raffetti, Elena; Ridolfi, Elena; Rusca, Maria; Savelli, Elisa; Tootoonchi, Faranak (AGU Advances, 2021)
Abstract Predicting floods and droughts is essential to inform the development of policy in water management, climate change adaptation and disaster risk reduction. Yet, hydrological predictions are highly uncertain, while the frequency, severity and spatial distribution of extreme events are further complicated by the increasing impact of human activities on the water cycle. In this commentary, we argue that four main aspects characterizing the complexity of human‐water systems should be explicitly addressed: feedbacks, scales, tradeoffs and inequalities. We propose the integration of multiple research methods as a way to cope with complexity and develop policy‐relevant science. , Plain Language Summary Several governments today claim to be following the science in addressing crises caused by the occurrence of extreme events, such as floods and droughts, or the emergence of global threats, such as climate change and COVID‐19. In this commentary, we show that there are no universal answers to apparently simple questions such as: Do levees reduce flood risk? Do reservoirs alleviate droughts? We argue that the best science we have consists of a plurality of legitimate interpretations and a range of foresights, which can be enriched by integrating multiple disciplines and research methods. , Key Points Accounting for both power relations and cognitive heuristics is key to unravel the interplay of floods, droughts and human societies Flood and drought predictions are complicated by the increasing impact of human activities on the water cycle We propose the integration of multiple research methods as a way to cope with uncertainty and develop policy‐relevant science

A Canadian River Ice Database from National Hydrometric Program Archives - De Rham, Laurent; Dibike, Yonas; Beltaos, Spyros; Peters, Daniel; Bonsal, Barrie; Prowse, Terry (Hydrology and Soil Science – Hydrology, 2020)
Abstract. River ice is a common occurrence in cold climate hydrological systems. The annual cycle of river ice formation, growth, decay and clearance can include low flows and ice jams, as well as mid-winter and spring break-up events. Reports and associated data on river ice occurrence are often limited to site and season-specific studies. Within Canada, the National Hydrometric Program (NHP) operates a network of gauging stations with water level as the primary measured variable to derive discharge. In the late 1990s, the Water Science and Technology Directorate of Environment and Climate Change Canada initiated a long-term effort to compile, archive and extract river ice related information from NHP hydrometric records. This data article describes the original research data set produced by this near 20-year effort: the Canadian River Ice Database (CRID). The CRID holds almost 73,000 variables from a network of 196 NHP stations throughout Canada that were in operation within the period 1894 to 2015. Over 100,000 paper and digital files were reviewed representing 10,378 station-years of active operation. The task of compiling this database involved manual extraction and input of more than 460,000 data entries on water level, discharge, date, time and data quality rating. Guidelines on the data extraction, rating procedure and challenges are provided. At each location, a time series of up to 15 variables specific to the occurrence of freeze-up and winter-low events, mid-winter break-up, ice thickness, spring break-up and maximum open-water level were compiled. This database follows up on several earlier efforts to compile information on river ice, which are summarized herein, and expands the scope and detail for use in Canadian river ice research and applications. Following the Government of Canada Open Data initiative, this original river ice data set is available at: https://doi.org/10.18164/c21e1852-ba8e-44af-bc13-48eeedfcf2f4 (de Rham et al., 2020).

Citizens’ viewpoints on stormwater Beneficial Management Practices (BMPs) in Brazil - Sousa, Bruno José de Oliveira; Fialho, Hailton César Pimentel; Taffarello, Denise; Souza, Felipe Augusto Arguello; Hassanzadeh, Elmira; Mendiondo, Eduardo Mario; de Oliveira, Paulo Tarso Sanches (Journal of Cleaner Production, 2021)
Floods are among the most dangerous and destructive hazards in the world. Stormwater Beneficial Management Practices (BMPs) are a set of strategies that can assist in reducing urban floods and their damages by capturing surface runoff and promoting infiltration. Engagement of citizens in the selection of stormwater BMPs may facilitate the decision-making processes and increase the chance of adopting and maintaining them. Due to existence of catastrophic floods in Brazil, implementing BMPs is essential in the urban areas. The objective of this study is to understand the viewpoints of citizens about a set of stormwater BMPs in Brazil. Moreover, we aim to comprehend whether diverging viewpoints about the BMPs can be associated with existence of different layers in the society. For this purpose, online surveys were used to access wide and diverse groups of citizens from different ages, levels of education and income, as well as geographical location. The questions and descriptions of BMPs were prepared in an accessible language, and then disseminated through various platforms. The responses of more than 1000 participants were analyzed using descriptive and statistical methods. Our results show that the participants found the retention and detention basins, as well as permeable pavement as the most efficient BMPs. Moreover, considering the small-scale practices, although lot related BMPs are considered less efficient, citizens are willing to use green roof, bioretention, and rain barrels in their properties. In addition, most of the respondents support public investments on stormwater BMPs. Our analyses show that participants' age and level of education statistically influenced their choice of BMPs and willingness to pay for their maintenance and construction. These results can help Brazilian policy makers to prepare flood management plans by including stormwater BMPs that would be more accepted by the population. In addition, proposing practices that are aligned with citizens’ perceptions creates a sense of responsibility, and is in accordance with the Brazilian New Framework of Sanitation that includes public participation in policy making.
Keywords: Infolettre; Infolettre_Juillet_2022; Site_internet_RIISQ

Use of Mixed Methods in the Science of Hydrological Extremes: What Are Their Contributions? - Kabo, Raymond; Bourgault, Marc-André; Barrette, Nathalie; Tanguay, Louis (Hydrology, 2023)
Research in hydrological sciences is constantly evolving to provide adequate answers to address various water-related issues. Methodological approaches inspired by mathematical and physical sciences have shaped hydrological sciences from its inceptions to the present day. Nowadays, as a better understanding of the social consequences of extreme meteorological events and of the population’s ability to adapt to these becomes increasingly necessary, hydrological sciences have begun to integrate knowledge from social sciences. Such knowledge allows for the study of complex social-ecological realities surrounding hydrological phenomena, such as citizens’ perception of water resources, as well as individual and collective behaviors related to water management. Using a mixed methods approach to combine quantitative and qualitative approaches has thus become necessary to understand the complexity of hydrological phenomena and propose adequate solutions for their management. In this paper, we detail how mixed methods can be used to research flood hydrology and low-flow conditions, as well as in the management of these hydrological extremes, through the analysis of case studies. We frame our analysis within the three paradigms (positivism, post-positivism, and constructivism) and four research designs (triangulation, complementary, explanatory, and exploratory) that guide research in hydrology. We show that mixed methods can notably contribute to the densification of data on extreme flood events to help reduce forecasting uncertainties, to the production of knowledge on low-flow hydrological states that are insufficiently documented, and to improving participatory decision making in water management and in handling extreme hydrological events.
Keywords: Infolettre; Infolettre_Ete_2023

Interpolation of Precipitation Extremes on a Large Domain Toward IDF Curve Construction at Unmonitored Locations - Jalbert, Jonathan; Genest, Christian; Perreault, Luc (Journal of Agricultural, Biological and Environmental Statistics, 2022)
Abstract An intensity–duration–frequency (IDF) curve describes the relationship between rainfall intensity and duration for a given return period and location. Such curves are obtained through frequency analysis of rainfall data and commonly used in infrastructure design, flood protection, water management, and urban drainage systems. However, they are typically available only in sparse locations. Data for other sites must be interpolated as the need arises. This paper describes how extreme precipitation of several durations can be interpolated to compute IDF curves on a large, sparse domain. In the absence of local data, a reconstruction of the historical meteorology is used as a covariate for interpolating extreme precipitation characteristics. This covariate is included in a hierarchical Bayesian spatial model for extreme precipitations. This model is especially well suited for a covariate gridded structure, thereby enabling fast and precise computations. As an illustration, the methodology is used to construct IDF curves over Eastern Canada. An extensive cross-validation study shows that at locations where data are available, the proposed method generally improves on the current practice of Environment and Climate Change Canada which relies on a moment-based fit of the Gumbel extreme-value distribution.
Keywords: Infolettre; Infolettre_Avril_2022; Site_internet_RIISQ

Entre héritage réglementaire et imaginaire du risque: gestion des zones inondables et pratiques d'adaptation au Québec et à Lachute - Gaudette, Marilyne; Germain, Daniel (Zenodo, 2025)
Floods, intensified by climate change, pose major challenges for flood zone management in Quebec. This report addresses these issues through two complementary aspects: a historical analysis of the evolution of flood zone management in Quebec and the projected impact of the cartographic and regulatory overhaul, as well as an exploration of the imaginary surrounding the flood-prone territory of the city of Lachute, which has faced recurrent floods for decades and yet continues to be inhabited. The historical analysis reveals that the major floods of 1974, 1976, 2017, and 2019 marked significant turning points in Quebec’s risk management, particularly by highlighting gaps in the regulatory framework and flood zone mapping. The adoption of the Act Respecting Land Use Planning and Development (LAU) in 1979 and the Policy for the Protection of Shorelines, Littorals, and Floodplains (PPRLPI) in 1987 represented a shift toward a preventive approach. However, inconsistencies, insufficient updates to maps, and uneven enforcement of standards have hindered their effectiveness. The catastrophic floods of 2017 and 2019 triggered a regulatory overhaul, a modernization of mapping, and measures to strengthen community resilience. In 2022, a transitional regime came into effect to tighten the regulation of activities in flood zones, pending the adoption of a risk-based management framework. However, to this day, the regulatory perimeters proposed in the modernization project fail to account for the adaptive capacities deployed by communities to live with water, thus providing a biased interpretation of flood risk. The second part explores the social and cultural representations associated with Lachute’s flood-prone territory. It highlights the complex relationships that have developed between residents and the Rivière du Nord through successive flooding episodes and the adaptation strategies implemented to cope, particularly by those who have repeatedly experienced flooding. These residents have come to live with overflow events and to (co)exist with water, challenging the persistent notion that flood-prone areas are inherently dangerous. While local strategies are sometimes innovative, they remain constrained by a regulatory framework that disregards the human experience of the territory and the specific ways in which people inhabit exposed areas to learn to manage flood risks. In summary, this report underscores the urgency of a territorialized, risk-based approach to modernizing flood zone management. It also highlights the need to look beyond cartographic boundaries and better integrate human and cultural dimensions into planning policies, as illustrated in the case of Lachute, to more accurately reflect the true level of risk. These reflections aim to promote more coherent, sustainable, and acceptable management, planning, and development of exposed territories in response to the growing challenges posed by climate change.
Keywords: Infolettre; Infolettre_Mai_2025

Strategies for integrating water management and spatial planning: Organising for spatial quality in the Dutch “Room for the River” program - Busscher, T.; Van Den Brink, M.; Verweij, S. (Journal of Flood Risk Management, 2019)
In response to extreme flood events and an increasing awareness that traditional flood control measures alone are inadequate to deal with growing flood risks, spatial flood risk management strategies have been introduced. These strategies do not only aim to reduce the probability and consequences of floods, they also aim to improve local and regional spatial qualities. To date, however, research has been largely ignorant as to how spatial quality, as part of spatial flood risk management strategies, can be successfully achieved in practice. Therefore, this research aims to illuminate how spatial quality is achieved in planning practice. This is done by evaluating the configurations of policy instruments that have been applied in the Dutch Room for the River policy program to successfully achieve spatial quality. This policy program is well known for its dual objective of accommodating higher flood levels as well as improving the spatial quality of the riverine areas. Based on a qualitative comparative analysis, we identified three successful configurations of policy instruments. These constitute three distinct management strategies: the “program‐as‐guardian”, the “project‐as‐driver,” and “going all‐in” strategies. These strategies provide important leads in furthering the development and implementation of spatial flood risk management, both in the Netherlands and abroad.
Keywords: Ouvrage_Collectif_Numéro1

Pluralité des instruments et des logiques politiques pour l’adaptation aux changements globaux en zone côtière - Dhénain, Sandrine; Barreteau, Olivier (Natures Sciences Sociétés, 2018)
L’adaptation au changement climatique est un nouvel enjeu pour la gestion des territoires. Au niveau local, elle apparaît souvent comme une injonction, alors même que, pour l’instant, elle est un concept flou. Elle est présentée comme l’application de bonnes pratiques, mais les questions « qui s’adapte à quoi ? » et « pourquoi ? » demeurent implicites. En explicitant ces éléments, nous proposons de montrer que l’adaptation est une question plurielle et politique. À partir de l’analyse des documents de planification et des plans d’action faisant référence aux changements globaux sur un territoire littoral, nous montrons l’existence de quatre logiques d’adaptation distinctes, plus ou moins transformatrices du système socioécologique, que l’on peut appréhender à partir de la typologie suivante : « contrôler et maintenir », « faire faire », « réguler » et « reconfigurer », qui portent en germe différentes reconfigurations socioéconomiques et politiques. , Since the 2000s, “adaptation” is a new dictate for the management of local territories in France, but its implementation is fairly limited. Adaptation is mainly a semantically unclear and loosely defined concept. Decision-makers could “operationalize” adaptation by simply applying a specific methodology. However, adaptation is not a mere mechanism; it is also a process that implies economic, social and ecological trade-offs for the socio-ecological system. These political dimensions are often unformulated. In order to provide a vehicle to clarify this concept and its political dimensions, we propose a typology of adaptation measures. What does adaptation mean? Adjustment of what (territories, populations, communities, local economies, etc.), to what (climate change, global change) and with what effects? We reviewed local actions and strategic plans related to climate but also to urban planning, flooding and water management on the eastern coastal area of Languedoc Roussillon in Mediterranean France. We conducted and analyzed semi-structured interviews with institutional actors. We analyzed and classified public policy instruments, associated the underlying “logic” (raise limiting factors, create a new awareness, etc.), and their potential effects. Throughout our effort to develop a typology, we have highlighted the political dimensions of adaptation actions and shed a light on trade-offs linked to adaptation choices.
Keywords: Ouvrage_Collectif_Numéro1

Stream habitat provided by large wood at risk under drainage law - Shirey, Patrick D.; Kenny, Jillian B.; Brueseke, Michael A.; Lamberti, Gary A. (Earth Surface Processes and Landforms, 2020)
Watershed management efforts in agriculturally dominated landscapes of North America face nearly two centuries of laws and policies that encouraged habitat destruction. Although streams and wetlands in these landscapes are actively being restored using designs that incorporate science and engineering, watershed drainage laws can constrain action or impact passively restored or naturalized habitat. In general, drainage laws require removal of any riparian vegetation or wood deemed to obstruct flow in streams regulated as drains. We use a case study from Indiana (USA) to introduce the shortcomings of drainage laws for allowing large wood, which is an important habitat feature, to remain in stream ecosystems. Removals of large wood from monitored stream reaches in a regulated drain were associated with subsequent declines in fish biomass. Such legal activities represent an important environmental management problem that exists under drainage laws which apply to streams over a widespread geographic region of North America. Recent litigation in Wisconsin (USA) suggests that if state legislatures fail to update these antiquated laws, the courts may act in favour of science-based management of drains. The statutes and regulations that govern agricultural drainage warrant careful consideration if streams within drainage districts are to be managed to improve ecological function. © 2020 John Wiley & Sons, Ltd.
Keywords: Ouvrage_Collectif_Numéro1

Comparison of Hydrologic Responses at Different Watershed Scales - Mohamoud, Yusuf (2004)
Land surface hydrology controls runoff production and the associated transport of sediments, and a wide variety of anthropogenic organic chemicals, and nutrients from upland landscape areas and hillslopes to streams and other water bodies. Based on interactions between landscape characteristics and precipitation inputs, watersheds respond differently to different climatic inputs (e.g. precipitation and solar radiation). This study compares the hydrologic responses of the MidAtlantic watersheds, and identifies the landscape and climatic descriptors that control those responses. Our approach was to select representative watersheds from the Mid-Atlantic region, group the watersheds by physiographic province and ecoregion, and then collect landscape, climate, and hydrologic response descriptor data for each selected watershed. For example, we extracted extensive landscape descriptor data from soil, land use and land cover, and digital elevation model geographic information system (GIS) databases. After sufficient data was collected, we conducted a variety of studies to determine how different landscape and climatic descriptors influence the hydrologic response of Mid-Atlantic watersheds. This report is comprised of four main parts. Part I describes the selection of the representative study watersheds and the determination of representative physical landscape descriptors for each watershed using geographic information system analysis tools. Part II characterizes the climate and associated hydrologic responses of the study watersheds. To select climate descriptors that are good predictors of hydrologic response, we examined a large number of candidate descriptors. Based on our examination, we selected dryness index and mean monthly rainfall as the best hydrologic response predictors. In Part II, we also present the results of our study hydrologic response comparisons of the study watersheds using a water balance approach. The water balance approach was based on comparisons of precipitation, streamflow, and evapotranspiration at annual, monthly, and daily time scales. These comparisons revealed that elevation and latitudinal position strongly influence hydrologic response. The results also showed that mountainous watersheds of the Appalachian Plateau, Ridge and Valley, and Blue Ridge Physiographic Provinces have more streamflow and less evapotranspiration than watersheds located in the Piedmont Province, and that snowmelt contributes a large portion of streamflow. Part III presents relationships we derived between landscape-climatic descriptors and the hydrologic response descriptors. Flow duration indices (Q1...Q95) were used to represent the hydrologic responses of the study watersheds. In Part III, we also present comparisons of the hydrologic responses of the study watersheds at high flow condition, represented by the Q1 index, medium flow condition represented by the Q50 index, and low flow condition represented by the Q95 index. These comparisons revealed that: the Appalachian Plateau, ridge-dominated Ridge and Valley, and Blue Ridge watersheds have the highest Q1 and Q50 indices; the valley-dominated Ridge and Valley watersheds have the lowest Q50 index, and the Piedmont watersheds have the lowest Q1 index and a relatively high Q95 index. Finally, Part IV discusses some of the implications of the study results for watershed management. We also present applications of the research for hydrologic modeling and watershed assessment.
Keywords: Ouvrage_Collectif_Numéro1

The Importance of Climate Risks for Institutional Investors - Krueger, Philipp; Sautner, Zacharias; Starks, Laura T. (Review of Financial Studies, 2020)
According to our survey about climate risk perceptions, institutional investors believe climate risks have financial implications for their portfolio firms and that these risks, particularly regulatory risks, already have begun to materialize. Many of the investors, especially the long-term, larger, and ESG-oriented ones, consider risk management and engagement, rather than divestment, to be the better approach for addressing climate risks. Although surveyed investors believe that some equity valuations do not fully reflect climate risks, their perceived overvaluations are not large.
Keywords: Ouvrage_Collectif_Numéro1

Privatizing climate adaptation: How insurance weakens solidaristic and collective disaster recovery - Lucas, Chloe H.; Booth, Kate I. (WIREs Climate Change, 2020)
Abstract As losses from extreme weather events grow, many governments are looking to privatize the financing and incentivization of climate adaptation through insurance markets. In a pure market approach to insurance for extreme weather events, individuals become responsible for ensuring they are adequately covered for risks to their own properties, and governments no longer contribute funds to post‐disaster recovery. Theoretically, insurance premiums signal the level of risk faced by each household, and incentivize homeowners to invest in adaptive action, such as retrofitting, or drainage work, to reduce premiums. Where risk is considered too high by insurance markets, housing is devalued, in theory leading to retreat from risky areas. In this review article, we evaluate the suitability of private insurance as a mechanism for climate adaptation at a household and community level. We find a mismatch between social understandings of responsibility for climate risks, and the technocratic, market‐based home insurance products offered by private insurance markets. We suggest that by constructing increasingly individualized, technical, and calculative evaluations of risk, market‐based models of insurance for extreme weather events erode the solidaristic and collective discourses and practices that support adaptive behavior. This article is categorized under: Vulnerability and Adaptation to Climate Change > Institutions for Adaptation
Keywords: Ouvrage_Collectif_Numéro1

When disaster strikes: Under-insurance in Australian households - Booth, Kate; Tranter, Bruce (Urban Studies, 2018)
In undertaking what we believe is the first national-scale study of its kind, we provide methodologically transparent, statistically robust insights into associations and potential unfolding effects of house and contents under-insurance. We identify new dimensions in the complex relationship between householders and insurance, including the salience of interpersonal – and likely institutional – trust. Under-insurance is (re)produced along socio-economic and geographical lines, with those of lower socio-economic status or living in cities more likely to be under-insured. Should a disaster strike, such communities are likely to suffer further disadvantage, especially if governments continue to shift the responsibility for risk onto households. Our findings support the observation that insurance can contribute to increasing socio-economic urban polarisation in light of natural disasters. We conclude by considering how under-insurance may contribute to growing urban social stratification, as well as how it may produce situated ethical and political responses that exceed neoliberal aspirations.
Keywords: Ouvrage_Collectif_Numéro1

Design and Implementation of Machine Learning Models and Algorithms for Flood, Drought and Frazil Prediction - Yagnik, Bhargav Charudatt (Concordia University, 2023)
Natural calamities like floods and droughts pose a significant threat to humanity, impacting millions of people each year and incurring substantial economic losses to society. In response to this challenge, this thesis focuses on developing advanced machine learning techniques to improve water height prediction accuracy that can aid municipalities in effective flood mitigation. The primary objective of this study is to evaluate an innovative architecture that leverages Long Short Term Networks - neural networks to predict water height accurately in three different environmental scenarios, i.e., frazil, droughts and floods due to snow spring melt. A distinguishing feature of our approach is the incorporation of meteorological forecast as an input parameter into the prediction model. By modeling the intricate relationships between water level data, historical meteorological data and meteorological forecasts, we seek to evaluate the impact of meteorological forecasts and if any inaccuracies could impact water-level prediction. We compare the outcomes obtained by incorporating next-hour, next-day and next-week meteorological data into our novel LSTM model. Our results indicate a comprehensive comparison of the usage of various parameters as input and our findings suggest that accurate weather forecasts are crucial in achieving reliable water height predictions. Additionally, this study focuses on the utilization of IoT sensor data in combination with ML models to enhance the effectiveness of flood prediction and management. We present an online machine learning approach that performs online training of the model using real-time data from IoT sensors. The integration of live sensor data provides a dynamic and adaptive system that demonstrates superior predictive capabilities compared to traditional static models. By adopting these advanced techniques, we can mitigate the adverse impacts of natural catastrophes and work towards building more resilient and disaster-resistant communities.

Estimation du débit en rivière à l’aide de l’imagerie RADARSAT en utilisant l’apprentissage profond. - Ziadi, Samar (Maîtrise en sciences de l'eau, 2023)
L’estimation du débit en rivières est un paramètre clé pour la gestion des ressources hydriques, la prévention des risques liés aux inondations et la planification des équipements hydroélectriques. Lorsque le débit d’eau est très élevé lors d'évènements extrêmes, les méthodes de jaugeage traditionnelles ne peuvent pas être utilisées. De plus, les stations du réseau hydrométrique sont généralement éparses et leur répartition spatiale n’est pas optimale. Par conséquent, de nombreuses sections de rivières ne peuvent être suivies par des mesures et observations du débit. Pour ces raisons, pendant la dernière décennie, les capteurs satellitaires ont été considérés comme une source d’observation complémentaire aux observations traditionnelles du niveau d’eau et du débit en rivières. L’utilisation d’une telle approche a fourni un moyen de maintenir et d’étendre le réseau d'observation hydrométrique. L’approche avec télédétection permet d’estimer le débit à partir des courbes de tarage qui met en relation le débit instantané (Q) et la géométrie d’une section transversale du chenal (la largeur ou la profondeur effective de la surface d’eau). En revanche, cette méthode est associée à des limitations, notamment, sa dépendance aux courbes de tarage. En effet, en raison de leurs natures empiriques, les courbes de tarage sont limitées à des sections spécifiques et ne peuvent être appliquées dans d’autres rivières. Récemment, des techniques d’apprentissage profond ont été appliquées avec succès dans de nombreux domaines, y compris en hydrologie. Dans le présent travail, l’approche d’apprentissage profond a été choisie, en particulier les réseaux de neurones convolutifs (CNN), pour estimer le débit en rivière. L’objectif principal de ce travail est de développer une approche d’estimation du débit en rivières à partir de l’imagerie RADARSAT 1&2 à l’aide de l’apprentissage profond. La zone d’étude se trouve dans l’ecozone du bouclier boréal à l’Est du Canada. Au total, 39 sites hydrographiques ont fait l’objet de cette étude. Dans le présent travail, une nouvelle architecture de CNN a été a été proposée, elle s'adapte aux données utilisées et permet d’estimer le débit en rivière instantané. Ce modèle donne un résultat du coefficient de détermination (R²) et de Nash-Sutcliffe égale à 0.91, le résultat d’erreur quadratique moyenne égale à 33 m³ /s. Cela démontre que le modèle CNN donne une solution appropriée aux problèmes d’estimation du débit avec des capteurs satellites sans intervention humaine. Estimating river flow is a key parameter for effective water resources management, flood risk prevention and hydroelectric facilities planning. In cases of very high flow of water or extreme events, traditional gauging methods cannot be reliable. In addition, hydrometric network stations are often sparse and their spatial distribution is not optimal. Therefore, many river sections cannot be monitored using traditional flow measurements and observations. For these reasons, satellite sensors are considered as a complementary observation source to traditional water level and flow observations in the last decades. The use of this kind of approach has provided a way to maintain and expand the hydrometric observation network. Remote sensing data can be used to estimate flow from rating curves that relate the instantaneous flow (Q) to the geometry of a channel cross-section (the effective width or depth of the water surface). On the other hand, remote sensing is also associated with limitations, notably its dependence on the rating curves. Indeed, due to their empirical nature, rating curves are limited to specific sections and cannot be applied in other rivers. Recently, deep learning techniques have been successfully applied in many fields, including hydrology. In the present work, the deep learning approach has been chosen, in particular convolutional neural networks (CNN), to estimate river flow. The main objective of this work is to develop an approach to estimate river flow from RADARSAT 1&2 imagery using deep learning. In this study, 39 hydrographic sites of the Boreal Shield ecozone in Eastern Canada were considered. A new CNN architecture was developed to provide a straightforward estimation of the instantaneous river flow rate. The achieved results demonstrated a coefficient of determination (R²) and Nash-Sutcliffe values of 0.91, and a root mean square error of 33m³ /s. This indicates the effectiveness of CNN in automatic flow estimation with satellite sensors.

Improving hydrological forecasting at multiple lead-times for hydropower reservoir management - Sabzipour, Behmard (École de technologie supérieure, 2023)
Streamflow forecasting is important for managing water resources in sectors like agriculture, hydropower, drought management, and urban flood prevention planning. Our study examines short and long lead-times to create a framework for streamflow forecasting that can benefit water resource management and related sectors. To improve streamflow forecasts for up to ten days of lead-time, the study first focuses on improving initial conditions using an ensemble Kalman filter as a data assimilation method. The goal is to regulate the hyperparameters of the ensemble Kalman filter for each season to produce more accurate forecasts. A sensitivity analysis is conducted to identify the best hyperparameter sets for each season, including uncertainty in temperature, precipitation, observed streamflow, and the water content of three state variables - vadose zone, saturated zone, and snowpack - from the CEQUEAU model. Results indicate that improving initial conditions with the ensemble Kalman filter produces more skillful forecasts until a 6-day leadtime. Temperature uncertainty is particularly sensitive and varies across seasons. The vadose zone state variable was identified as the most important and sensitive state variable, and updating all state variables systematically may not be necessary for improving forecast skill. Recent machine learning advances are improving short-term streamflow forecasting. One such method is the Long Short-Term Memory (LSTM) model. In general, neural networks learn from regression as relationships exist between input-output. However, LSTM models have a feature named ‘forget gate’, which enables them to learn the relationship between inputs (e.g., temperature and precipitation) and output (streamflow), and also to capture temporal dependencies in the data. The study aimed to compare the performance of the Long ShortTerm Memory (LSTM) model with data assimilation-based and process-based hydrological models in short-term streamflow forecasting. All three models were tested using the same ensemble weather forecasts. The LSTM model demonstrated good performance in forecasting streamflow, with a Kling-Gupta efficiency (KGE) greater than 0.88 for 9 lead-times. The LSTM model did not incorporate data assimilation, but it benefited from observed streamflow until the last day before the forecast. This is because the LSTM model learned and incorporated knowledge from the previous days while issuing forecasts, similar to how data assimilation updates initial conditions. The study results also showed that the LSTM model had better performance up to day 6 of lead-time compared to the data assimilation-based models. However, training the LSTM model separately for each lead-time is a time-consuming process and is a disadvantage compared to the data assimilation-based methods. Nonetheless, the study demonstrated the potential of machine learning techniques in improving streamflow forecasting. The forecasting of streamflow for long lead-times such as a month usually involves the use of historical meteorological data to create probable future scenarios, as meteorological forecasts become unreliable beyond this lead-time. In this study, we proposed a novel method for streamflow forecasting based on ensemble streamflow forecasting (ESP) filtering, using a Genetic Algorithm (GA) to filter forecast scenarios. This method quantifies the potential of historical data for each basin. This potential could be utilized to enhance the accuracy of streamflow forecasts. We sorted the selected and unselected scenarios to find out the common features between them, but the results did not help distinguish between the two groups. Nonetheless, the GA method can be used as a benchmark for future studies to improve longterm streamflow forecasting. This method can also be used to compare different forecast methods based on the potential shown by the GA method for a specific size of ESP members. For instance, if a method uses large-scale climate signals to filter ESP members, the forecast skill result could be compared with the potential of historical data for that particular size of ESP members.

Using a stochastic weather generator to account for climate non-stationarity in extended streamflow forecasts - Sohrabi Molla Yousef, Samaneh (École de technologie supérieure, 2020)
Reliable long-term streamflow forecast is essential in water resources management and plays a key role in reservoir management and hydropower generation. Properly framing the uncertainty is the key issue in providing a reliable long-term streamflow forecast, and probabilistic forecasts have been used to this effect. In a probabilistic approach, each observed historical data is taken as a possible realization of the future. Non stationarity of hydrometeorological variables, either due to the climate internal variability or anthropogenic change, is another important problem for long-term streamflow forecasts as it is becoming increasingly clearer that past historical data may not adequately represent the current climate. Therefore, there is a need to develop flexible approaches taking into account non-stationarity for long-term streamflow forecasts. Resampling past historical time series is the main approach used for probabilistic long term streamflow forecasts. However, non-stationarity is a key issue of resampling approaches. One possible approach is to make use of a stochastic weather generator coupled to a hydrological model to generate long-term probabilistic streamflow forecasts. Weather generators can easily be modified to account for climatic trends and therefore have the potential to take non-stationarity into account. However, before weather generators can be modified to account for climate non-stationarity, it is first necessary to evaluate whether the modeling chain consisting of a stochastic weather generator and a hydrological model can generate probabilistic streamflow forecasts with a performance similar to that of more traditional resampling approaches. The first objective of this study is therefore, to compare the performance of a stochastic weather generator against that of resampling historical meteorological time series in order to produce ensemble streamflow forecasts. Results indicate that while there are differences between both methods, they nevertheless largely both perform similarly, thus showing that weather generators can be used as substitutes to resampling the historical past. Based on these results, two approaches for taking non-stationarity into account have been proposed. Both approaches are based on a climate-based perturbation of the stochastic weather generator parameters. The first approach explored a simple perturbation method in which the entire length of the historical record is used to quantify internal variability, while a subset of recent years is used to characterize mean climatic values for precipitation, minimum and maximum temperatures. Results show that the approach systematically improves long-term streamflow forecasts accuracy, and that results are dependent on the time window used to estimate current mean climatic estimates. The second approach conditioned the parameters of a stochastic weather generator on largescale climate indices. In this approach, the most important climate indices are identified by looking at yearly correlations between a set of 40 indices and precipitation and temperature. A linear model is then constructed to identify precipitation and temperature anomalies which are then used to induce perturbations in the stochastic weather generator. Five different time windows are defined to determine the optimal linear model. Results show that temperatures are significantly correlated with large-scale climate indices, whereas precipitation is only weakly related to the same indices. The length of the time window has a considerable impact on the prediction ability of the linear models. The precipitation models based on short-duration time windows performed better than those based on longer windows, while the reverse was found for the temperature models. Results show that the proposed method improves long-term streamflow forecasting, particularly around the spring flood.

Livelihood vulnerability to climatic stresses: A study of the northeastern floodplain communities of Bangladesh - Rahman, H.M. (2018)
Climatic stress vulnerability has cross-scaler influences on development interventions, particularly in developing countries. While most of climate adaptation plans and interventions are developed at national or international scales, relatively little attention has been paid to incorporate the contextual properties of climate vulnerability in adaptation-related decision making. Focusing on the wetland ecosystem dominated northeastern floodplain communities of Bangladesh, this exploratory research seeks to better understand how locally-specific socio-economic and biophysical properties serve to compound vulnerability to climatic stresses; how community members use their resources and assets in order to reduce their sensitivity to climatic stresses; and the extent to which government adaptation programmes reflect context-specific adaptation demands. Recognizing that Bangladesh is widely acknowledged to be one of the most climate-vulnerable countries in the world, this dissertation begins with a systematic literature review of the state of knowledge related to climate change impacts in Bangladesh. Results indicate a shortage of context specific scientific studies and identify that northeastern floodplain region is the most understudied area in the country. Issues related to multidisciplinary research approaches and geographic connectedness of research efforts point to potential limitations in the evidence base used to support public policy initiatives on climate change adaptation. A participatory climate stress exposure assessment reveals that local biophysical changes and resource use behaviors significantly contribute to compounding the impacts of climatic stresses. However, these observations are generally poorly represented in local-level climate model-based stress assessments. Results reveal that community stress perceptions are largely determined by the temporal occurrence of a climatic event, with a climatic event considered a stress if it occurs in their production period and causes losses to their productivity. Stress perceptions are also influenced by household resource ownership, local innovation and technological uses. Using the sustainable rural livelihood approach, a mixed method study is then used to better understand the actions taken by households to reduce their livelihood sensitivity to climatic stresses. Households were found to organize, transform and combine their capital assets for generating different livelihood portfolios. Using diverse combinations of assets, two strategies were observed: 1) extending external networks in order to create non-natural resource dependent livelihood opportunities; and 2) extending uses of available natural resources. Both of these strategies required external supports from government programmes or market mechanisms. Finally, a climate change policy analysis of Bangladesh, supported with key informant interviews, is presented to assess how different government policy interventions have supported local adaptation initiatives. The results reveal that despite recent advancements in climate change related policy making and institutional changes for supporting local adaptation actions in Bangladesh, plans and policies often fail to respond to local demands. More specifically, the existing climate change adaptation planning and policy processes tend to lack wider public participation and have inadequate coordination with natural resource management policies. This dissertation considers the diverse socio-economic and social-ecological contexts of climate vulnerability in rural Bangladesh. The results offer important research and policy insights to developing more a systematic understanding of climate vulnerability, and how local knowledge might be better integrated into national and international policy processes.

Déterminants de l'intention d'adoption d'un nouvel outil prévisionnel des crues dans le cadre du projet info-crue - Mutabazi, Jean-Paul (Université du Québec à Rimouski, 2022)
RÉSUMÉ : Pour atténuer les risques d'inondation au Québec mais aussi partout dans le monde, plusieurs organismes gouvernementaux et des organismes privés, qui ont dans leurs attributions la gestion des risques des catastrophes naturelles, continuent d'améliorer ou d'innover en matière d'outils qui peuvent les aider efficacement à la mitigation des risques d'inondation et aider la société à mieux s'adapter aux changements climatiques, ce qui implique des nouvelles technologies pour la conception de ces outils. Après les inondations de 2017, le ministère de l'Environnement et de la Lutte contre les changements climatiques (MELCC) du gouvernement du Québec, en collaboration avec d'autres ministères et organismes et soutenu par Ouranos, a initié le projet INFO-Crue qui vise d'une part, à revoir la cartographie des zones inondables et, d'autre part, à mieux outiller les communautés et les décideurs en leur fournissant une cartographie prévisionnelle des crues de rivières. De ce fait, l'objectif de notre travail de recherche est d'analyser de façon empirique les facteurs qui influencent l'adoption d'un outil prévisionnel des crues. La revue de la littérature couvre les inondations et les prévisions, les théories et les modèles d'acceptation de la technologie de l'information (TI). Pour atteindre l'objectif de recherche, le modèle développé s'est appuyé particulièrement sur le modèle qui combine les concepts de la théorie unifiée de l'acceptation et l'utilisation des technologies (UTAUT) de Venkatesh et al. (2003) avec le concept « risque d'utilisation ». Afin de répondre à notre objectif de recherche, nous avons utilisé une méthodologie de recherche quantitative hypothético-déductive. Une collecte de données à l'aide d'une enquête par questionnaire électronique a été réalisée auprès de 106 citoyens qui habitent dans des zones inondables. L'analyse des résultats concorde avec la littérature. La nouvelle variable « risque d'utilisation » rajoutée au modèle UTAUT a engendré trois variables qui sont : « risque psychologique d'utilisation »; « risque de performance de l'outil » et « perte de confiance ». Pour expliquer l'adoption d'un nouvel outil prévisionnel des crues, notre analyse a révélé que cinq variables à savoir : « l'utilité perçue », « la facilité d'utilisation », « l'influence sociale », « la perte de confiance » et « le risque psychologique » sont des facteurs significatifs pour l'adoption du nouvel outil prévisionnel. -- Mot(s) clé(s) en français : Inondation, Prévision, UTAUT, Adoption de la technologie, Risque perçu d'utilisation, facteurs d'adoption, Projet INFO-Crue. -- ABSTRACT : With the aim of mitigating flood risks in Canada as well as around the world, several government and private organizations that have the responsibility of natural hazard risk management, are working hard to improve or innovate the flood mitigation approaches that can help effectively reducing flood risks and helping people adapt to climate change. After the 2017 floods, the Ministry of the Environment and the Fight against Climate Change (MELCC) of the Government of Quebec, in collaboration with other ministries and organizations and supported by Ouranos, initiated the INFO-Crue project which aims at reviewing the mapping of flood zones and providing communities and decision-makers with a forecast mapping of river floods. In this context, the objective of our research is to analyze the factors that may influence the adoption of a flood forecasting tool. The literature review covers flood and forecasting, as well as technology adoption models. To achieve the goal of our research, a conceptual model that combines the Unified Theory of Acceptance and Use of Technology (UTAUT) of Venkatesh et al. (2003) with perceived use risk was developed. A quantitative research methodology was used, and we administrate an electronic questionnaire survey to 106 citizens who live in flood-plain area. Results analysis show that the new variable "perceived use risk" introduced in the model generates three variables which are: "psychological risk"; "performance risk" and "loss of trust". To explain the adoption of a new forecasting tool, our analysis revealed that the following five variables which are "perceived usefulness", "ease of use", "social influence", "loss of trust" and "psychological risk" are significant factors for the adoption of the new forecasting tool. -- Mot(s) clé(s) en anglais : Flood, Forecasting, UTAUT, Technology Adoption, perceived Risk of use, adoption factors, INFO-Crue project.

A comparative assessment of hydrologic models of varying complexity applied to a semi-arid region (Sardinia, Italy). for climate change studies - Perra, Enrica (Università degli Studi di Cagliari - Université du Québec, Institut national de la recherche scientifique, 2018)
L'évaluation de l'impact hydrologique du changement climatique présente une importance particulière pour les bassins de la Méditerranée, qui sont très sensibles aux événements hydrologiques extrêmes. La modélisation des systèmes aussi complexes pour la gestion des ressources hydriques est un défi difficile. L'objectif global de ce travail est de contribuer au développement d'une approche de modélisation qui permette l'évaluation de l'impact hydrologique du changement climatique sur deux bassins de la Méditerranée, localisés en Sardaigne. Cette contribution se concentre sur deux sujets principaux: comprendre comment la représentation physique des modèles hydrologiques grave sur l'évaluation de l'impact hydrologique dû au changement climatique sur un bassin avec un climat semi-aride, le Rio Mannu di San Sperate, et montrer comme le modélisation avancé puisse aider à définir de mesures de modération et adaptation dans un système complexe enclin aux événements hydrique extrêmes, le Flumendosa, en conditions de changement climatique. Pour atteindre cet objectif le travail s'articule en trois phases. Les effets du changement climatique sur le bassin du Rio Mannu sont évalués à travers la comparaison des résultats de cinq modèles hydrologiques, CATchment HYdrology (CATHY), Soil and Water Assessment Tool (SWAT), TIN-based Real time Integrated Basin Simulator (tRIBS), TOPographic Kinematic APproximation and Integration-eXtended (TOPKAPI-X), and Water flow and balance Simulation Model (WASIM), en utilisant comme forçage atmosphérique les données de quatre combinaisons de modèles climatiques globaux (GCM) et régionaux (RCM). Pour évaluer les incertitudes une métrique récemment proposée est utilisée: les résultats des modèles sont comparés pendant une période de référence et future, en utilisant l'index de corrélation de Pearson et le bias de Duveiller. Même si certaines différences existent, en tout les modèles hydrologiques montrent une bonne concordance, et ils répondent de manière semblable à la réduction de la précipitation et à l'accroissement de la température prévu par les modèles climatiques. Il s'attend donc que le bassin dans l'avenir sera sujet à une réduction de la disponibilité de ressource hydrique, avec des conséquences négatives en particulier pour le secteur agricole. Une comparaison détaillée des réponses obtenue sur le même bassin avec trois modèles hydrologique à base physique avec différent degré pour ce qui concerne la représentation des procès physiques et des caractéristiques du terrain, CATHY, TOPKAPI-X, tRIBS, est effectué dans le but de tester la transférabilité des paramètres entre les trois modèles hydrologiques, avec une attention particulière sur les difficultés relevées dans les périodes de calibrage et validation. Tandis que les trois modèles ont répondu de manière semblable pendant la période de calibrage, significatives différences ont été relevées pendant la période de validation, caractérisé par un climat très sec, avec le modèle CATHY, qu'il a produit un très bas décharge. En conséquence, pour obtenir résultats satisfaisants avec le modèle CATHY, l’hypothèse de croûtage de sol a été assumée, sur la base dont la couche premier de sol a été modelée avec une conductibilité hydraulique saturée réduite. Finalement le modèle TOPKAPI-X est implémenté sur un des principaux bassins de la Sardaigne, d'importance stratégique pour le système hydrique de la région, le Flumendosa, afin d’évaluer les effets du changement climatique à plus grande échelle. Le modèle répond avec une diminution des valeurs de décharge, contenu hydrique et évapotranspiration réelle à la réduction de la précipitation et accroissement des températures prévus par les modèles climatiques en donnant aussi support à une scène future de carence de la ressource hydrique dans ce bassin de la zone Méditerranéenne. Assessing the hydrologic impacts of climate change is of great importance in the Mediterranean basins, which are heavily sensitive to climate variability, with significant impacts on water resources and hydrologic extremes. Modeling such complex systems to manage water resources and predict hydrologic extremes is a difficult task. The overall aim of the work described in this thesis is to bring a contribution in developing a modeling approach that allows evaluation of local hydrologic impacts of climate changes in two Mediterranean catchments located in Sardinia. This contribution revolves around two main themes: understanding how physical representation of hydrologic models can affect hydrologic impact assessment under climate change on a semi-arid basin of the Mediterranean region, the Rio Mannu catchment, and demonstrating how advanced hydrologic modeling can help in defining adaptation measures in a complex water system, the Flumendosa basin, under climate change. The work to achieve the general objective is elaborated into three stages. The effects of climate change are evaluated on the Rio Mannu catchment through comparison of the results from five hydrologic models, CATchment HYdrology (CATHY), Soil and Water Assessment Tool (SWAT), TIN-based Real time Integrated Basin Simulator (tRIBS), TOPographic Kinematic APproximation and Integration-eXtended (TOPKAPI-X), and Water flow and balance Simulation Model (WASIM), and using as atmospheric input outputs of four climate global (GCM) and regional (RCM) model combinations. In order to evaluate uncertainties, a recently proposed metric is used: climate and hydrologic models results are compared in terms of agreement with each other in reference and future periods using Pearson correlation values and Duveiller bias. Notwithstanding some differences, overall the five hydrologic models show good agreement, and they respond similarly to the reduced precipitation and increased temperatures predicted by the climate models, lending strong support to a future scenario of increased water shortages for this region of the Mediterranean, with negative consequences especially for the agricultural sector. Detailed comparison of the responses obtained with three physically based hydrologic models, but to varying degrees as regards physical processes and terrain features representation – CATHY, tRIBS, and TOPKAPI-X – on the same catchment is carried out, with the aim to test the transferability of parameters between the three hydrologic models, focusing in particular on the calibration and validation difficulties. While the three hydrologic models responded similarly during the calibration year, significant differences were found for the drier validation period for the CATHY model, which produced very low streamflow. To obtain satisfactory results for the CATHY model, an hypothesis of soil crusting was assumed and the first soil layer was modeled with a lower saturated hydraulic conductivity. Finally, the TOPKAPI-X model is applied on a large Sardinian basin prone to extreme flood events, the Flumendosa basin, to assess the hydrologic impact of climate change at much larger scale. The model responds with decreasing value of discharge, soil water content, and actual evapotranspiration to the reduced precipitation and increased temperature predicted by the climate models, lending strong support to a future scenario of increased water shortages also in this basin of the Mediterranean region. La valutazione dell’impatto idrologico del cambiamento climatico riveste particolare importanza per i bacini del Mediterraneo, sensibili ad eventi idrologici estremi. Modellizzare dei sistemi così complessi per la gestione della risorse idriche è una sfida difficile. L’obiettivo globale di questo lavoro è contribuire allo sviluppo di un approccio modellistico che consenta la valutazione dell’impatto idrologico del cambiamento climatico su due bacini del Mediterraneo localizzati in Sardegna. Questo contributo si focalizza su due temi principali: capire come la rappresentazione fisica dei modelli idrologici incida sulla valutazione dell’impatto idrologico dovuto al cambiamento climatico su un bacino con un clima semi-arido, il Rio Mannu di San Sperate, e dimostrare come la modellizzazione avanzata possa aiutare nel definire misure di adattamento in un sistema idrico complesso incline ad eventi estremi, il Flumendosa, in condizioni di cambiamento climatico. Per raggiungere tale obiettivo il lavoro si articola in tre fasi. Gli effetti del cambiamento climatico sul bacino del Rio Mannu sono stati valutati attraverso il confronto dei risultati di cinque modelli idrologici, CATchment HYdrology (CATHY), Soil and Water Assessment Tool (SWAT), TIN-based Real time Integrated Basin Simulator (tRIBS), TOPographic Kinematic APproximation and Integration-eXtended (TOPKAPI-X), and Water flow and balance Simulation Model (WASIM), utilizzando come forzante atmosferica gli output di quattro combinazioni di modelli climatici globali (GCM) e regionali (RCM). Per valutare le incertezze è stata utilizzata una metrica recentemente proposta: i risultati dei modelli sono stati comparati durante un periodo di riferimento e futuro, utilizzando l’indice di correlazione di Pearson e il bias di Duveiller. Pur con qualche differenza, complessivamente i modelli idrologici mostrano una buona concordanza tra loro, e rispondono in maniera simile alla riduzione della precipitazione e all’incremento della temperatura previsti dai modelli climatici. Ci si aspetta pertanto che il bacino nel futuro sarà soggetto ad una riduzione della disponibilità di risorsa idrica, con conseguenze negative in particolare per il settore agricolo. È stato effettuato un confronto dettagliato delle risposte ottenute sullo stesso bacino con tre modelli idrologici fisicamente basati di diverso grado per quanto riguarda la rappresentazione dei processi fisici e delle caratteristiche del terreno, CATHY, TOPKAPI-X, tRIBS, con lo scopo di testare la trasferibilità dei parametri tra i tre modelli idrologici, concentrandosi sulle difficoltà riscontrate nei periodi di calibrazione e validazione. Mentre i tre modelli hanno risposto in maniera simile durante il periodo di calibrazione, sono state riscontrate significative differenze durante il periodo di validazione, caratterizzato da un clima molto secco, con il modello CATHY, che ha prodotto una portata molto bassa. Pertanto, per ottenere risultati soddisfacenti con il modello CATHY, è stata assunta l’ipotesi di soil crusting, sulla base della quale il primo strato di suolo è stato modellato con una ridotta conducibilità idraulica satura. Infine il modello TOPKAPI-X è stato implementato su uno dei principali bacini sardi di importanza strategica per il sistema idrico della regione, il Flumendosa, per valutare gli effetti del cambiamento climatico a scala maggiore. Il modello risponde con una diminuzione dei valori di portata, contenuto idrico ed evapotraspirazione reale alla riduzione della precipitazione ed incremento della temperature previsto dai modelli climatici, dando supporto ad uno scenario futuro di carenza della risorsa idrica anche in questo bacino dell’area Mediterranea.

Essays on Water Infrastructure Investments and Infectious Diseases Management - Kouassi, Régis (2024)
En étant nécessaire à la vie humaine, l’eau est également nécessaire au fonctionnement des économies. Pour qu’elle soit utile à la société, l’eau doit être disponible en quantité et en qualité adéquates, caractéristiques qui ne sont pas toujours disponibles dans la nature. Ainsi, trop ou pas assez d’eau entraînerait des inondations ou des sécheresses, tandis qu’une eau contaminée pourrait être le vecteur de maladies contagieuses mortelles, chacun de ces fléaux entraînant des dommages économiques. Cette thèse est organisée en trois chapitres traitant de thématiques liées aux investissements dans les infrastructures d'eau et à la gestion des maladies infectieuses. Le premier chapitre étudie comment les améliorations apportées aux réseaux d’égouts atténuent les impacts économiques des inondations provoquées par la pluie. Pour estimer l’effet causal de ces investissements, ce chapitre utilise un resserrement inattendu du financement fédéral américain en faveur des réseaux d’égouts, à la suite de l’amendement de 1977 à la politique du Clean Water Act. L'analyse empirique combine un nouveau modèle statistique du risque d'inondation induit par la pluie avec des données horaires sur la quantité de pluie dans les comtés et les codes postaux américains de 1996 à 2019. Les résultats indiquent que des investissements plus importants dans les réseaux d'égouts ont conduit à des réductions substantielles des inondations locales. Les bénéfices de ces investissements sont supérieurs à leurs coûts, économisant près de 23 millions de dollars pour le comté moyen. Dans l’ensemble, ces résultats mettent en évidence à quel point la détérioration des infrastructures publiques peut exacerber les conséquences du changement climatique. Le deuxième chapitre étudie le rôle des épidémies locales de maladies infectieuses dans l'adoption de systèmes centralisés d'approvisionnement en eau dans les premières villes américaines au XIXe siècle. À l’aide d’un vaste corpus de données provenant d’archives de journaux de 1800 à 1896, je construis un nouvel indicateur capturant les épidémies de fièvre jaune, de choléra et de fièvre typhoïde au niveau des villes. Les résultats indiquent que (1) les épidémies locales de maladies infectieuses ont entraîné une augmentation du nombre systèmes d'approvisionnement en eau construits par les villes et ont joué un rôle crucial dans la décision de construire environ 12% des ouvrages d’adduction d’eau en activité en 1897 ; (2) La réponse des villes aux épidémies de typhoïde a été deux fois plus importante que celle qui a suivi les épidémies de fièvre jaune ou de choléra. (3) Les entreprises privées ont construit davantage de nouveaux réseaux d’adduction d’eau après les épidémies locales, tandis que les gouvernements locaux ont procédé à davantage d’améliorations et d’extensions des réseaux d’adduction d’eau publics existants ainsi qu’à des rachats de sociétés d’eau privées. Enfin, je discute du rôle potentiel de divers facteurs sociodémographiques. Le troisième chapitre étudie les coûts économiques associés à une stratégie utilisée pour gérer les épidémies locales lors de la récente pandémie de COVID-19. Dans ce travail en collaboration avec Jian Tang, nous quantifions les effets de la politique ‘zéro-COVID’ à l’aide d’un riche ensemble de données sur les confinements au niveau des comtés en Chine et d’images satellitaires nocturnes. Nous constatons que des confinements plus stricts induisent une forte baisse de la luminosité nocturne au cours de la même période, suivie d’une lente reprise, qui se produit au moins deux trimestres après l’instauration du confinement. En l’absence de contagions généralisées, un comté soumis à un confinement total subit en moyenne une perte de PIB de 6% par rapport aux comtés non confinés. L’effet négatif est particulièrement persistant dans les zones où la production est dominée par les services, par opposition aux zones où la production est dominée par l’activité manufacturière. L’on note par ailleurs la présence d’effets d’entraînement à proximité des comtés confinés, mais ces effets sont de courte durée.

Validation et adaptation d’une approche géomatique pour délimiter en première approximation les zones inondées à partir du débit simulé par un modèle hydrologique distribué. - El Batti, Zainab (Maîtrise en sciences de l'eau, 2023)
Au Québec, les conditions printanières extraordinaires de 2017 et 2019 ont incité le gouvernement provincial à commander une mise à jour des cartes des zones inondables. La plupart des cartes existantes ne reflètent pas adéquatement l’aménagement actuel du territoire, ni l’aléa associé. Généralement, pour la cartographie, les modèles hydrodynamiques tel que HEC-RAS sont utilisés, mais ces outils nécessitent une expertise significative, des données hydrométriques et des relevés bathymétriques à haute résolution. Étant donnée la nécessité de mettre à jour ces cartes tout en réduisant les coûts financiers associés, des méthodes conceptuelles simplifiées ont été développées. Ces approches, y compris l’approche géomatique HAND (Height above the nearest drainage), qui reposent uniquement sur un modèle numérique d’élévation (MNE), sont de plus en plus utilisées. HAND permet de calculer la hauteur d’eau nécessaire pour inonder chaque pixel du MNE selon la différence entre son élévation et celle du pixel du cours d’eau dans lequel il se déverse. Les informations sur la géométrie hydraulique dérivées par HAND ainsi que l’application de l’équation de Manning permettent la construction d’une courbe de tarage synthétique (CTS) pour chaque tronçon de rivière homogène. Dans la littérature, cette méthode a été appliquée pour établir une cartographie de la zone inondable de première instance de grands fleuves aux États-Unis avec un taux de correspondance de 90% par rapport à l’utilisation de HEC-RAS. Elle n’a toutefois pas été appliquée sur de petits bassins versants, car ceux-ci engendrent des défis méthodologiques substantiels. Ce projet s’attaque à ces défis sur deux bassins versants Québécois, ceux des rivières à la Raquette et Delisle. Les conditions frontières des modèles sont dérivées d’un traitement statistique empirique des séries de débits simulés avec le modèle hydrologique HYDROTEL. Étant donnée l’absence de stations météorologiques sur le territoire à l’étude, des chroniques du système Canadien d’Analyse de la précipitation (CaPA) ont été utilisées pour cette modélisation hydrologique. Les résultats de ce projet pointent vers des performances satisfaisantes de l’approche géomatique HAND-CTS en comparaison avec le modèle hydrodynamique HEC-RAS (1D/2D et 2D au complet), avec des taux de correspondance entre les étendues des inondations supérieurs à 60 % pour les bassins versants de Delisle et à la Raquette. Les comparaisons étaient effectuées sur une gamme de débit allant d’un débit de période de retour de 2 ans jusqu’à un débit de plus de 350 ans. On notera que l’application sur la rivière à la Raquette a été développée dans les règles de l’art, incluant un processus de calage développé dans le cadre d’un projet de maitrise en sciences de l’eau connexe à ce mémoire, relativement à la longueur du tronçon, le calage vertical de la CTS en considérant la hauteur d’eau présente dans le cours d’eau lors du relevé LiDAR et sa précision verticale. Les résultats ont montré que le coefficient de précision globale le plus bas était de 98 % pour un débit de 350 ans, avec une précision de plus que 99 % pour les autres périodes de retour, ce qui représente une très bonne performance du modèle. Et par ailleurs, le coefficient de Kappa conditionnel humide variait entre 58 % et 28 %. Alors, que pour la rivière Delisle, l’application se veut naïve, c’est-à-dire sans calage préalable de la méthode HANDCTS. La précision globale a varié entre 83 % et 96 %, ce qui est considéré comme "très approprié" et une variation du coefficient Kappa conditionnel humide de 35,2 à 64,3 %. Alors que pour une différence d’élévations d'eau entre les élévations de référence et simulées, la performance était quantifiée par un RMSE qui variait pour les périodes de retour de 100 ans et de 350 ans respectivement de 4,5 m et de 7,1 m. Enfin, la distribution spatiale des différences d’élévations montre une distribution gaussienne avec une moyenne qui est à peu près égale à 0 où la plupart des erreurs se situent entre -0,34 m et 1,1 m La cartographie des zones inondables dérivée de HAND-CTS présente encore certains défis associés notamment à la présence d’infrastructures urbaines complexes (ex. : ponceaux, ponts et seuils) dont l’influence hydraulique n’est pas considérée. Dans le contexte où l’ensemble du Québec (529 000 km²) dispose d’une couverture LiDAR, les résultats de ce mémoire permettront de mieux comprendre les sources d’incertitude associées à la méthode HAND-CTS tout en démontrant son potentiel pour les bassins versants dépourvus de données bathymétriques et hydrométéorologiques. The 2017 and 2019 extraordinary spring conditions prompted the Quebec government to update flood risk maps, as most of them do not adequately reflect current land use and associated hazard. Generally, hydrodynamic models such as HEC-RAS are used for flood mapping, but they require significant expertise, hydrometric data, and high-resolution bathymetric surveys. Given the need to update these maps while reducing the associated financial costs, simplified conceptual methods have been developed over the last decade. These methods are increasingly used, including HAND (height above the nearest drainage), which relies on a Digital Elevation Model (DEM) to delineate the inundation area given the water height in a river segment. Furthermore, the river geometry derived from HAND data and the application of Manning’s equation allow for the construction of a synthetic rating curve (SRC) for each homogeneous river segment. In the scientific literature, this framework has been applied to produce first-instance floodplain mapping of large rivers. For example, in the Continental United States 90% match rates were achieved when compared to the use of HEC-RAS. However, this framework has not been validated for small watersheds, as substantial methodological challenges are anticipated. This project addresses these underlying challenges in two Quebec watersheds, the à la Raquette and Delisle watersheds. The boundary conditions of the HECRAS models were derived from an empirical statistical treatment of flow time series simulated by HYDROTEL, a hydrological model, using Canadian Precipitation Analysis Product (CaPA) time series. The results of this project point towards satisfactory performances, with match rates greater than 60 % for both watersheds. It should be noted that the application on the Delisle River is naive, that is without prior calibration of the HAND-SRC method. The overall accuracy ranged from 83.4 % to 96.2 % while the water surface elevation difference was quantified by an RMSE that was for the 100-year and 350-year return periods of 4.5 m and 7.1 m respectively and where most errors are between -0.34 m and 1.1 m representing a very good model comparing to similar studies. For à la Raquette, the application showed an overall accuracy coefficient of 98 % for a 350-year flow, with an accuracy of over 99 % for other return periods. The mapping of flood risk areas using HAND-SRC still faces certain challenges, notably the presence of complex urban infrastructures (e.g., culverts, bridges, and weirs) whose hydraulic influences are not considered by this geomatic approach. Given that most of Quebec (529,000 km²) topography has been digitized using LiDAR data, the results conveyed in this MSc thesis will allow for a better understanding of the sources of uncertainty associated with the application of the HAND-SRC method while demonstrating its potential for watersheds lacking hydrometeorological and high-resolution bathymetric data.

Caractériser et évaluer la capacité d'adaptation des communautés face aux risques naturels : le cas de Saint-Raymond - Hume, Jonathan (2019)
Les changements climatiques impactent de plus en plus la vie, le développement et la vulnérabilité de plusieurs communautés à travers le monde, lesquelles devant de plus en plus mitiger les risques naturels. Au Québec, la gestion des risques présente une philosophie de « retour à la normale » qui se penche davantage sur les dimensions d’intervention et de rétablissement. Cependant, à la lumière des incertitudes amenées par les changements climatiques, il est impératif que les communautés québécoises aient les capacités d’augmenter leur résilience face aux risques naturels qui s’accentuent rapidement. Ainsi, la capacité d’adaptation doit se retrouver au cœur de la gestion des risques. Cela dit, il existe peu d’outils d’évaluation de la capacité d’adaptation au Québec, entendue comme l’ensemble des ressources dynamiques disponibles et accessibles qui permettent une augmentation de la résilience et une diminution de la vulnérabilité en transformant positivement une communauté et son environnement. La présente recherche vise ainsi à développer une méthode d’analyse de la capacité d’adaptation des individus et des communautés québécoises touchées par les inondations à l’aide de systèmes d’information géographique (SIG), en utilisant la Ville de Saint-Raymond de Portneuf comme étude de cas. Ce projet se base principalement sur les concepts de vulnérabilité, de résilience et d’adaptation pour recenser des indicateurs pouvant servir à caractériser et évaluer la capacité des personnes et municipalités exposées aux inondations à mobiliser les ressources nécessaires pour non seulement atténuer les risques lors de tels événements, mais aussi mieux les prévenir et s’en préparer. Des données socioéconomiques et d’aménagement du territoire sont notamment mises à profit pour des fins d’analyse de même que des données issues d’un sondage effectué en 2014 à la suite d’une inondation majeure par la CAPSA, l’organisme de bassin versant de la région de Portneuf, en collaboration avec le comité Rivière de la Ville de Saint-Raymond.

Gestion intégrée des catastrophes en Afrique Subsaharienne : rôle de l’assurance, pour un système de gestion performant et la résilience des populations au Bénin - Goundjo, Antoine (2018)
Les variabilités et changements climatiques et les incapacités pour faire face à leurs risques, à leurs effets et, plus précisément, à gérer les catastrophes hydrométéorologiques (inondation et sécheresse) qui les accompagnent, viennent en ajouter aux vulnérabilités et aux problèmes, qui sont déjà une préoccupation en Afrique Subsaharienne et au Bénin. Face à leurs manifestations de plus en plus récurrentes – la faiblesse des systèmes de financement local de la gestion des catastrophes et le déficit des systèmes de protection sociale, qui témoignent des limites des capacités de transfert des risques de catastrophe – cette étude a identifié la structure (gouvernance-ressources), comme le problème essentiel de la gestion des catastrophes au Bénin. Une étude synthétique, étude de cas multiples avec trois niveaux d’analyse imbriqués, dans une approche qualitative, a permis de mieux comprendre comment, dans un contexte de pauvreté, l’intégration de la micro assurance climatique, modifie la structure, le processus et le résultat de la gestion des catastrophes et assure la performance du système et la résilience des populations. Elle a documenté les différents aspects de la structure et des vulnérabilités des systèmes et des populations et a identifié l’absence d’intégration de la micro assurance climatique aux systèmes de gestion des catastrophes, comme un problème au coeur de la complexité des déterminants de la résilience, aussi confrontée à une autre complexité, celle de la diversité des interconnexions entre les différentes catégories de risques, qui place la santé au coeur de tous les risques. La nécessité d’une gestion holistique du risque global, ou d’une gestion tout risque, telle que retenue par le Cadre d’Action de Hyōgo et le Cadre d’Action de Sendai; et l’importance d’apporter une réponse en accord au contexte et à son profil de risques, qui prend l’option pour la "démocratisation" d’une micro assurance climatique, gouvernée sur la base de fondements idéologiques d’équité et d’efficience, cette recherche a préconisé – pour une gestion plus rationnelle, pertinente, efficace et efficiente des catastrophes – une intégration de trois systèmes : le système de la gestion des catastrophes; le système de protection sociale, y compris celui de la micro assurance climatique, et le système de la santé; tous reconnus outillés pour la gestion des risques. Elle a retenu, qu’une telle approche saurait aussi assurer une gestion efficace du changement qu’induirait l’intégration de la micro assurance climatique à la gestion des catastrophes; de ii même qu’une meilleure utilisation des outils et méthodes de sensibilisation, de prévention, de prévision et d’évaluation des risques et des dommages dont recèlent les pratiques en micro assurance climatique. Elle constate que la réussite de l’intégration de la MAC et son développement sont essentiellement plus déterminés par les acteurs et leurs intérêts, que par les ressources financières, même si elles sont aussi indispensables. Cette recherche préconise qu’à partir de choix de modèles et de modes d’intégration bien étudiés, son intégration ou sa prise en compte dans les différents programmes d’aide et de protection sociale mis en oeuvre au Bénin pourrait être, à travers les subventions de l’État, un moyen de mobilisation de fonds en faveur de son financement et de sa viabilité/durabilité. Ce financement pourra aussi s’appuyer sur les mécanismes traditionnels de financement de l’assurance, de la micro assurance, des changements climatiques et de la réduction des risques de catastrophe au Bénin, en Afrique et dans le monde. C’est pourquoi, en termes de gouvernance, ce travail soutien une restructuration avec une gestion entièrement centrée sur les communes, dans une approche des services de première ligne avec les réseaux de services ; en termes de ressources, il a aussi analysé les conditions et les possibilités de développement d’une micro assurance climatique, qui dépend avant tout de la qualité de la gestion des catastrophes (capacités à réduire les risques et limiter les pertes ou capacités à induire la résilience des systèmes et des populations). Cette approche puise dans les réalités et pratiques endogènes de gestion des catastrophes et surtout de protection sociale ou de transfert de risques ; elle s’inspire des bonnes pratiques d’ailleurs ; elle contribue à instaurer l’équité, comme principe de la gestion intégrée des catastrophes et, au-delà de la résilience, à susciter une convergence des efforts pour l’autonomisation de la structure et des populations, face aux manifestations catastrophiques des inondations et de la sécheresse. Cette recherche pense qu’il faut oser la micro assurance universelle pour la gestion des catastrophes hydrométéorologiques; qu’elle est réalisable ou faisable, même en contexte de pauvreté; et qu’il est aussi possible de combiner micro assurance climatique universelle et assurance médicale universelle, dans une dynamique qui mobilise des approches efficientes et les intérêts.

Improving ensemble streamflow forecasts through targeted post-processing and rating curve uncertainty analysis - Askarinejad, Alireza (2024)
Abstract : Flood forecasting plays a pivotal role in effective water resource management and flood risk mitigation. Despite recent advancements, existing ensemble forecasting systems often grapple with issues of unreliability and under-dispersion. The uncertainty in ensemble forecasts can emanate from various sources, including inputs like precipitation, temperature, and streamflow, as well as initial conditions, model structure and parameters, and boundary conditions. Over the past two decades, numerous endeavors have been made to address bias and under-dispersion through the introduction of various statistical post-processing methods in meteorological and hydrological forecasts. However, a significant challenge lies in selecting the appropriate method and strategy in the forecast chain. Limited research has addressed the integration of pre-processing and post-processing in streamflow ensemble forecasting. Moreover, existing studies have generally focused on lumped hydrological models, while the performance of this integration in distributed hydrological models remains scarcely examined. On the other hand, streamflow data, often indirectly measured through rating curves, are particularly susceptible to errors. While various methods have been proposed to estimate rating curve uncertainty (RCU), the impact of RCU on streamflow forecasting system performance remains underexplored. In addition, current post-processing methods utilized in streamflow forecasting systems have disregarded the inherent uncertainty in observational streamflow data. Thus, this thesis delves into the potential and hurdles associated with considering different sources of uncertainty in flood forecasting systems and their impact on system performance. The primary objectives entail 1) assessing and identifying optimal scenarios from pre-processing of both temperature and precipitation and post-processing of streamflow forecasts approaches, or a combination thereof, and 2) evaluating the consideration of rating curve uncertainty on flood forecasting system performance through incorporating into targeted post-processing methodologies. The thesis focuses on a short-range ensemble streamflow forecasting framework spanning lead times of 1 to 5 days for the au Saumon watershed in southern Quebec, Canada. This watershed, being flood-prone, encountered significant challenges during the 2019 and 2017 flood events, including widespread inundation, road closures, and damage to property and infrastructure. Enhancing streamflow ensemble forecasts and upgrading flood forecasting systems holds the potential to greatly benefit decision-makers and the local populace. Chapter 4 (Results part 1), presented as a scientific article, thus delves into assessing and employing various pre- and post-processing strategy scenarios within the flood forecasting framework employing a spatially distributed hydrological model. By applying different statistical processing and bias correction techniques, the performance and quality of ensemble streamflow forecasts were evaluated across different scenarios. The findings highlight biases and under-dispersion as significant factors affecting raw ensemble forecasts. Pre-processing partially improves raw forecasts but doesn't fully address bias in under-dispersed forecasts. Combining pre- and post-processing enhances forecast skill and reliability, albeit with some variations compared to post-processing alone. Integrating flood events into the training dataset and optimizing its length improves the effectiveness of processing methods, underscoring the critical role of data management strategies in enhancing streamflow forecasting systems. Subsequently, Chapter 5 (Results part 2) , evaluates the consideration of rating curve uncertainty, derived from the Voting Point Method (VPM) and Bayesian Rating curve (BaRatin) estimation methods, on the performance of streamflow ensemble forecasts by integrating into a targeted post-processing approach using Weighted Ensemble Dressing (WED) and Cumulative Distribution Function Matching (CDFM) post-processing methods. Post-processing without RCU enhances forecasting system skill and reliability but overlooks the inherent uncertainty in observational data, posing concerns about its effectiveness. Conversely, integrating RCU improves forecast skill, reliability, and effectively addresses observational data uncertainty, offering a notable advantage over traditional post-processing methods. Comparing WED and CDFM post-processing methods highlighted nuanced differences in forecast outcomes, influenced by uncertainty estimation techniques. Both methods showed favorable accuracy metrics, with RCU integration, especially from VPM, notably enhancing forecast quality. However, variations in RCU from different estimation methods may lead to forecast underestimation or overestimation, warranting careful consideration. These findings collectively shed light on the potential and challenges associated with incorporating different sources of uncertainty into flood forecasting systems.

An urban political ecology of flood control and population relocation in Ouagadougou - Burkina Faso - Bamba, Madiara (Concordia University, 2022)
Globally, the number of people at risk from flooding has been increasing since 2000, with the population from the South being more vulnerable. Millions of households are displaced by disasters every year. In 2009, the city of Ouagadougou in Burkina Faso experienced its most disastrous flood ever recorded. As a response, the government designed a permanent relocation plan in Yagma, a village located outside the city of Ouagadougou. The relocation plan disrupted the livelihoods of the households that were affected by the flood, leading many of them to return and rebuild their houses in flood prone areas. This paper contributes to a body of literature analyzing the heritage of postcolonialism on the flood vulnerability on the poorer communities in Ouagadougou. Using a political ecology frame, the thesis attempts to understand how the government of Burkina Faso and flood victims understand land and belongings, and how that understanding shaped the relocation program. After interviewing flood victims and government officials, an analysis revealed that contrasting views are at work. A perspective based on technical calculations and a neo-colonialist vision of development, on the one hand, and a grounded perspective based on relationships to the land and each other, on the other.

Développement d’approches statistiques multivariées pour les modèles de copules, applications en hydrologie. - Ben Nasr, Iméne (Doctorat en sciences de l'eau, 2021)
Les études portant sur les évènements hydrologiques extrêmes sont d’une grande importance vu leurs nombreux impacts socio-économiques. Ces études reposent dans une large mesure sur la capacité à estimer adéquatement les risques associés à ces évènements. Dans ce cadre, l’analyse fréquentielle (AF) est une des approches les plus utilisées pour la modélisation et l’estimation des risques associés aux évènements extrêmes. Généralement, ces évènements sont caractérisés par plusieurs variables dépendantes, comme le volume, la pointe et la durée pour les crues. Par conséquent, l'analyse de chacune de ces variables séparément ne peut pas fournir une évaluation complète des risques et peut engendrer des pertes de vies humaines ou de biens associés à une sous estimation, ou une augmentation des coûts des ouvrages hydrauliques associés à une surestimation. L’AF multivariée (AFM) permet de pallier ce problème en considérant simultanément ces variables. L’AF classique est basée sur trois hypothèses à savoir l’homogénéité, la stationnarité et l’indépendance. Par ailleurs, différentes conditions non standards telles que la complexité topographique, les perturbations par les aménagements urbains et les changements climatiques peuvent influencer la réponse hydrologique. De telles conditions rendent la prédétermination des crues, par les méthodes classiques d’AFM, un exercice non efficace et mal adapté à de tels contextes. L’objectif de cette thèse consiste à proposer de nouvelles méthodes plus prometteuses pour l'analyse et la modélisation des variables hydrologiques à la fois dans un cadre multivarié et en l’absence de l’hypothèse d’homogénéité. Ces méthodes visent à contourner les limites de celles utilisées dans la littérature. Ces nouvelles méthodes, basées sur les copules, permettent une meilleure estimation des risques des extrêmes hydrologiques en tenant compte des interactions et es dépendances entre les différentes variables. Par conséquent, les gestionnaires des ressources hydriques peuvent prendre des décisions éclairées et mieux adaptées au contexte actuel. Précisément, nous nous intéressons dans une première partie à tester l’homogénéité des séries hydrologiques multivariées. Pour ce faire, nous avons proposé un nouveau test, basé sur les L moments multivariés, capable de détecter la rupture dans la structure de dépendance des variables hydrologiques. Les résultats obtenus montrent la bonne performance du test proposé sous différents scénarios. Par la suite, dans le but de modéliser l’hétérogénéité des séries hydrologiques multivariées, un modèle de mélange de copules a été mis au point. Dans ce cadre, nous avons proposé une nouvelle méthode pour l’estimation des différents paramètres du modèle. La méthode proposée est basée sur l’utilisation des algorithmes génétiques. Sa performance est illustrée sur des séries simulées. Les résultats obtenus montrent que la méthode proposée est un outil efficace capable de fournir de bonnes estimations, en particulier dans un contexte hydrologique. Finalement, deux nouveaux tests d’adéquation pour les copules multiparamètres ont été développés. Le but de ces tests est de vérifier la qualité de l’ajustement de la copule aux données et améliorer ainsi l’estimation des risques associés aux évènements extrêmes. Les résultats révèlent que les tests proposés performent bien dans le contexte hydrologique. Studies of hydrological extreme events are of great importance given their many socio-economic impacts. These studies rely on the ability to adequately estimate the associated risk. In this context, frequency analysis (FA) is one of the most widely used approaches for modeling and estimating the risks associated with extreme events. Generally, these events are characterized by several correlated random variables. Therefore, analyzing each of these variables separately cannot provide a complete risk assessment and may result in loss of life or property associated with an underestimation, or an increase in the costs of hydraulic structure associated with an overestimation. Multivariate FA (MFA) overcomes this problem by simultaneously considering these variables. Classical FA is based on three assumptions namely homogeneity, stationarity and independence. However, different non-standard conditions such as topographic complexity, disturbances by urban development and climate change can influence the hydrological response. Such conditions make flood predetermination, by conventional MFA methods, an ineffective exercise and unsuitable to such contexts. The main objective of this thesis is to propose new and more promising methods for the analysis and modeling of hydrological variables both in a multivariate framework and in the lack of the homogeneity assumption. These methods aim to overcome the limitations of classical methods used in the literature. These new proposed methods, based on copulas, allow a better estimation of the risks associated to hydrological extremes by taking into account the dependence between the different variables. As a result, water resource managers can make informed decisions that are better suited to the current context. In the first part, we propose a novel statistical test for multivariate heterogeneity detection, based on copula and multivariate L-moments. A simulation study is conducted to evaluate the performance of the proposed test and to compare it with those of existing tests. Results show the ability of the proposed test to discriminate homogeneous and inhomogeneous series. In the second part, we propose a new model based on mixtures of copulas that take into account the heterogeneity of multivariate hydrological series. To estimate the components of this model, we propose a new parameter estimation approach, based on the maximum pseudo-likelihood using genetic algorithms. Results indicate that the proposed method estimates more accurately the parameters even with small sample sizes compared to the existing classical EM method. In the last part, we introduce new goodness of fit (GOF) tests specifically for multiparameter copulas and adapted to hydrometeorological context. More precisely, the proposed GOF tests are based on multivariate L moments. A simulation study is conducted to evaluate and compare the performances of the proposed tests. The results confirm the usefulness of the new GOF tests in comparison with some well-established ones.

Quel regard porter sur le travail social à l’ère des changements climatiques? : le cas des inondations (2017-2019) au Québec - Hamelin, Marilou (2021)
Les changements climatiques anthropogéniques posent des défis énormes pour toutes les sociétés humaines. Ces défis majeurs mettront à l’épreuve les capacités d’adaptation des États et de ses institutions et des communautés partout dans le monde et devront se résoudre par un élan de solidarité humaine afin d’en atténuer les conséquences. Le Canada connaît déjà un réchauffement climatique important. Le pays a d’ailleurs récemment été touché par des événements climatiques extrêmes : des canicules, des feux de forêt, une sécheresse anormale et des inondations dont l’intensité est prévue d’augmenter avec les changements climatiques anthropogéniques. La province du Québec a quant à elle été touchée par de fortes inondations entre 2017 et 2019. L’objectif principal de la présente étude vise à discuter la manière dont le paradigme écosocial peut faire évoluer le travail social en tant que champ de savoir et d’intervention dans un contexte de changements climatiques. Cette étude s’est appuyée sur des données issues de groupes focus réalisés avec des intervenants suite aux inondations survenues au Québec (2017-2019). Notre analyse vise les interventions réalisées en contexte d’inondations, dans le sud de la province, mise en œuvre par le système de santé. Les données ont été collectées lors d’entrevues de groupe réalisées avec des intervenants psychosociaux et des gestionnaires de CI(U)SSS au courant des mois d’octobre et de novembre 2019. Les thèmes suivants ont émergé des analyses: les caractéristiques des inondations de 2019, les divergences d’opinions vis-à-vis des changements climatiques, l’aide et le soutien apportés durant les inondations et la participation citoyenne. J’insisterai également sur l’exacerbation possible des inégalités sociales dans ce contexte. D’autres thèmes se sont également révélés importants : l’engagement des intervenants psychosociaux, la participation et la décentralisation des décisions politiques. Enfin, mes réflexions porteront sur les conséquences sociales qu’entrainent les inondations et sur les types de pratiques sociales qui s’avèrent pertinentes à l’ère des changements climatiques et dans un contexte d’urgence.

Processus de rétablissement et attachement au lieu dans un contexte de cumul d’inondations : perspective des résident.es d’un quartier socioéconomiquement défavorisé de Gatineau - Hamel, Ariane (Université du Québec en Outaouais, 2024)
Dans la dernière décennie, le Québec a été touché par plusieurs épisodes d’inondations majeures. C’est le cas des communautés riveraines de Pointe-Gatineau, frappées par des inondations historiques en 2017, 2019 et 2023. Depuis, le départ d’une grande partie des riverains de ce quartier socio-économiquement défavorisé et la destruction de plusieurs maisons laissent un grand vide. La présence de nombreux lots vacants amène de l’incertitude parmi les citoyen.nes qui sont resté.es, dans ce qui est considéré comme l’un des plus vieux quartiers de Gatineau (Conseil régional de l'environnement et du développement durable de l'Outaouais, 2021). Bien que ce domaine d’étude soit en émergence, on observe dans la littérature que l’attachement des individus à leur milieu suivant une ou des catastrophes exercerait une influence sur leur processus de rétablissement. Cette étude s’intéresse donc au processus de rétablissement d’individus provenant d’un quartier socioéconomiquement défavorisé qui ont vécu un cumul d’inondations, et au rôle de l’attachement au lieu dans ce processus. Cette recherche mobilise le cadre de désorientation et de réorientation proposé par Cox et Perry (2011) pour expliquer le processus de rétablissement d’individus dans un lieu modifié par un désastre. L’attachement au lieu est conceptualisé en fonction des dimensions recensées par Raymond et ses collègues (2010) et du sentiment d’être chez soi par Cox et Perry (2011). Quatorze personnes sinistrées qui ont vécu les inondations de 2017 et de 2019 dans le quartier de Pointe-Gatineau ont été rencontrées lors d’entrevues individuelles ou familiales en 2023. Parmi ce nombre, neuf demeurent encore dans les communautés riveraines de Pointe-Gatineau, alors que cinq ont quitté le quartier après les inondations de 2019. Les résultats révèlent que l’attachement au lieu joue un rôle prédominant dans le processus de rétablissement des sinistré.es. Selon les participant.es, l’attachement au lieu contribue à l’étape de désorientation ou favorise au contraire la réorientation. Les résultats soulignent en particulier que l’attachement que les participant.es ressentent envers leur domicile et leur environnement naturel et bâti constitue une motivation importante à vouloir demeurer dans le quartier inondable. Par contre, la recherche montre que des facteurs autres que la relation au lieu influencent également le processus de rétablissement, tels que la difficulté à naviguer dans les démarches administratives entourant les programmes d’indemnisation du gouvernement, le fait d’appartenir à un groupe vulnérable, le soutien social et certaines caractéristiques personnelles. De même, l’expérience de vivre plusieurs inondations amène des spécificités qui influencent elles aussi le processus de rétablissement. Les résultats dévoilent notamment des stratégies d’adaptation mises en place par les personnes participantes qui ont décidé de demeurer dans leur quartier. Les stratégies acquises avec l’expérience font en sorte qu’elles se sentent davantage préparées pour des éventuelles inondations. Cette recherche contribue à la littérature émergente qui s’intéresse au processus de rétablissement d’individus touchés par un cumul d’inondations et au rôle de l’attachement au lieu sur ce processus. Elle permet d’offrir des pistes de réflexion aux différents acteurs qui accompagnent les personnes sinistrées avant, pendant et après des inondations et propose des recommandations en ce sens.

Espaces amphibiens, pouvoir et mémoire: les fluctuations de la rivière Sainte-Anne - Bouchard-Bastien, Emmanuelle (2023)
This thesis examines the main socio-environmental relationships related to recurrent floodings in the Sainte-Anne River watershed by mobilizing the history of land use, local knowledge and risk management policies. From a political ecology perspective, these relationships are part of both social representations of nature, power dynamics associated with the appropriation of ressources and multiple temporalities. By also mobilizing the theoreticals frameworks of the anthropology of disasters and amphibian anthropology, this study allow to retrace step by step what “flood zone” is as a socially constructed space by the authorities, and go back to the source of the advent of “flood” as a catastrophic event, where rising waters have been part of the characteristics of these territories since the beginning of the sedentarization of its inhabitants. Based on 93 semi-directed interviews (76 residents and 17 institutions stakeholders) realized between February to October 2019, non-participant observation and documentary research in municipal and regional archives, this ethnography of the Sainte-Anne River watershed allows a unique incursion with Quebec riverside residents who live with recurrent rising waters. Through four case studies (Saint-Raymond, Saint-Alban, Saint-Casimir and Sainte-Anne-de-la-Pérade), historical contexts of occupation of the territory were documented and significant events were described by focusing on local residents adaptation strategies and anticipated management by institutional stakeholders. The result is a portrait, in a temporal perspective, of the relationship of cohabitation between residents and the river and its overflows. This cohabitation is characterized by tensions and paradoxes associated with different social representations of water and temporality that coexist within the actors, as well as changes in power relations towards the environment. Cette thèse examine les principaux rapports socio-environnementaux liés aux inondations récurrentes dans le bassin versant de la rivière Sainte-Anne en mobilisant l’histoire de l’occupation du territoire, les savoirs locaux et les politiques de gestion des risques. Dans une perspective d’écologie politique, ces rapports s’inscrivent à la fois dans les représentations sociales de la nature, les dynamiques de pouvoir associées à l’appropriation des ressources et des temporalités multiples. En puisant également dans les cadres théoriques de l’anthropologie des catastrophes et de l’anthropologie amphibienne, cette étude permet notamment de retracer pas à pas ce qu’est la « zone inondable » en tant qu’espace construit socialement par les autorités, et de remonter à la source de l’avènement de « l’inondation » comme étant un événement catastrophique, alors que la montée des eaux fait partie des caractéristiques de ces territoires depuis le début de la sédentarisation des habitants. Basée sur 93 entrevues semi-dirigées (76 riverains et 17 acteurs institutionnels) menées de février à octobre 2019, de l’observation non participante et une recherche documentaire dans les archives municipales et régionales, cette ethnographie du bassin versant de la rivière Sainte-Anne permet une incursion unique auprès de citoyens québécois qui vivent avec la montée récurrente des eaux. Pour quatre municipalités riveraines (Saint-Raymond, Saint-Alban, Saint-Casimir et Sainte-Anne-de-la-Pérade), les contextes historiques de l’occupation du territoire ont été documentés et les événements significatifs ont été décrits en focalisant sur les stratégies d’adaptation des résidents et la gestion menée par des acteurs institutionnels. En résulte un portrait, dans une perspective temporelle, de la relation de cohabitation entre les riverains et la rivière et ses débordements. Cette cohabitation est caractérisée par des tensions et des paradoxes associés aux différentes représentations sociales de l’eau et de la temporalité qui coexistent au sein des acteurs, ainsi qu’aux changements dans les rapports de pouvoir envers l’environnement.
Keywords: Infolettre; Infolettre_Mars_2023

Evidence-Based Framework to Manage Cyanobacteria and Cyanotoxins in Water and Sludge from Drinking Water Treatment Plants - Jalili, Farhad; Moradinejad, Saber; Zamyadi, Arash; Dorner, Sarah; Sauvé, Sébastien; Prévost, Michèle (Toxins, 2022)
Freshwater bodies and, consequently, drinking water treatment plants (DWTPs) sources are increasingly facing toxic cyanobacterial blooms. Even though conventional treatment processes including coagulation, flocculation, sedimentation, and filtration can control cyanobacteria and cell-bound cyanotoxins, these processes may encounter challenges such as inefficient removal of dissolved metabolites and cyanobacterial cell breakthrough. Furthermore, conventional treatment processes may lead to the accumulation of cyanobacteria cells and cyanotoxins in sludge. Pre-oxidation can enhance coagulation efficiency as it provides the first barrier against cyanobacteria and cyanotoxins and it decreases cell accumulation in DWTP sludge. This critical review aims to: (i) evaluate the state of the science of cyanobacteria and cyanotoxin management throughout DWTPs, as well as their associated sludge, and (ii) develop a decision framework to manage cyanobacteria and cyanotoxins in DWTPs and sludge. The review identified that lab-cultured-based pre-oxidation studies may not represent the real bloom pre-oxidation efficacy. Moreover, the application of a common exposure unit CT (residual concentration × contact time) provides a proper understanding of cyanobacteria pre-oxidation efficiency. Recently, reported challenges on cyanobacterial survival and growth in sludge alongside the cell lysis and cyanotoxin release raised health and technical concerns with regards to sludge storage and sludge supernatant recycling to the head of DWTPs. According to the review, oxidation has not been identified as a feasible option to handle cyanobacterial-laden sludge due to low cell and cyanotoxin removal efficacy. Based on the reviewed literature, a decision framework is proposed to manage cyanobacteria and cyanotoxins and their associated sludge in DWTPs.
Keywords: Dorner_Sarah

Quantifying the Probability of Decline in Quality: Implications for Selection Management in Northern Hardwood Forests - Moreau, Guillaume; Cecil-Cockwell, Malcolm J. L.; Achim, Alexis; Bédard, Steve; Guillemette, François; Caspersen, John (Forests, 2023)
Northern hardwoods are susceptible to a wide range of defects that can reduce the amount of sound wood with desirable qualities, such as the clear sapwood of sugar maple trees. Yet, the rate at which trees decline in quality due to the development of such defects has never been quantified in northern hardwood forests due to a dearth of repeat inventories that record the appearance of defects over time. As a result, it remains uncertain whether, and how, selection management reduces the probability of decline in quality. In this study, we quantify the rate at which trees decline in quality due to the development of defects, and we test several hypotheses regarding the influence of selection management on quality. Our results show that (1) the probability of decline in quality increases as trees grow larger; (2) crown dieback also increases the probability of decline in quality; (3) the probability of decline in quality is slightly lower in managed stands than in unmanaged stands, and (4) the probability of decline in quality increases with the mean annual temperature of the site. Finally, we combined our estimates of the probability of decline in quality with previous estimates of the probability of mortality to assess the overall risk associated with retaining trees of different species, sizes, and vigour profiles. The resulting metric can inform efforts to improve the management of northern hardwood forests by providing an integrated estimate of the risk that the value of a tree will be reduced, or eliminated, due to mortality or decline in quality.
Keywords: Guillemette_Francois

Potential for Sugar Maple to Provide High-Quality Sawlog Trees at the Northern Edge of Its Range - Guillemette, François; Bédard, Steve (Forest Science, 2019)
Abstract The management of sugar maple (Acer saccharum) at the northern edge of its range is mainly oriented toward timber production, from trees of higher grades. However, both the quality of mature trees in natural stands and how the quality may vary depending on the silvicultural treatment are unknown, especially under northern conditions. The objective of this study was to describe the variation in stem quality of mature maple trees (diameter >33 cm) according to climatic, geographic or soil variables, and to evaluate the effects of a first selection cutting cycle on this quality. Annual temperature (1.7–4.1° C) was the most important variable explaining differences in the proportion of higher-grade trees, with a 16 percent gain associated with every additional increase in degrees Celsius. The practice of a first selection cutting was associated with an 11 percent gain in this proportion. Although the actual proportion of high-quality trees was below 35 percent on the coolest sites, a proper tree selection through silviculture could likely improve this proportion in future decades, whereas the potential effects of climate change are unclear.
Keywords: Guillemette_Francois

Artefacts of disaster risk reduction: conceptualizing bottom-up initiatives of climate action in informal settlements - Lizarralde, Gonzalo; Herazo, Benjamín; Smith, David; Bornstein, Lisa; Gould, Kevin; Monsalve, Elsa; Ordoñez, Nicolás; López, Adriana; López, Oswaldo; Burdiles, Roberto; Araneda, Claudio; Olivera, Andrés (Disaster Prevention and Management: An International Journal, 2024)
Purpose Disaster risk reduction is of prime importance in informal settlements in the Global South, where several forms of vulnerability coexist. Policy and official programmes, however, rarely respond to the needs and expectations of citizens and local leaders living in these settlements. Even though these agents constantly attempt to reduce risks in their own way, we know very little about their activities, motivations and effective impact on risk reduction. Here we seek to conceptualize bottom-up initiatives to better grasp their origins, limitations and success. Design/methodology/approach Through a four-year action-research project in Colombia, Cuba and Chile, we theorize about the production of change by local agents. Through detailed case studies we explored the activism of 17 local leaders. Through narrative analysis we studied their motivations and explanations. Finally, by documenting 22 initiatives, we revealed effective changes in space. Findings In the face of risk and disasters, residents and leaders in informal settings engaged in symbolic, physical and social spaces of interaction. Their actions were guided by trust, emotions, time cycles and activism. Local agency was justified by narratives about risk and climate change that differ from those of authorities and scholars. Research limitations/implications There is still limited understanding of bottom-up initiatives in informal settings. It is crucial to conceptualize their origins, limitations and success. The focus on three specific countries necessitates further research for broader applicability and understanding. Practical implications A better comprehension of bottom-up actions is crucial for informing policies and programmes aimed at reducing risk in informal settings. Stakeholders must recognize the political, social and cultural roles of these actions for more impactful climate action. Originality/value We borrow Simon’s concept of “artefact” to introduce the notion of “Artefacts of Disaster Risk Reduction”, providing insights into the multifaceted nature of bottom-up initiatives. We also emphasize the simultaneous political and phenomenological character of these actions, contributing to a deeper understanding of their origins and impact.
Keywords: Infolettre; Infolettre_Ete_2024; Lizarralde_Gonzalo

The problem with net zero building policy: reflecting on the making, and future, of a global discourse - Hasan, L; Lizarralde, G; Lachapelle, E (IOP Conference Series: Earth and Environmental Science, 2023)
Abstract The Paris Agreement made net zero emissions a global target. In response, net zero carbon building standards have proliferated, making net zero a popular target for buildings. But to meaningfully contribute to global decarbonization efforts, net zero standards and the organizations who promote them, must be deemed legitimate. Given the building industry’s reputation for being highly fragmented and slow to change, how has this legitimacy been constructed? What are the implications of this legitimation process? This article seeks to answer these questions by exploring the narratives used by the World Green Building Council (WGBC) to legitimate Net Zero Carbon Buildings (NZCB) from 2015 to 2021. Our analysis is based on over 100 documents produced by the WGBC and 22 interviews with WGBC and Green Building Council representatives, policymakers, and industry actors. Results reveal six main storylines adopted by the WGBC to extend the legitimacy of sustainable green building movement actors to the new net zero governance space. This legitimation process allows the WGBC to develop and implement net zero standards quickly, but also creates tensions between efficiency and procedural integrity, potential and proven results, corporate and collective value. While NZCB are here to stay, these tensions highlight barriers to their wide-scale adoption and question their ability to deliver an economically viable, socially just, environmental, net zero transition.
Keywords: Lizarralde_Gonzalo

Assessing the long-term hydrological services provided by wetlands under changing climate conditions: A case study approach of a Canadian watershed - Fossey, Maxime; Rousseau, Alain N. (Journal of Hydrology, 2016)
The water content of wetlands represents a key driver of their hydrological services and it is highly dependent on short- and long-term weather conditions, which will change, to some extent, under evolving climate conditions. The impact on stream flows of this critical dynamic component of wetlands remains poorly studied. While hydrodynamic modelling provide a framework to describe the functioning of individual wetland, hydrological modelling offers the opportunity to assess their services at the watershed scale with respect to their type (i.e., isolated or riparian). This study uses a novel approach combining hydrological modelling and limited field monitoring, to explore the effectiveness of wetlands under changing climate conditions. To achieve this, two isolated wetlands and two riparian wetlands, located in the Becancour River watershed within the St Lawrence Lowlands (Quebec, Canada), were monitored using piezometers and stable water isotopes (δD – δ18O) between October 2013 and October 2014. For the watershed hydrology component of this study, reference (1986–2015) and future meteorological data (2041–2070) were used as inputs to the PHYSITEL/HYDROTEL modelling platform. Results obtained from in-situ data illustrate singular hydrological dynamics for each typology of wetlands (i.e., isolated and riparian) and support the hydrological modelling approach used in this study. Meanwhile, simulation results indicate that climate change could affect differently the hydrological dynamics of wetlands and associated services (e.g., storage and slow release of water), including their seasonal contribution (i.e., flood mitigation and low flow support) according to each wetland typology. The methodological framework proposed in this paper meets the requirements of a functional tool capable of anticipating hydrological changes in wetlands at both the land management scale and the watershed management scale. Accordingly, this framework represents a starting point towards the design of effective wetland conservation and/or restoration programs.
Keywords: Rousseau_Alain

Insights from socio-hydrological modeling to design sustainable wastewater reuse strategies for agriculture at the watershed scale - Jeong, Hanseok; Bhattarai, Rabin; Adamowski, Jan; Yu, David J. (Agricultural Water Management, 2020)

The diffusion of climate change adaptation policy - Schoenefeld, Jonas J.; Schulze, Kai; Bruch, Nils (Wiley Interdisciplinary Reviews: Climate Change, 2022)
Adapting to some level of climate change has become unavoidable. However, there is surprisingly limited systematic knowledge about whether and how adaptation policies have diffused and could diffuse in the future. Most existing adaptation studies do not explicitly examine policy diffusion, which is a form of interdependent policy-making among jurisdictions at the same or across different levels of governance. To address this gap, we offer a new interpretation and assessment of the extensive adaptation policy literature through a policy diffusion perspective; we pay specific attention to diffusion drivers and barriers, motivations, mechanisms, outputs, and outcomes. We assess the extent to which four motivations and related mechanisms of policy diffusion—interests (linked with learning and competition), rights and duties (tied to coercion), ideology, and recognition (both connected with emulation)—are conceptually and empirically associated with adaptation. We also engage with adaptation policy characteristics, contextual conditions (e.g., problem severity) and different channels of adapation policy diffusion (e.g., transnational networks). We demonstrate that adaptation policy diffusion can be associated with different mechanisms, yet many of them remain remarkably understudied. So are the effects of adaptation policy diffusion in terms of changes in vulnerability and resilience. We thus identify manifold avenues for future research, and provide insights for practitioners who may hope to leverage diffusion mechanisms to enhance their adaptation efforts. This article is categorized under: Policy and Governance > Multilevel and Transnational Climate Change Governance Vulnerability and Adaptation to Climate Change > Institutions for Adaptation

We said, they said: the politics of conceptual frameworks in disasters and climate change in Colombia and Latin America - Lizarralde, Gonzalo; Páez, Holmes; Lopez, Adriana; Lopez, Oswaldo; Bornstein, Lisa; Gould, Kevin; Herazo, Benjamin; Muñoz, Lissette (Disaster Prevention and Management: An International Journal, 2020)
Purpose Few people living in informal settlements in the Global South spontaneously claim that they are “resilient” or “adapting” to disaster risk or climate change. Surely, they often overcome multiple challenges, including natural hazards exacerbated by climate change. Yet their actions are increasingly examined through the framework of resilience, a notion developed in the North, and increasingly adopted in the South. To what extent eliminate’ do these initiatives correspond to the concepts that scholars and authorities place under the resilience framework? Design/methodology/approach Three longitudinal case studies in Yumbo, Salgar and San Andrés (Colombia) serve to investigate narratives of disaster risks and responses to them. Methods include narrative analysis from policy and project documents, presentations, five workshops, six focus groups and 24 interviews. Findings The discourse adopted by most international scholars and local authorities differs greatly from that used by citizens to explain risk and masks the politics involved in disaster reduction and the search for social justice. Besides, narratives of social change, aspirations and social status are increasingly masked in disaster risk explanations. Tensions are also concealed, including those regarding the winners and losers of interventions and the responsibilities for disaster risk reduction. Originality/value Our findings confirm previous results that have shown that the resilience framework contributes to “depoliticize” the analysis of risk and serves to mask and dilute the responsibility of political and economic elites in disaster risk creation. But they also show that resilience fails to explain the type of socioeconomic change that is required to reduce vulnerabilities in Latin America.
Keywords: Lizarralde_Gonzalo

Integrated assessment of climate change impact on surface runoff contamination by pesticides - Gagnon, Patrick; Sheedy, Claudia; Rousseau, Alain N.; Bourgeois, Gaétan; Chouinard, Gérald (Integrated Environmental Assessment and Management, 2016)
Pesticide transport by surface runoff depends on climate, agricultural practices, topography, soil characteristics, crop type, and pest phenology. To accurately assess the impact of climate change, these factors must be accounted for in a single framework by integrating their interaction and uncertainty. This paper presents the development and application of a framework to assess the impact of climate change on pesticide transport by surface runoff in southern Quebec (Canada) for the 1981-2040 period. The crop enemies investigated were: weeds for corn (Zea mays); and for apple orchard (Malus pumila), three insect pests (codling moth (Cydia pomonella), plum curculio (Conotrachelus nenuphar) and apple maggot (Rhagoletis pomonella)) and two diseases (apple scab (Venturia inaequalis) and fire blight (Erwinia amylovora)). A total of 23 climate simulations, 19 sites, and 11 active ingredients were considered. The relationship between climate and phenology was accounted for by bioclimatic models of the Computer Centre for Agricultural Pest Forecasting (CIPRA) software. Exported loads of pesticides were evaluated at the edge-of-field scale using the Pesticide Root Zone Model (PRZM), simulating both hydrology and chemical transport. A stochastic model was developed to account for PRZM parameter uncertainty. Results of this study indicate that for the 2011-2040 period, application dates would be advanced from 3 to 7 days on average with respect to the 1981-2010 period. However, the impact of climate change on maximum daily rainfall during the application window is not statistically significant, mainly due to the high variability of extreme rainfall events. Hence for the studied sites and crop enemies considered, climate change impact on pesticide transported in surface runoff is not statistically significant throughout the 2011-2040 period.
Keywords: Rousseau_Alain

Hydrological behaviour of an ice‐layered snowpack in a non‐mountainous environment - Paquotte, Andrea; Baraer, Michel (Hydrological Processes, 2022)
Abstract The increased frequency of mild rain‐on‐snow (R.O.S.) events in cold regions associated with climate change is projected to affect snowpack structure and hydrological behaviour. The ice layers that form in a cold snowpack when R.O.S. events occur have been shown to influence flowthrough processes and liquid water retention, with consequences for winter floods, groundwater recharge, and water resources management. This study explores interconnections between meteorological conditions, ice layer formation, and lateral flows during R.O.S. events throughout the 2018–2019 winter in meridional Quebec, Canada. Automated hydro‐meteorological measurements, such as water availability for runoff, snow water equivalent, and snowpit observations, are used to compute water and energy balances, making it possible to characterize a snowpack's internal conditions and flowthrough regimes. For compatibility assessment, water and energy balances‐based flowthrough scenarios are then compared to different hydro‐meteorological variables', such as water table or streamlet water levels. The results show an association between highly variable meteorological conditions, frequent R.O.S. events, and ice layer formation. Lateral flows were mainly observed during the early stage of the ablation period. The hydrologically significant lateral flows observed in the study are associated with winter conditions that are predicted to become more frequent in a changing climate, stressing the need for further evaluation of their potential impact at the watershed scale.
Keywords: Baraer_Michel; Infolettre; Infolettre_Ete_2023

Cumulative Effects of Watershed Disturbances and Run-of-river Dams on Mercury Cycling: Case Study and Recommendations for Environmental Managers - Amyot, M.; Bilodeau, F.; Tremblay, A.; Planas, D.; Walsh, D.; Ponton, D. E. (Environmental Management, 2024)
Abstract Run-of-river power plants (ROR) represent the majority of hydroelectric plants worldwide. Their environmental impacts are not well documented and are believed to be limited, particularly regarding the contamination of food webs by methylmercury (MeHg), a neurotoxin. RORs are typically installed in small rivers where combined effects of watershed disturbances with dam construction can complicate environmental management. We report a multi-year case study on the Saint-Maurice River (Canada) where an unpredicted temporary increase in MeHg accumulation in predator fish was observed after the construction of two ROR plants. The associated pondages acted as sedimentation basins for mercury (Hg) and organic matter from a watershed disturbed by a forest fire and by logging. This fresh organic carbon likely fueled microbial MeHg production. Hg methylation was more associated with environmental conditions than to the presence of Hg, and main methylating microbial groups were identified. A constructed wetland was a site of significant Hg methylation but was not the main source of the fish Hg increase. Organic carbon degradation was the main driver of MeHg accumulation at the base of the food chain whereas trophic levels explained the variations at the top of the food chain. Overall, carbon cycling was a key driver of Hg dynamics in this system, and ROR plants can cause temporary (ca. 12 years) Hg increase in food webs when developed in disturbed watersheds, although this increase is smaller than for large reservoirs. Recommendations for future ROR construction are to establish a good environmental monitoring plan with initial high temporal resolution and to consider recent and potential watershed disturbances in the plan.

Quarante ans de participation publique en environnement, aménagement du territoire et urbanisme au Québec : entre expression des conflits et gestion consensuelle - Bherer, Laurence; Gauthier, Mario; Simard, Louis (Cahiers de géographie du Québec, 2019)
En près de 40 ans, les revendications pour plus de participation et de transparence, ainsi que la diffusion du principe de développement durable ont profondément transformé les secteurs de l’environnement, de l’aménagement du territoire et de l’urbanisme. Au fil des décennies, divers types de dispositifs de participation publique ont vu le jour dans ces deux secteurs d’activité qui ont permis de démocratiser le rapport gouvernants / gouvernés et la relation entre les pouvoirs publics et la société civile. À partir d’une grille d’analyse axée sur deux dimensions – ouverture / fermeture et antagoniste / consensuel – nous analysons les différents dispositifs de participation publique à l’oeuvre dans ces deux secteurs. L’analyse tend à montrer que : 1) au cours des 40 dernières années, les dispositifs participatifs se sont multipliés ; 2) aux dispositifs participatifs traditionnels permettant l’expression des conflits et des oppositions se sont progressivement ajoutés des dispositifs davantage orientés vers la recherche du consensus et la résolution des conflits ; 3) de nos jours, ces deux grandes catégories de dispositifs cohabitent et peuvent parfois apparaître comme étant complémentaires et parfois comme étant contradictoires. , Over the past 40 years, demands for greater participation, transparency and the dissemination of the principle of sustainable development have transformed the areas of environment, land-use planning and urban planning. Over the decades, various types of public participation mechanisms have emerged in these sectors that helped democratize the rulers / governed report and the relationship between public authorities and civil society. Starting from a grid analysis based on two dimensions—opening / closing and antagonist / consensus—this article analyses the different public participation mechanisms at work in these two areas. Analysis tends to demonstrate that during the last forty years the number of participatory mechanisms has increased. Moreover, devices oriented towards the search for consensus and conflict resolution were gradually added to the traditional participatory mechanisms that allowed for the voicing of concerns and oppositions. Currently, these two broad categories of participatory tools coexist and can at times appear complementary and at others contradictory. , En casi cuarenta años, las reivindicaciones de mayor participación y transparencia, tanto como la difusión del principio de desarrollo sostenido, han transformado profundamente los sectores del medio ambiente, de la planificación territorial y del urbanismo. Con el correr de las décadas, varios tipos de dispositivos de participación pública surgieron en esos dos sectores de actividad que permitieron democratizar la relación gobernantes /  gobernados y la relación poderes públicos y la sociedad civil. Gracias a una tabla de análisis con dos coordenadas – apertura / cierre y antagonista /  consensual – analizamos diferentes dispositivos de participación pública que actúan en esos dos sectores. El análisis propone que: 1) durante los últimos cuarenta años, los dispositivos de participación han aumentado. 2) A los dispositivos participativos tradicionales que permiten la expresión de conflictos y oposiciones, se añadieron progresivamente dispositivos mejor orientados hacia la busqueda de consenso y de solución de conflictos. 3) Hoy, esas dos grandes categorías de dispositivos cohabitan y hasta parecen unas veces complementarias y otras contradictorias.
Keywords: Ouvrage_Collectif_Numéro1

Floodplain Management for All: Addressing Inequities and Meeting Needs of Indigenous Communities - Zimmerman, Olivia Nicole; Eison, Tanya; Carey, Robert G.; Carey, Robert F.; Levin, Phillip S. (Social Science Research Network, 2022)

Understanding Uncertainty in Probabilistic Floodplain Mapping in the Time of Climate Change - Zahmatkesh, Zahra; Han, Shasha; Coulibaly, Paulin (Water, 2021)
An integrated framework was employed to develop probabilistic floodplain maps, taking into account hydrologic and hydraulic uncertainties under climate change impacts. To develop the maps, several scenarios representing the individual and compounding effects of the models’ input and parameters uncertainty were defined. Hydrologic model calibration and validation were performed using a Dynamically Dimensioned Search algorithm. A generalized likelihood uncertainty estimation method was used for quantifying uncertainty. To draw on the potential benefits of the proposed methodology, a flash-flood-prone urban watershed in the Greater Toronto Area, Canada, was selected. The developed floodplain maps were updated considering climate change impacts on the input uncertainty with rainfall Intensity–Duration–Frequency (IDF) projections of RCP8.5. The results indicated that the hydrologic model input poses the most uncertainty to floodplain delineation. Incorporating climate change impacts resulted in the expansion of the potential flood area and an increase in water depth. Comparison between stationary and non-stationary IDFs showed that the flood probability is higher when a non-stationary approach is used. The large inevitable uncertainty associated with floodplain mapping and increased future flood risk under climate change imply a great need for enhanced flood modeling techniques and tools. The probabilistic floodplain maps are beneficial for implementing risk management strategies and land-use planning.

Challenges to enabling and implementing Natural Flood Management in Scotland - Waylen, K. A.; Holstead, K. L.; Colley, K.; Hopkins, J. (Journal of Flood Risk Management, 2018)
We explore factors that constrain implementation of Natural Flood Management ( NFM ), based on qualitative analysis of interviews with those influencing and enabling flood risk management in Scotland. NFM entails collaboration by multiple individuals and organisations to plan and deliver measures such as re‐meandering or buffer strips. Our interviewees identified many interacting issues. They particularly focused on difficulties in securing resources, and evidence gaps and uncertainties associated with NFM . Co‐ordination was not simple, often requiring new types of skill, expertise, and resources. NFM is thus outside the ‘comfort zone’ of many leading or engaged with flood risk management. These experiences echo and elaborate on other studies of attempts to encourage sustainable flood management. To tackle these challenges, practitioners should reflect how pre‐existing ideas and practices may shape and constrain new approaches to managing floods, while research is needed on specific strategies that can assist in enabling change.
Keywords: Ouvrage_Collectif_Numéro1

The Monetary Measurement of Flood Damage and the Valuation of the Proactive Policies in Sicily - Trovato, Maria Rosa; Giuffrida, Salvatore (Geosciences, 2018)
Although floods, as well as other natural disasters, can be considered as relevant causes of intra-generational inequalities, frequent catastrophes and the resulting damage to the territory can be seen as a consequence of a generalized indifference about future. Land protection is one of the societal issues typically concerning inter-generational solidarity, involving the administrative system in the implementation of proactive policies. In the last three decades, the widespread demand for subsidiarity has made local communities more and more independent, so that attention to the long-term effects—typically concerning the territorial system as a whole at geographical scale—has been dispersed, and the proactive policies that come from the central government have become more ineffective. Regarding the case of the 2009 flood in the Fiumedinisi-Capo Peloro river basin in North Eastern Sicily, we propose an economic valuation of the land protection policy. This valuation, compared to the cost of recovery of the damaged areas, can provide helpful information on the decision-making process concerning the trade-off between reactive and proactive land policy. The economic value of land protection was calculated by means of the method of the imputed preferences, to obtain a real measure of the social territorial value from the point of view of the harmony between social system and environment. This method consists of an estimate based on the attribution of the expenditures according to the importance of the different areas. Since the value of land protection has been calculated by discounting the expenditures stream, some considerations about the economic significance of the proactive policy are referred to the role played by the social discount rate in the inter-temporal economic calculation.

Dynamics of household welfare change and analysis of coping strategies during floods: an empirical investigation - Senapati, Sibananda (International Journal of Social Economics, 2024)
Purpose This study aims to understand the socioeconomic impact of flood events on households, especially household welfare in terms of changes in consumption and coping strategies to deal with flood risk. This study is based on Bihar, one of the most frequently flood-affected, most populous and economically backward states in India. Design/methodology/approach Primary data were collected from 700 households in the seven most frequently flood-affected districts in Bihar. A total of 100 individuals from each district were randomly selected from flood-affected villages. Based on a detailed literature review, an econometric (probit) model was developed to test the null hypothesis of the availability of consumption insurance, and the multivariate probability approach was used to analyze the various coping strategies of these households. Findings The results of this study suggest that flood-affected households maintain their consumption by overcoming various losses, including income, house damage and livestock loss. Households depend on financial transfers, borrowings and relief, and migrate to overcome losses. Borrowing could be an extra burden as the government compensates for house damage and crop loss late to the affected households. Again, there is no compensation to overcome livelihood loss and deal with occurrences of post-flood diseases, which further emphasizes the policy implications of strengthening the health infrastructure in the state and generating alternative livelihood opportunities. Originality/value This study discusses flood risk in terms of changes in household welfare, identifies the most effective risk-coping capabilities of rural communities and contributes to the shortcomings of the government insurance and relief model. Peer review The peer review history for this article is available at: https://publons.com/publon/10.1108/IJSE-07-2023-0569

Flood impact on income inequality in the Itapocu River basin, Brazil - Silva Araújo, Rafael; Ohara, Miho; Miyamoto, Mamoru; Takeuchi, Kuniyoshi (Journal of Flood Risk Management, 2022)
Abstract Disasters worldwide tend to affect the poorest more severely and increase inequality. Brazil is one of the countries with high income‐inequality rates and has unplanned urbanization issues and an extensive disaster risk profile with little knowledge on how those disasters affect people's welfare. Thus, disasters often hit the poorest hardest, increasing the country's income inequality and poverty rates. This study proposes a method to assess the impact of floods on households spatially based on their income levels by conducting flood analysis and income analysis. The method is applied to the Itapocu River basin (IRB) located in Santa Catarina State, Brazil. The flood is assessed by conducting rainfall analysis and hydrological simulation and generating flood inundation maps. The income is evaluated using downloaded 2010 census data and a dasymetric approach. Flood and income information is combined to analyze flood‐impacted households by income level and flood return period. The results confirm the initial assumption that flood events in the IRB are more likely to affect the lowest‐income households rather than the highest‐income levels, thus, increasing the income inequality.

A network-based analysis of critical resource accessibility during floods - Preisser, Matthew; Passalacqua, Paola; Bixler, R. Patrick; Boyles, Stephen D. (2023)
Numerous government and non-governmental agencies are increasing their efforts to better quantify the disproportionate effects of climate risk on vulnerable populations with the goal of creating more resilient communities. Sociodemographic based indices have been the primary source of vulnerability information the past few decades. However, using these indices fails to capture other facets of vulnerability, such as the ability to access critical resources (e.g., grocery stores, hospitals, pharmacies, etc.). Furthermore, methods to estimate resource accessibility as storms occur (i.e., in near-real time) are not readily available to local stakeholders. We address this gap by creating a model built on strictly open-source data to solve the user equilibrium traffic assignment problem to calculate how an individual's access to critical resources changes during and immediately after a flood event. Redundancy, reliability, and recoverability metrics at the household and network scales reveal the inequitable distribution of the flood's impact. In our case-study for Austin, Texas we found that the most vulnerable households are the least resilient to the impacts of floods and experience the most volatile shifts in metric values. Concurrently, the least vulnerable quarter of the population often carries the smallest burdens. We show that small and moderate inequalities become large inequities when accounting for more vulnerable communities' lower ability to cope with the loss of accessibility, with the most vulnerable quarter of the population carrying four times as much of the burden as the least vulnerable quarter. The near-real time and open-source model we developed can benefit emergency planning stakeholders by helping identify households that require specific resources during and immediately after hazard events.

Beyond ‘just’ flood risk management: the potential for—and limits to—alleviating flood disadvantage - O’Hare, Paul; White, Iain (Regional Environmental Change, 2018)
The threat of flooding poses a considerable challenge for justice. Not only are more citizens becoming exposed to risk, but they are expected to play increasingly active roles in flood risk management. However, until recently, few efforts have charted broader understandings of disadvantage relating to flood risk exposure. Drawing upon social science scholarship that has long been sensitive to concerns related to justice, we deploy and develop the notion of flood disadvantage as a means to assess the challenges to more ‘just’ flood risk management. We contend that the concept of flood disadvantage offers a useful lens to appreciate the constraints of technical approaches to flood risk management, in particular, its limited ability to incorporate complex social elements such as how individuals have differing vulnerabilities and sensitivities to flooding and uneven abilities to engage with risk agendas. The notion highlights the compounding interactions between flooding and other social disadvantages across multiple public policy areas and scales. We argue a fuller acknowledgement of the socio-spatial-temporal dimensions of intersecting disadvantages can help sensitise technical risk analyses that tend to see people and communities as homogeneous entities in a given spatiality. In doing so we can better reveal why some individuals or communities are more vulnerable to disasters or are slower to recover than others. Finally, we outline the challenges in turning more ‘just’ flood risk management from an abstract notion into one that could inform future practice.

Flood Risk Management: Exploring the Impacts of the Community Rating System Program on Poverty and Income Inequality - Noonan, Douglas S.; Sadiq, Abdul‐Akeem A. (Risk Analysis, 2018)
Abstract Flooding remains a major problem for the United States, causing numerous deaths and damaging countless properties. To reduce the impact of flooding on communities, the U.S. government established the Community Rating System (CRS) in 1990 to reduce flood damages by incentivizing communities to engage in flood risk management initiatives that surpass those required by the National Flood Insurance Program. In return, communities enjoy discounted flood insurance premiums. Despite the fact that the CRS raises concerns about the potential for unevenly distributed impacts across different income groups, no study has examined the equity implications of the CRS. This study thus investigates the possibility of unintended consequences of the CRS by answering the question: What is the effect of the CRS on poverty and income inequality? Understanding the impacts of the CRS on poverty and income inequality is useful in fully assessing the unintended consequences of the CRS. The study estimates four fixed‐effects regression models using a panel data set of neighborhood‐level observations from 1970 to 2010. The results indicate that median incomes are lower in CRS communities, but rise in floodplains. Also, the CRS attracts poor residents, but relocates them away from floodplains. Additionally, the CRS attracts top earners, including in floodplains. Finally, the CRS encourages income inequality, but discourages income inequality in floodplains. A better understanding of these unintended consequences of the CRS on poverty and income inequality can help to improve the design and performance of the CRS and, ultimately, increase community resilience to flood disasters.

Causes, impacts and patterns of disastrous river floods - Merz, Bruno; Blöschl, Günter; Vorogushyn, Sergiy; Dottori, Francesco; Aerts, Jeroen C. J. H.; Bates, Paul D.; Bertola, Miriam; Kemter, Matthias; Kreibich, Heidi; Lall, Upmanu; Macdonald, Elena (2021)
Disastrous floods have caused millions of fatalities in the twentieth century, tens of billions of dollars of direct economic loss each year and serious disruption to global trade. In this Review, we provide a synthesis of the atmospheric, land surface and socio-economic processes that produce river floods with disastrous consequences. Disastrous floods have often been caused by processes fundamentally different from those of non-disastrous floods, such as unusual but recurring atmospheric circulation patterns or failures of flood defences, which lead to high levels of damage because they are unexpected both by citizens and by flood managers. Past trends in economic flood impacts show widespread increases, mostly driven by economic and population growth. However, the number of fatalities and people affected has decreased since the mid-1990s because of risk reduction measures, such as improved risk awareness and structural flood defences. Disastrous flooding is projected to increase in many regions, particularly in Asia and Africa, owing to climate and socio-economic changes, although substantial uncertainties remain. Assessing the risk of disastrous river floods requires a deeper understanding of their distinct causes. Transdisciplinary research is needed to understand the potential for surprise in flood risk systems better and to operationalize risk management concepts that account for limited knowledge and unexpected developments. River floods have direct and indirect consequences for society, and can cause fatalities, displacement and economic loss. This Review examines the physical and socioeconomic causes and impacts of disastrous river flooding, and past and projected trends in their occurrence.

Urban form and structure explain variability in spatial inequality of property flood risk among US counties - Ma, Junwei; Mostafavi, Ali (Communications Earth & Environment, 2024)
Abstract Understanding the relationship between urban form and structure and spatial inequality of property flood risk has been a longstanding challenge in urban planning and emergency management. Here we explore eight urban form and structure features to explain variability in spatial inequality of property flood risk among 2567 US counties. Using datasets related to human mobility and facility distribution, we identify notable variation in spatial inequality of property flood risk, particularly in coastline and metropolitan counties. The results reveal variations in spatial inequality of property flood risk can be explained based on principal components of development density, economic activity, and centrality and segregation. The classification and regression tree model further demonstrates how these principal components interact and form pathways that explain spatial inequality of property flood risk. The findings underscore the critical role of urban planning in mitigating flood risk inequality, offering valuable insights for crafting integrated strategies as urbanization progresses.

The behavioral turn in flood risk management, its assumptions and potential implications - Kuhlicke, Christian; Seebauer, Sebastian; Hudson, Paul; Begg, Chloe; Bubeck, Philip; Dittmer, Cordula; Grothmann, Torsten; Heidenreich, Anna; Kreibich, Heidi; Lorenz, Daniel F.; Masson, Torsten; Reiter, Jessica; et al. (WIREs Water, 2020)
Abstract Recent policy changes highlight the need for citizens to take adaptive actions to reduce flood‐related impacts. Here, we argue that these changes represent a wider behavioral turn in flood risk management (FRM). The behavioral turn is based on three fundamental assumptions: first, that the motivations of citizens to take adaptive actions can be well understood so that these motivations can be targeted in the practice of FRM; second, that private adaptive measures and actions are effective in reducing flood risk; and third, that individuals have the capacities to implement such measures. We assess the extent to which the assumptions can be supported by empirical evidence. We do this by engaging with three intellectual catchments. We turn to research by psychologists and other behavioral scientists which focus on the sociopsychological factors which influence individual motivations (Assumption 1). We engage with economists, engineers, and quantitative risk analysts who explore the extent to which individuals can reduce flood related impacts by quantifying the effectiveness and efficiency of household‐level adaptive measures (Assumption 2). We converse with human geographers and sociologists who explore the types of capacities households require to adapt to and cope with threatening events (Assumption 3). We believe that an investigation of the behavioral turn is important because if the outlined assumptions do not hold, there is a risk of creating and strengthening inequalities in FRM. Therefore, we outline the current intellectual and empirical knowledge as well as future research needs. Generally, we argue that more collaboration across intellectual catchments is needed, that future research should be more theoretically grounded and become methodologically more rigorous and at the same time focus more explicitly on the normative underpinnings of the behavioral turn. This article is categorized under: Engineering Water > Planning Water Human Water > Water Governance Science of Water > Water Extremes

What determines flood risk perception? A review of factors of flood risk perception and relations between its basic elements - Lechowska, Ewa (Natural Hazards, 2018)
While the methods of risk analysis are generally based on objective measurements, the subjective assessment of risk, such as risk perception, is currently considered a crucial aspect in the context of flood risk management. Risk perception is regarded as an assessment of the perceived probability of hazard and the perceived probability of the results (most often—negative consequences). The work attempts to answer the question: What determines flood risk perception? The knowledge of the factors influencing flood risk perception can solve the issue of the society’s underestimation of flood risk. This issue was considered both in terms of the impact of particular factors on flood risk perception and the interrelationship between three characteristics of flood risk perception: preparedness, worry and awareness. The results were developed based on critical analysis of the empirical research. The review shows that the way particular characteristics determine flood risk perception is not clear and many authors show the diverse conclusions from the similar research. Taking into account various research results, the following factors were distinguished: primary (which clearly influence risk perception), secondary (which influence it unclearly and require further research) and intervening (often describing the context). The organization of the results of the research on the flood risk assessment conducted herein aims to improve the understanding of the human perception of flood risk and, as a result, will lead to the decrease in flood risk by improving the communication of the issue and motivating the residents of the endangered areas to take actions that reduce the negative effects of floods.

Natural and imposed injustices: the challenges in implementing 'fair' flood risk management policy in England - Johnson, Clare L.; Penning-Rowsell, Edmund C.; Parker, Dennis J. (The Geographical Journal, 2007)
This paper examines the challenges facing English flood risk management (FRM) policy and practice when considering fair decision-making processes and outcomes at a range of spatial scales. It is recognised that flooding is not fair per se : the inherent natural spatial inequality of flood frequency and extent, plus the legacy of differential system interventions, being the cause. But, drawing on the three social justice models – procedural equality, Rawls’ maximin rule and maximum utility – the authors examine the fairness principles currently employed in FRM decision-making. This is achieved, firstly, in relation to the distribution of taxpayer’s money for FRM at the national, regional and local levels and, secondly, for non-structural strategies – most notably those of insurance, flood warnings and awareness raising, land use control, home owner adaptation and emergency management. A case study of the Lower Thames catchment illustrates the challenges facing decision-makers in ‘real life’: how those strategies which appear to be most technically and economically effective fall far short of being fair from either a vulnerability or equality perspective. The paper concludes that if we are to manage flood risk somewhat more fairly then a move in the direction of government funding of nationally consistent non-structural strategies, in conjunction with lower investment decision thresholds for other local-level FRM options, appears to offer a greater contribution to equality and vulnerability-based social justice principles than the status quo.

Turkmen women’s traditional craft skills in post-disaster recovery: the case of the 2019 Northeast floods in Iran - Hassani, Atoosa; Fayazi, Mahmood; Mottaki, Zoheir; Adib, Morteza; Dehbandi, Ramin; Khalili Gheidari, Yasamam; Seraji, Fatemeh (Disaster Prevention and Management: An International Journal, 2025)
Purpose This study investigates why Turkmen women’s traditional handicraft skills have declined and explains how the local, traditional craft skills accelerated the post-flood recovery of Turkmen women in the aftermath of the 2019 Northeast floods in Iran. Design/methodology/approach The research adopts a case study approach, employing reflective thematic analysis. Findings Post-disaster recovery spurred a shift from traditional to modern lifestyles through new housing designs, enhanced female literacy and greater economic participation. However, this transition devalued traditional crafts due to heightened household chores, material scarcity and reduced market demand. Nonetheless, women with craft skills played a pivotal role in household recovery by repairing damaged items and crafting dowries for their daughters, illustrating their contribution to social and economic resilience. Social implications These research findings shed light on the importance of traditional craft skills in enabling the female household member, in particular, to recover from disasters and contribute to the recovery of their households and communities. Originality/value The originality of this study lies in its focus on the specific context of Turkmen women’s traditional craft skills and their role in post-disaster recovery, particularly after the 2019 Northeast floods in Iran. While there is existing research on post-disaster recovery mechanisms, this study uniquely examines the under-researched impact of traditional craft skills on the recovery process, specifically for female household members.
Keywords: Infolettre; Infolettre_Fevrier_2025

Fair strategies to tackle unfair risks? Justice considerations within flood risk management - Herve, Mathilde de Goër de (International journal of disaster risk reduction, 2021)
Risk management, justice (i.e. equity, fairness), and sustainability are tightly interconnected. This literature review investigates how and why justice is considered in flood risk management. 20 scientific documents published between 2015 and 2020 are analyzed in depth. The results show a distinction between distributive and procedural justice and a complicated judgment of fairness based on different philosophies that vary depending on the country, the type of flood, and the type of strategy studied. Equity is found to be an under-discussed topic compared to its importance. Justice in flood risk management matters because (i) the impacts of floods affect different people unevenly, (ii) the interest in equity evinced by public authorities influences societal transformation, and (iii) the perception of fairness matters at both individual and collective levels. This paper analyzes the link between justice considerations and sustainability in relation to four dimensions: social, ecological, spatial, and temporal. Social and spatial issues are the most commonly studied in the literature, while ecological and temporal ones have generally been overlooked, creating a research gap. The results are discussed in terms of their diversities of justice concepts, places of investigation, and types of strategies. Various justice frameworks are used, but since none of them focus specifically on the contribution of flood risk management to sustainability through justice considerations, a flood risk justice framework is developed, which translates into theoretical and practical tools. It is based on the considerations of both humans and non-humans into different spatio-temporal scales. • Justice issues are under-discussed while they matter for flood risk management. • Diverse case studies in various places show procedural and distributive (in)justice. • There is no agreement in the literature on how to judge the fairness of a strategy. • The literature is mostly limited to social and spatial justice aspects. • Flood risk justice includes social, ecological, spatial, and temporal issues.

Long-term consequences of flooding: a case study of the 2011 Queensland floods - Fitzgerald, Gerard; Toloo Sheikhzadeh Yazd, Sam; Baniahmadi, Sara; Crompton, David; Tong, Shilu (Australian Journal of Emergency Management, 2019)
Devastating floods in southeast Queensland in 2011 were the combination of flash flooding in the Lockyer Valley with riverine flooding in the Brisbane metropolitan area. While there is considerable information about the immediate impact on those affected, there is less understanding of the long-term health effects that follow such events. This study explored the perceptions of health effects and support received by people affected by the 2011 southeast Queensland flood six years after the event. A cross-sectional survey of 327 people was conducted in areas affected by the floods. The questionnaire sought information about the ongoing social, economic, demographic and self-declared physical and mental health effects. The data were analysed through comparison of those unaffected with those directly affected by the floods. Residents whose households were flooded were more likely to score their health negatively than non-affected residents and had higher reported rates of trauma, injury and mental illness. Twenty-six per cent of this group reported that they still experience some adverse health effects from the floods. Managing the long-term health implications of a flood-affected population is an important public policy task. Dissatisfaction with recovery operations and perceived injustices associated with insurance and compensation arrangements may aggravate health consequences. Early recognition and intervention may assist with reducing secondary effects.
Keywords: Ouvrage_Collectif_Numéro1

Flooding Related Consequences of Climate Change on Canadian Cities and Flow Regulation Infrastructure - Gaur, Ayushi; Gaur, Abhishek; Yamazaki, Dai; Simonovic, Slobodan P. (Water, 2019)
This study discusses the flooding related consequences of climate change on most populous Canadian cities and flow regulation infrastructure (FRI). The discussion is based on the aggregated results of historical and projected future flooding frequencies and flood timing as generated by Canada-wide hydrodynamic modelling in a previous study. Impact assessment on 100 most populous Canadian cities indicate that future flooding frequencies in some of the most populous cities such as Toronto and Montreal can be expected to increase from 100 (250) years to 15 (22) years by the end of the 21st century making these cities highest at risk to projected changes in flooding frequencies as a consequence of climate change. Overall 40–60% of the analyzed cities are found to be associated with future increases in flooding frequencies and associated increases in flood hazard and flood risk. The flooding related impacts of climate change on 1072 FRIs located across Canada are assessed both in terms of projected changes in future flooding frequencies and changes in flood timings. Results suggest that 40–50% of the FRIs especially those located in southern Ontario, western coastal regions, and northern regions of Canada can be expected to experience future increases in flooding frequencies. FRIs located in many of these regions are also projected to experience future changes in flood timing underlining that operating rules for those FRIs may need to be reassessed to make them resilient to changing climate.

Efficient or Fair? Operationalizing Ethical Principles in Flood Risk Management: A Case Study on the Dutch‐German Rhine - Ciullo, Alessio; Kwakkel, Jan H.; De Bruijn, Karin M.; Doorn, Neelke; Klijn, Frans (Risk Analysis, 2020)
Abstract Flood risk management decisions in many countries are based on decision‐support frameworks which rely on cost‐benefit analyses. Such frameworks are seldom informative about the geographical distribution of risk, raising questions on the fairness of the proposed policies. In the present work, we propose a new decision criterion that accounts for the distribution of risk reduction and apply it to support flood risk management decisions on a transboundary stretch of the Rhine River. Three types of interventions are considered: embankment heightening, making Room for the River, and changing the discharge distribution of the river branches. The analysis involves solving a flood risk management problem according to four alternative formulations, based on different ethical principles. Formulations based on cost optimization lead to very poor performances in some areas for the sake of reducing the overall aggregated costs. Formulations that also include equity criteria have different results depending on how these are defined. When risk reduction is distributed equally, very poor economic performance is achieved. When risk is distributed equally, results are in line with formulations based on cost optimization, while a fairer risk distribution is achieved. Risk reduction measures also differ, with the cost optimization approach strongly favoring the leverage of changing the discharge distribution and the alternative formulations spending more on embankment heightening and Room for the River, to rebalance inequalities in risk levels. The proposed method advances risk‐based decision‐making by allowing to consider risk distribution aspects and their impacts on the choice of risk reduction measures.

Exploring the Environmental Justice Implications of Hurricane Harvey Flooding in Greater Houston, Texas. - Chakraborty, Jayajit; Collins, Timothy W.; Grineski, Sara E. (American Journal of Public Health, 2019)
Objectives. To assess the environmental justice implications of flooding from Hurricane Harvey in Greater Houston, Texas, we analyzed whether the areal extent of flooding was distributed inequitably with respect to race, ethnicity, and socioeconomic status, after controlling for relevant explanatory factors.Methods. Our study integrated cartographic information from Harvey’s Inundation Footprint, developed by the US Federal Emergency Management Agency, with sociodemographic data from the 2012–2016 American Community Survey. Statistical analyses were based on bivariate correlations and multivariate generalized estimating equations.Results. The areal extent of Harvey-induced flooding was significantly greater in neighborhoods with a higher proportion of non-Hispanic Black and socioeconomically deprived residents after we controlled for contextual factors and clustering.Conclusions. Results provide evidence of racial/ethnic and socioeconomic injustices in the distribution of flooding and represent an importa...

Comparative analysis of local and large-scale approaches to floodplain mapping: a case study of the Chaudière River - Bessar, M. A.; Choné, G.; Lavoie, A.; Buffin-Bélanger, T.; Biron, P. M.; Matte, P.; Anctil, F. (Canadian Water Resources Journal / Revue canadienne des ressources hydriques, 2021)
Floods are among natural disasters that increasingly threaten society, especially with current and future climate change trends. Several tools have been developed to help planners manage the risks associated to flooding, including the mapping of flood-prone areas, but one of the major challenges is still the availability of detailed data, particularly bathymetry. This manuscript compares two modeling approaches to produce flood maps. An innovative large-scale approach that, without bathymetric data, estimates by inverse modeling the bed section for a given flow and a given roughness coefficient through 1 D/2D hydraulic modeling (LISFLOOD-FP). And a local approach, with a detailed coupled 1 D/2D hydraulic model (HEC-RAS) that uses all available information at the bed and floodplain (LiDAR and bathymetry). Both implementations revealed good performance values for flood peak levels as well as excellent fit indices in describing the areal extent of flooding. As expected, the local approach is more accurate, but the results of the large-scale approach are very promising especially for areas lacking bathymetric data and for large-scale governmental programs.

Sensibilisation au risque d’inondation par une séquence d’enseignement en probabilités - Thibault, Mathieu (2024)
Je fais partie d’une équipe interdisciplinaire d’un projet de recherche subventionné qui vise à sensibiliser les élèves du premier cycle du secondaire (12-14 ans) au risque d’inondation. Avec une didacticienne de la géographie, deux personnes didacticiennes des sciences et technologie et deux spécialistes de l’hydrologie et de l’hydraulique, nous avons fait ressortir des points d’ancrage à prendre en compte pour concevoir une séquence didactique interdisciplinaire (en mathématiques, sciences et technologie, univers social) sur ce sujet. Ce projet s’inscrit dans une approche de recherche- développement (Bergeron et Rousseau, 2021), ayant une double finalité de développement (concevoir un produit en réponse aux besoins du milieu de pratique) et de recherche (contribuer à l’avancement des connaissances scientifiques). Cet article présente : 1. Des informations sur les inondations ainsi que les concepts associés (aléa, exposition, vulnérabilité et risque) ; 2. Une analyse des programmes de formation de l’école québécoise (PFEQ) en mathématiques au secondaire (Gouvernement du Québec, 2006, 2016a) et de la progression des apprentissages (PDA) au primaire (Gouvernement du Québec, 2009) et au secondaire (Gouvernement du Québec, 2016b) au sujet du risque d’inondation ; 3. Les grandes lignes d’une séquence d’enseignement en probabilités visant à sensibiliser les élèves du premier cycle du secondaire au risque d’inondation.
Keywords: Infolettre; Infolettre_Mai_2024; Site_internet_RIISQ

La portée et les limites des approches participatives pour la gestion intégrée des inondations - Massé, Simon; Buffin-Bélanger, Thomas; Biron, Pascale; Ruiz, Julie (Revue des sciences de l’eau, 2019)
La gestion intégrée des risques d’inondation (GIRI) fait appel à la coordination de tous les niveaux et secteurs du gouvernement et de la société civile. Afin de favoriser la responsabilisation et l’appropriation des plans de GIRI par les communautés, l’implication des acteurs non gouvernementaux et des citoyens est de plus en plus valorisée. D’abord, l’émergence des approches participatives est exacerbée par l’optimisme face à la possibilité d’améliorer substantiellement la qualité et la portée des décisions, de gérer les conflits, de faciliter l'implantation des mesures non structurelles et de renforcer les capacités sociales au sein des communautés. Toutefois, certains avancent que l'intégration des non-experts dans le processus décisionnel brime l'impartialité de la procédure technocratique et que leur manque d’intérêt et de compétences limite la portée des démarches participatives. Des lacunes dans la représentativité des parties prenantes affectées et concernées au sein des instances peuvent aussi biaiser les aboutissants de la participation. De plus, la réticence des autorités à partager le pouvoir décisionnel limite l’institutionnalisation des approches participatives, tandis que la rigidité de l’appareil gouvernemental freine les élans participatifs des collectivités. Considérant l’intérêt grandissant des chercheurs, des décideurs et de la société civile envers les approches participatives dans le contexte de la gestion des inondations, cet article propose une synthèse de la littérature pour démêler les principales retombées et les limites de la participation. , In order to promote community accountability for flood risks, the involvement of non-governmental actors and citizens is increasingly valued. The emergence of participatory approaches is consolidated by optimism about the possibility of improving the quality and scope of decisions, managing conflicts, facilitating the implementation of non-structural measures and strengthening social capacity within communities. However, some argue that the integration of non-experts undermines the impartiality of the decision-making process and that their lack of interest and expertise limits the scope of participatory approaches. Moreover, the authorities’ reluctance to share decision-making power limits the institutionalization of participatory approaches, whereas the rigidity of the governmental framework hampers participatory impulses within communities. Lack of stakeholder representativeness within the decision-making framework may also bias the outcome of participation. In addition, the reluctance of the authorities to share decision-making power limits the institutionalization of participatory approaches, while the rigidity of the government apparatus hinders the participatory momentum of communities. Considering the growing interest of researchers, policymakers and civil society in participatory approaches in the context of flood management, this article provides a synthesis of the literature to unravel the major benefits and limitations of participation.
Keywords: Ouvrage_Collectif_Numéro1

Défis de l’action intersectorielle et pistes de réflexion pour renforcer la concertation dans les milieux ruraux du Québec en contexte de pandémie - Richard, Julie; Bergeron, Dave A.; Lessard, Lily; Toupin, Isabelle; Ouellet, Nicole; Bédard, Emmanuelle (Global Health Promotion, 2021)
La présente pandémie nécessite le recours aux mécanismes qui favorisent l’action intersectorielle entre les autorités et les partenaires de différents secteurs de la santé et de la société civile pour coordonner et adapter la réponse socio-sanitaire en fonction des particularités des milieux et de l’évolution de la pandémie. Ce commentaire propose de mettre en lumière quelques défis qui se posent actuellement dans la mise en œuvre d’actions intersectorielles dans les milieux ruraux du Québec. Des pistes de réflexion en faveur du renforcement des mécanismes de concertation nécessaires à la gestion de la pandémie sont proposées.
Keywords: Lessard_Lily

Les stratégies d’intervention déployées lors des inondations de 2019 : le point de vue d’intervenants de première et de deuxième lignes sur les avenues prometteuses - Maltais, Danielle; Lansard, Anne-Lise; Généreux, Mélissa (2021)
Au printemps 2017 et 2019, plus 300 municipalités du Québec ont été confrontées à de graves inondations qui ont provoqué d’importants dommages aux propriétés, aux biens personnels de milliers de citoyens et à plusieurs infrastructures municipales. Dans le contexte des inondations de 2019, il faut toutefois souligner l’importante différence entre celles vécues par la municipalité de Sainte-Marthe-sur-le-Lac et celles survenues dans les autres municipalités du Québec. À Sainte-Marthe-sur-le-Lac, les inondations ont été soudaines, et rapides, car elles ont été provoquées par la rupture d’une digue. Ce sinistre, de nature anthropique, a occasionné la relocalisation d’urgence de plusieurs centaines de familles. Quant aux autres municipalités, c’est la crue printanière qui a généré des inondations fluviales, un sinistre de cause naturelle, dont l’ampleur et la durée ont dépassé les précédents évènements historiques, y compris ceux de 2017. Lors de ces inondations, les municipalités et divers partenaires gouvernementaux (CIUSSS/CISSS, MSP, SQ…) et certains organismes bénévoles en sécurité civile (Croix-Rouge Canadienne, Armée du Salut, Ambulance St-Jean, etc.), ont déployé leurs intervenants afin d’apporter leur aide et leur soutien aux municipalités et aux personnes sinistrées. Des centaines de policiers, pompiers, employés municipaux, gestionnaires, chefs d’équipe, militaires, intervenants psychosociaux, bénévoles spécialisés en recherche et sauvetage ou en soutien émotionnel ont alors travaillé sans relâche pour assurer la sécurité des personnes et des biens, mais pour aussi amortir, autant que possible, les impacts psychosociaux inévitablement causés par ce type de sinistre. Ce rapport synthèse présente le point de vue d’une centaine d’intervenants, provenant de différentes régions du Québec qui ont contribué à la gestion et la coordination des efforts pour orchestrer la réponse nécessaire lors des inondations de 2019. Ils ont été invités à documenter les stratégies mises en place à court et à moyen terme qui, selon leurs observations, ont contribué à : •Augmenter le sentiment de sécurité des sinistrés ; •Diminuer leur niveau d’anxiété et d’isolement ; et •Prévenir la détérioration de leur état de santé physique et psychologique.
Keywords: Généreux_Mélissa

Applicabilité du concept d’espace de liberté dans les pratiques de gestion des cours d’eau et des plaines inondables au Québec - Massé, Simon; Buffin-Belanger, Thomas; Biron, Pascale; Ruiz, Julie (Les inondations au Québec : risques, aménagement du territoire, impacts socioéconomiques et transformation des vulnérabilités, 2022)
Keywords: Chapitre_Ouvrage_Collectif_Numero1

The 2023 wildfire season in Québec: an overview of extreme conditions, impacts, lessons learned and considerations for the future - Boulanger, Yan; Arseneault, Dominique; Bélisle, Annie Claude; Bergeron, Yves; Boucher, Jonathan; Boucher, Yan; Danneyrolles, Victor; Erni, Sandy; Gachon, Philippe; Girardin, Martin P.; Grant, Eliane; Grondin, Pierre; et al. (Canadian Journal of Forest Research, 2024)
The 2023 wildfire season in Québec set records due to extreme warm and dry conditions, burning 4.5 million hectares and indicating persistent and escalating impacts associated with climate change. This study reviews the unusual weather conditions that led to the fires, discussing their extensive impacts on the forest sector, fire management, boreal caribou habitats, and particularly the profound effects on First Nation communities. The wildfires led to significant declines in forest productivity and timber supply, overwhelming fire management resources, and necessitating widespread evacuations. First Nation territories were dramatically altered, facing severe air quality issues and disruptions. While caribou impacts were modest across the province, the broader ecological, economical, and social repercussions were considerable. To mitigate future extreme wildfire seasons, the study suggests changes in forest management practices to increase forest resilience and resistance, adapting industrial structures to changes in wood type harvested, and enhancing fire suppression and risk management strategies. It calls for a comprehensive, unified approach to risk management that incorporates the lessons learned from the 2023 fire season and accounts for ongoing climate change. The studyunderscores the urgent need for detailed planning and proactive measures to reduce the growing risks and impacts of wildfires in a changing climate.
Keywords: Gachon_Philippe; Guillemette_Francois

Soil Erosion in the United States. Present and Future (2020-2050) - Shojaeezadeh, Shahab Aldin; Al-Wardy, Malik; Nikoo, Mohammad Reza; Mooselu, Mehrdad Ghorbani; Alizadeh, Mohammad Reza; Adamowski, Jan Franklin; Moradkhani, Hamid; Alamdari, Nasrin; Gandomi, Amir H. (2022)
Soil erosion is a significant threat to the environment and long-term land management around the world. Accelerated soil erosion by human activities inflicts extreme changes in terrestrial and aquatic ecosystems, which is not fully surveyed/predicted for the present and probable future at field-scales (30-m). Here, we estimate/predict soil erosion rates by water erosion, (sheet and rill erosion), using three alternative (2.6, 4.5, and 8.5) Shared Socioeconomic Pathway and Representative Concentration Pathway (SSP-RCP) scenarios across the contiguous United States. Field Scale Soil Erosion Model (FSSLM) estimations rely on a high resolution (30-m) G2 erosion model integrated by satellite- and imagery-based estimations of land use and land cover (LULC), gauge observations of long-term precipitation, and scenarios of the Coupled Model Intercomparison Project Phase 6 (CMIP6). The baseline model (2020) estimates soil erosion rates of 2.32 Mg ha 1 yr 1 with current agricultural conservation practices (CPs). Future scenarios with current CPs indicate an increase between 8% to 21% under different combinations of SSP-RCP scenarios of climate and LULC changes. The soil erosion forecast for 2050 suggests that all the climate and LULC scenarios indicate either an increase in extreme events or a change in the spatial location of extremes largely from the southern to the eastern and northeastern regions of the United States.
Keywords: Infolettre; Infolettre_Ete_2024

Supply and Transport Limitations on Phosphorus Losses from Agricultural Fields in the Lower Great Lakes Region, Canada - Plach, Janina M.; Macrae, Merrin L.; Ali, Genevieve A.; Brunke, Richard R.; English, Michael C.; Ferguson, Gabrielle; Lam, W. Vito; Lozier, Tatianna M.; McKague, Kevin; O'Halloran, Ivan P.; Opolko, Gilian; Van Esbroeck, Christopher J. (Journal of Environmental Quality, 2018)
Phosphorus (P) mobilization in agricultural landscapes is regulated by both hydrologic (transport) and biogeochemical (supply) processes interacting within soils; however, the dominance of these controls can vary spatially and temporally. In this study, we analyzed a 5‐yr dataset of stormflow events across nine agricultural fields in the lower Great Lakes region of Ontario, Canada, to determine if edge‐of‐field surface runoff and tile drainage losses (total and dissolved reactive P) were limited by transport mechanisms or P supply. Field sites ranged from clay loam, silt loam, to sandy loam textures. Findings indicate that biogeochemical processes (P supply) were more important for tile drain P loading patterns (i.e., variable flow‐weighted mean concentrations ([ C f ]) across a range of flow regimes) relative to surface runoff, which trended toward a more chemostatic or transport‐limited response. At two sites with the same soil texture, higher tile [ C f ] and greater transport limitations were apparent at the site with higher soil available P (STP); however, STP did not significantly correlate with tile [ C f ] or P loading patterns across the nine sites. This may reflect that the fields were all within a narrow STP range and were not elevated in STP concentrations (Olsen‐P, ≤25 mg kg −1 ). For the study sites where STP was maintained at reasonable concentrations, hydrology was less of a driving factor for tile P loadings, and thus management strategies that limit P supply may be an effective way to reduce P losses from fields (e.g., timing of fertilizer application). Core Ideas We used metrics to evaluate controls on edge‐of‐field phosphorus losses. We examined a 5‐yr database of stormflow events (all seasons, including winter). Tile P runoff trended toward being more supply limited than surface runoff.

Changes in floodplain regimes over Canada due to climate change impacts: Observations from CMIP6 models - Mohanty, Mohit Prakash; Simonovic, Slobodan P. (Science of The Total Environment, 2021)
Abstract With the recent Coupled Model Intercomparison Project Phase 6 (CMIP6), water experts and flood modellers are curious to explore the efficacy of the new and upgraded climate models in representing flood inundation dynamics and how they will be impacted in the future by climate change. In this study, for the first time, we consider the latest group of General Circulation Models (GCMs) from CMIP6 to examine the probable changes in floodplain regimes over Canada. A set of 17 GCMs from Shared Socioeconomic Pathways (SSPs) 4.5 (medium forcing) and 8.5 (high end forcing) common to historical (1980 to 2019), near-future (2021 to 2060), and far-future (2061 to 2100) time-periods are selected. A comprehensive framework consisting of hydrodynamic flood modelling, and statistical experiments are put forward to derive high-resolution Canada-wide floodplain maps for 100 and 200-yr return periods. The changes in floodplain regimes for the future periods are analyzed over drainage basin scale in terms of (i) changes in flood inundation extents, (ii) changes in flood hazards (high and very-high classes), and (iii) changes in flood frequency. Our results show a significant rise (>30%) in flood inundation extents in the future periods; particularly intense over western and eastern regions. The flood hazards are expected to cover ~16% more geographical area of Canada. We also find that large areas in northern and western Canada and a few spots in the eastern parts of Canada will be getting flooded more frequently compared to the historical period. The observations derived from this study are vital for enhancing flood preparedness, optimal land-use planning, and refurbishing both structural and non-structural flood control options for improved resilience. The study instills new knowledge on revamping the existing flood management approaches and adaptation strategies for future protection.

A Comprehensive Approach for Floodplain Mapping Through Identification of Hazard Using Publicly Available Data Sets Over Canada - Mohanty, M.P.P; Simonovic, Slobodan P. (2022)
Flood events and their associated damages have escalated significantly in the last few decades. To add to the gruesome situation, many reports and studies warn that flood risk would aggravate significantly in future periods due to significant alterations in the climate patterns and socio-economic dynamics. Floodplain mapping is looked upon as a viable option to tackle this global issue as it provides both quantitative and qualitative information on flood dynamics. Moreover, with the increasing availability of global data and enhancement in computational simulations, it has become easier to simlate flooding patterns at large scales. This study deter-mines the usability of publicly available datasets in capturing flood hazards over Canada. Run-off data set from the North American Regional Reanalysis (NARR), along with a few other rele-vant inputs are fed to CaMa-Flood, a robust global hydrodynamic model to generate flooding patterns for 1 in 100 and 1 in 200-yr return period events over Canada . The simulated maps are compared and validated with the existing maps of a few flood-prone regions in Canada, thereby establishing their performance over both regional and country-scale. Later, the simulated flood-plain maps are used in conjunction with property related information at 34 cities (within the top 100 populous cities in Canada) to determine the degree of exposure due to flooding in 1991, 2001, and 2011. The results indicate that around 80 percent of inundated spots belong to high and very-high hazard classes in a 200-yr event, which is roughly 4 percent more than simulated for 100-yr event. NARR derived floodplain maps perform very well while compared over the six flood-prone regions. While analyzing the exposure of properties to flooding, we notice an in-crease in the number during the last three decades, with the maximum rise observed in Toronto, followed by Montreal, and Edmonton. To disseminate the extensive flood-related information, a web-based public tool, Flood Map Viewer (http://www.floodmapviewer.com/) is developed. The development of the tool was motivated by the commitment of the Canadian government to provide $63 M over the next three years for the completion of flood maps for higher-risk areas. The study reaches out to demonstrate how publicly available datasets can be utilized with a lesser degree of uncertainty in representing flooding patterns over large regions. The flood re-lated information derived from the study can be used along with vulnerability for quantifying flood risk, which will help in developing appropriate pathways for resilience building for long-term sustainable benefits.

Will Evolving Climate Conditions Increase the Risk of Floods of the Large U.S.‐Canada Transboundary Richelieu River Basin? - Lucas‐Picher, Philippe; Lachance‐Cloutier, Simon; Arsenault, Richard; Poulin, Annie; Ricard, Simon; Turcotte, Richard; Brissette, François (JAWRA Journal of the American Water Resources Association, 2021)
Abstract In spring 2011, an unprecedented flood hit the complex eastern United States (U.S.)–Canada transboundary Lake Champlain–Richelieu River (LCRR) Basin, destructing properties and inducing negative impacts on agriculture and fish habitats. The damages, covered by the Governments of Canada and the U.S., were estimated to C$90M. This natural disaster motivated the study of mitigation measures to prevent such disasters from reoccurring. When evaluating flood risks, long‐term evolving climate change should be taken into account to adopt mitigation measures that will remain relevant in the future. To assess the impacts of climate change on flood risks of the LCRR basin, three bias‐corrected multi‐resolution ensembles of climate projections for two greenhouse gas concentration scenarios were used to force a state‐of‐the‐art, high‐resolution, distributed hydrological model. The analysis of the hydrological simulations indicates that the 20‐year return period flood (corresponding to a medium flood) should decrease between 8% and 35% for the end of the 21st Century (2070–2099) time horizon and for the high‐emission scenario representative concentration pathway (RCP) 8.5. The reduction in flood risks is explained by a decrease in snow accumulation and an increase in evapotranspiration expected with the future warming of the region. Nevertheless, due to the large climate inter‐annual variability, short‐term flood probabilities should remain similar to those experienced in the recent past.

Mechanisms of spring freshet generation in southern Quebec, Canada - Kinnard, Christophe; Nemri, Saida; Assani, Ali (2023)
Seasonal forecasting of spring floods in snow-covered basins is challenging due to the ambiguity in the driving processes, uncertain estimations of antecedent catchment conditions and the choice of predictor variables. In this study we attempt to improve the prediction of spring flow peaks in southern Quebec, Canada, by studying the preconditioning mechanisms of runoff generation and their impact on inter-annual variations in the timing and magnitude of spring peak flow. Historical observations and simulated data from a hydrological and snowmelt model were used to study the antecedent conditions that control flood characteristics in twelve snow-dominated catchments. Maximum snow accumulation (peak SWE), snowmelt and rainfall volume, snowmelt and rainfall intensity, and soil moisture were estimated during the pre-flood period. Stepwise multivariate linear regression analysis was used to identify the most relevant predictors and assess their relative contribution to the interannual variability of flood characteristics. Results show that interannual variations in spring peak flow are controlled differently between basins. Overall, interannual variations in peak flow were mainly governed, in order of importance, by snowmelt intensity, rainfall intensity, snowmelt volume, rainfall volume, peak SWE, and soil moisture. Variations in the timing of peak flow were controlled in most basins by rainfall volume and rainfall and snowmelt intensity. In the northernmost, snow-dominated basins, pre-flood rainfall amount and intensity mostly controlled peak flow variability, whereas in the southern, rainier basins snowpack conditions and melt dynamics controlled this variability. Snowpack interannual variations were found to be less important than variations in rainfall in forested basins, where snowmelt is more gradual. Conversely, peak flow was more sensitive to snowpack conditions in agricultural basins where snowmelt occurs faster. These results highlight the impact of land cover and use on spring flood generation mechanism, and the limited predictability potential of spring floods using simple methods and antecedent hydrological factors.
Keywords: Infolettre; Infolettre_Fevrier_2025; Kinnard_Christophe

Using the theory of planned behavior to identify key beliefs underlying flood-related adaptive behaviors in the province of Québec, Canada - Jacob, Johann; Valois, Pierre; Tessier, Maxime; Talbot, Denis; Anctil, François; Cloutier, Geneviève; Renaud, Jean-Sébastien (Journal of Flood Risk Management, 2023)
Given that flooding episodes are occurring at a greater rate due to climate change, individuals must adopt certain adaptation behaviors to prevent or mitigate the anticipated or negative impact of such events. However, few studies have assessed if and how households and individuals have actually taken action in this regard. Because some individual beliefs can be linked to facilitating factors and barriers to action, a better understanding of the adoption of adaptive behaviors requires a combined analysis of individual psychosocial factors. The purpose of this study was to develop a better understanding of the reasons underlying the adoption of behaviors related to structural adaptation to flooding by people living in or near flood-prone areas in the Province of Québec (Canada). Results of a series of structural equation modeling showed that behavioral, normative and control beliefs were all significant predictors of the respondents' intention to adopt structural flood protective behaviors, with normative beliefs being the strongest. By identifying the best psychosocial predictors of the adoption of such behaviors, the results of this study provide valuable insights regarding the most effective factors to be used in public health messages to promote the adoption of behaviors related to structural adaptation to flooding.
Keywords: Infolettre; Infolettre_Mai_2023

Topography- and nightlight-based national flood risk assessment in Canada - Elshorbagy, Amin; Bharath, R.; Lakhanpal, Anchit; Ceola, Serena; Montanari, Alberto; Lindenschmidt, Karl-Erich (Hydrology and Earth System Sciences, 2016)
In Canada, flood analysis and water resource management, in general, are tasks conducted at the provincial level; therefore, unified national-scale approaches to water-related problems are uncommon. In this study, a national-scale flood risk assessment approach is proposed and developed. The study focuses on using global and national datasets available with various resolutions to create flood risk maps. First, a flood hazard map of Canada is developed using topography-based parameters derived from digital elevation models, namely, elevation above nearest drainage (EAND) and distance from nearest drainage (DFND). This flood hazard mapping method is tested on a smaller area around the city of Calgary, Alberta, against a flood inundation map produced by the city using hydraulic modelling. Second, a flood exposure map of Canada is developed using a land-use map and the satellite-based nightlight luminosity data as two exposure parameters. Third, an economic flood risk map is produced, and subsequently overlaid with population density information to produce a socioeconomic flood risk map for Canada. All three maps of hazard, exposure, and risk are classified into five classes, ranging from very low to severe. A simple way to include flood protection measures in hazard estimation is also demonstrated using the example of the city of Winnipeg, Manitoba. This could be done for the entire country if information on flood protection across Canada were available. The evaluation of the flood hazard map shows that the topography-based method adopted in this study is both practical and reliable for large-scale analysis. Sensitivity analysis regarding the resolution of the digital elevation model is needed to identify the resolution that is fine enough for reliable hazard mapping, but coarse enough for computational tractability. The nightlight data are found to be useful for exposure and risk mapping in Canada; however, uncertainty analysis should be conducted to investigate the effect of the overglow phenomenon on flood risk mapping.

La réduction des risques de désastres : défis et possibilités pour le Québec et le Canada. Université du Québec à Montréal, Chaire de recherche UQAM sur les risques hydrométéorologiques liés aux changements climatiques - Boyer-Villemaire, U.; Gachon, P.; Boucher, E.; Germain, D.; Raphoz, M.; Doré, M. C.; Martin, J. P. (2017)
En marge de la Cinquième Plateforme régionale pour la Réduction des risques de catastrophes des Amériques (PRA), le gouvernement du Canada a approché l’Institut des sciences de l’environnement(ISE) de l’Université du Québec à Montréal(UQAM) afin d’organiser un forum public. Les échanges de ce dernier devaient servir à alimenter les discussions de la PRA. Au total, 21 experts ont discuté avec une centaine de participants lors de panels organisés à l’UQAM sous les thèmes de la santé, de la sécurité civile et de l’aménagement du territoire. Plusieurs thèmes transversaux ont aussi émergé tout au long du forum. Il importe de pérenniser le rôle de la recherche et d’améliorer les capacités de formation technique et universitaire afin de former des spécialistes en mesure d’appréhender la complexité de la gestion du risque dans un contexte de changements environnementaux et climatiques. Ceci est également essentiel pour l’identification des facteurs de risque (multisources ou multidimensionnels), pour tirer des leçons apprises des événements majeurs passés et récents, et pour développer ou mettre à jour la connaissance sur les tendances en cours et à venir des aléas météorologiques, ainsi que des facteurs de vulnérabilité et d’exposition. Tous les panels ont discuté de l’importance de favoriser le décloisonnement intra/interorganisationnel pour promouvoir la transsectorialité et les retours d’expériences systématiques. Pour ce faire, il faut s’inspirer des modèles internationaux, notamment du système d’alertes hydrométéorologiques présenté par Météo-France. Celui-ci inclut une vigilance météorologique qui cible des populations et des autorités publiques, et les informe des comportements et des règles à suivre lors d’alertes plus problématiques (vigilance aux stades orange et rouge). Finalement, l’amélioration de la communication et le libre accès à l’information sont des éléments essentiels pour protéger les individus et développer une société plus résiliente.
Keywords: Gachon_Philippe

Spatiotemporal variability of fall daily maximum flows in southern Quebec (Canada) from 1930 to 2018 - Assani, Ali A. (Journal of Flood Risk Management, 2024)
Abstract Quebec is experiencing a significant increase in summer and fall temperatures and rainfall. This study compares the spatiotemporal variability of maximum daily flows generated by rainfall during the fall season (September–December) in relation to this climatic change and physiographic and land use factors. Analysis of the spatial variability of these maximum flows measured from 1930 to 2018 in 17 watersheds revealed that the magnitude of flows is approximately twice as low on the north shore as it is on the south shore south of 47° N. This difference is explained by three main factors: wetlands (negative correlation) and agricultural (positive correlation) surface area, and summer–fall total precipitation (positive correlation). As for the temporal variability of flows, the different Mann–Kendall statistical tests showed a significant increase in flows due to increased rainfall. The increase of flows was more widespread on the north shore than on the south because the storage capacity of wetlands and other water bodies does not change over time to store excess rainfall. On the south shore, the increase in flows over time is limited due to the significant reduction in agricultural areas since the modernization of agriculture. This reduction favored infiltration to the detriment of runoff.
Keywords: Infolettre; Infolettre_Septembre_2024; Site_internet_RIISQ

Outils de gestion intégrée des risques pour les municipalités basés sur l’approche par conséquences - Robert, Benoît; Hémond, Yannick (Les inondations au Québec : risques, aménagement du territoire, impacts socioéconomiques et transformation des vulnérabilités, 2022)
Keywords: Chapitre_Ouvrage_Collectif_Numero1; Hémond_Yannick

Adaptation des outils PHYSITEL/HYDROTEL au milieu boréal québécois : modélisation des processus hydrologiques et analyses de sensibilité et d’incertitudes. - Rousseau, Alain N.; Rousseau, A.N.; Mailhot, Alain; St-Hilaire, André (2015)
Les bassins versants du Moyen‐Nord quebecois (49e au 55e parallele) se distinguent par leur climatologie et le pourcentage eleve de territoires couverts par des lacs et milieux humides (de l’ordre de 20 a 30 %) et, surtout, par leur importante contribution a la production electrique du Quebec; le complexe de la riviere La Grande generant environ 40% de l’electricite quebecoise. Dans le contexte de la gestion de la production d’electricite, Hydro‐Quebec Production fait la prevision des apports aux reservoirs de ce complexe a l’aide d’un modele hydrologique global. Par ailleurs, depuis les annees 1980, le milieu boreal quebecois a subi des hausses de temperature et de precipitation qui ont modifie le regime des apports aux reservoirs. Compte tenu de ces changements et des caracteristiques physiographiques des bassins boreaux, il a ete propose d’utiliser un modele hydrologique distribue a base physique pour examiner l’impact sur ces apports des projections climatiques produites par Ouranos. En l’occurrence le modele HYDROTEL dont la prise en mains est en train d’etre completee par Hydro‐Quebec Production. Le modele qui est maintenant convenablement cale pour un certain nombre de bassins repond aux attentes dans les bassins du sud du Quebec. Toutefois, pour les grands bassins du Nord comme ceux du Complexe La Grande, l’utilisation du modele requiert des travaux d’adaptations, entre autres, aux niveaux de la modelisation des milieux humides et de la desagregation spatiale des precipitations simulees par les modeles climatiques. Les objectifs generaux de ce projet etaient d’accroitre notre comprehension de l’hydrologie du moyen nord afin qu’elle soit bien representee dans HYDROTEL tout en tenant compte des incertitudes parametriques associees aux differentes equations gouvernant les processus physiques. Ces objectives ont ete declines en trois activites de travail : (AT1) modelisation des processus hydrologiques; (AT2) calage et analyses de sensibilite, d’identifiabilite et d’incertitudes des parametres de calage d’HYDROTEL; et (AT3) amelioration des plateformes informatiques HYDROTEL et PHYSITEL, ce dernier etant un SIG dedie a la construction des bases de donnees de modeles hydrologiques distribues. Pour Ouranos et Hydro‐Quebec les principales realisations issues de ce projet incluent : (i) le developpement d’une methode eprouvee de desagregation sous grille de la precipitation mesoechelle permettant d’evaluer a fine echelle spatiale l’impact des changements climatiques sur les precipitations; (ii) une meilleure comprehension de la dynamique des ecoulements, du stockage de l’eau et de l’evapotranspiration d’un petit bassin versant boreal incluant une grande une tourbiere minerotrophe aqualysee; (iii) l’evaluation du parametrage de la sublimation et la relocalisation de la neige dues au vent et l’identification du besoin d’inclure le rayonnement sous la canopee pour bien reproduire la crue avec un modele complexe de l'evolution du couvert nival; (iv) la detection de la quasi neutralite frequente (~76% du temps, majoritairement le jour) de l’atmosphere au‐dessus d’un milieu humide causee par une turbulence mecanique forte et une grande inertie thermique; conditions ayant permises le developpement d’un modele simple d’evapotranspiration des milieux humides base le transfert massique et la stabilite atmospherique; (v) le developpement d’un modele de rayonnement net base uniquement sur des donnees de temperatures journalieres (min, max) et une estimation des parametres permettant de valider l’utilisation de l’equation de Penman‐Monteith dans le nord quebecois; (vi) la hierarchisation des parametres de calage d’HYDROTEL selon la saison et le developpement d’une methode permettant d’evaluer l’incertitude sur les debits simules et d’identifier son importance durant la fonte et l’etiage estival; (vii) dans un contexte d’analyse frequentielle des debits simules, evaluation de l’incertitude parametrique par rapport a l’incertitude statistique, cette derniere dominant pour les periodes de retour superieures a cinq ans; (viii) a l’aide de PHYSITEL, la premiere discretisation du complexe de la riviere La Grande (136 648 km2) en six sousbassins (LG1, LG2, LG3, LG4, La Forge 1 & 2,et Caniapiscau) leur subdivision en versants permettant le calcul de crues maximales probables a l’aide d’HYDROTEL; et (ix) le developpement d’une version 64 bits d’HYDROTEL incluant de nouveaux modules de de calculs de la temperature du sol et des bilans hydriques des milieux humides et isoles. L'avancement de nos comprehensions de l'hydrologie des milieux humides et du milieu boreal en general a ete a la base du developpement des versions adaptees d'HYDROTEL et de PHYSITEL qui permettront a Hydro‐Quebec d'apprehender, avec une modelisation distribuee, l'impact des changements climatiques sur le complexe de la riviere La Grande. Ces logiciels sont transposables a l’ensemble du milieu boreal canadien. Une entente conclut, depuis 2005, entre l’INRS et Hydro‐Quebec (HQ) permet d’ailleurs une distribution commerciale des differentes versions d’HYDROTEL avec interfaces usagers de meme qu’une distribution communautaire du noyau de calcul. Cette synergie a permis de mettre en commun des ressources et des expertises qui facilitent les echanges scientifiques et techniques entre les concepteurs d’HYDROTEL, le Centre d’expertise hydrique du Quebec (CEHQ), HQ, l’IREQ (Institut de recherche en electricite du Quebec) et d’autres usagers (ex. : l’IMTA, Instituto Mexicano de Technologia del Agua). Au total, plus d’une quarantaine de licences ont ete distribuees tant pour des besoins d’enseignement (Universite de Sherbrooke) et de recherche (Universite Laval, UQTR, UQAC, IREQ, Ecole de Technologie Superieure, INRA de Montpellier, Environnement Canada, Agriculture et Agroalimentaire Canada), que des besoins de prevision hydrologique (IMTA, Ville de Quebec, Centre d’expertise hydrique du Quebec, HQ). La modularite informatique d’HYDROTEL se prete egalement bien a cette synergie car elle offre la possibilite de partager le savoir‐faire et, par l’entremise d’un site internet public (CodePlex), de mettre a la disponibilite de tous les nouvelles versions du noyau de calcul. Ces developpements ont permis a l’equipe de l’INRS‐ETE d’acquerir une reconnaissance internationale en modelisation hydrologique distribuee. En effet, HYDROTEL et PHYSITEL ont dans le passe ete identifie comme les outils a utiliser dans le cadre d’appels de proposition de projets de determination du potentiel hydroelectrique finances par la Banque Mondiale [World Bank, 2009].
Keywords: Rousseau_Alain

Exploring local risk managers' use of flood hazard maps for risk communication purposes in Baden-Württemberg - Kjellgren, S. (Natural Hazards and Earth System Sciences, 2013)
Abstract. In response to the EU Floods Directive (2007/60/EC), flood hazard maps are currently produced all over Europe, reflecting a wider shift in focus from "flood protection" to "risk management", for which not only public authorities but also populations at risk are seen as responsible. By providing a visual image of the foreseen consequences of flooding, flood hazard maps can enhance people's knowledge about flood risk, making them more capable of an adequate response. Current literature, however, questions the maps' awareness raising capacity, arguing that their content and design are rarely adjusted to laypeople's needs. This paper wants to complement this perspective with a focus on risk communication by studying how these tools are disseminated and marketed to the public in the first place. Judging from communication theory, simply making hazard maps publicly available is unlikely to lead to attitudinal or behavioral effects, since this typically requires two-way communication and material or symbolic incentives. Consequently, it is relevant to investigate whether and how local risk managers, who are well positioned to interact with the local population, make use of flood hazard maps for risk communication purposes. A qualitative case study of this issue in the German state of Baden-Württemberg suggests that many municipalities lack a clear strategy for using this new information tool for hazard and risk communication. Four barriers in this regard are identified: perceived disinterest/sufficient awareness on behalf of the population at risk; unwillingness to cause worry or distress; lack of skills and resources; and insufficient support. These barriers are important to address – in research as well as in practice – since it is only if flood hazard maps are used to enhance local knowledge resources that they can be expected to contribute to social capacity building.
Keywords: Ouvrage_Collectif_Numéro1

Perception and Communication of Flood Risks: A Systematic Review of Empirical Research - Kellens, Wim; Terpstra, Teun; De Maeyer, Philippe (Risk Analysis, 2013)
Flood hazards are the most common and destructive of all natural disasters. For decades, experts have been examining how flood losses can be mitigated. Just as in other risk domains, the study of risk perception and risk communication has gained increasing interest in flood risk management. Because of this research growth, a review of the state of the art in this domain is believed necessary. The review comprises 57 empirically based peer‐reviewed articles on flood risk perception and communication from the Web of Science and Scopus databases. The characteristics of these articles are listed in a comprehensive table, presenting research design, research variables, and key findings. From this review, it follows that the majority of studies are of exploratory nature and have not applied any of the theoretical frameworks that are available in social science research. Consequently, a methodological standardization in measuring and analyzing people's flood risk perceptions and their adaptive behaviors is hardly present. This heterogeneity leads to difficulties in comparing results among studies. It is also shown that theoretical and empirical studies on flood risk communication are nearly nonexistent. The article concludes with a summary on methodological issues in the fields of flood‐risk perception and flood‐risk communication and proposes an agenda for future research.
Keywords: Ouvrage_Collectif_Numéro1

Standardised indicators for “resilient cities”: the folly of devising a technical solution to a political problem - Chmutina, Ksenia; Lizarralde, Gonzalo; Von Meding, Jason; Bosher, Lee (International Journal of Disaster Resilience in the Built Environment, 2023)
Purpose Driven by the New Urban Agenda and the Sustainable Development Goals, decision makers have been striving to reorientate policy debates towards the aspiration of achieving urban resilience and monitoring the effectiveness of adaptive measures through the implementation of standardised indicators. Consequently, there has been a rise of indicator systems measuring resilience. This paper aims to argue that the ambition of making cities resilient does not always make them less vulnerable, more habitable, equitable and just. Design/methodology/approach Using an inductive policy analysis of ISO standard 37123:2019 “Sustainable cities and communities — Indicators for resilient cities”, the authors examine the extent to which the root causes of risks are being addressed by the urban resilience agenda. Findings The authors show that the current standardisation of resilience fails to adequately address the political dimension of disaster risk reduction, reducing resilience to a management tool and missing the opportunity to address the socio-political sources of risks. Originality/value Such critical analysis of the Standard is important as it moves away from a hazard-centric approach and, instead, permits to shed light on the socio-political processes of risk creation and to adopt a more nuanced and sensitive understanding of urban characteristics and governance mechanisms.
Keywords: Infolettre; Infolettre_Juin_2023; Lizarralde_Gonzalo

Pratiques et approches déployées pour la prévention des risques liés aux inondations au Québec : Le cas des territoires concernés par les inondations du lac des Deux Montagnes - Fournier, Catherine (Université du Québec, Institut national de la recherche scientifique, 2022)
Les politiques québécoises de prévention des risques liés aux inondations ont été sujettes à débat ces dernières années, avec une remise en cause du modèle centralisé et uniforme à travers le Québec, pour une approche plus intégrée. Celle-ci fait notamment la promotion de mesures axées sur la vulnérabilité et d’une participation plus active des acteurs territoriaux. On en sait toutefois très peu sur les déclinaisons locales de l’approche intégrée dans le contexte québécois. Ce mémoire propose d’interroger les différentes approches locales de la prévention et de soulever les enjeux qu’elles posent du point de vue des autorités qui y participent. L’étude se penche sur le cas des territoires concernés par les inondations du lac des Deux Montagnes (Région hydrographique de l'Outaouais et de Montréal). Le cadre d’analyse met de l’avant l’approche des instruments d’action publique pour comprendre leur appropriation par les acteurs locaux et une approche pragmatique qui consiste à centrer notre regard sur les pratiques et les stratégies de réduction des risques d’inondation. La recherche s’appuie sur trois sources de données : une analyse documentaire des régimes provinciaux de régulation des risques d’inondation, un recensement des pratiques de prévention déployées par les autorités locales concernées par les inondations du lac des Deux Montagnes et une série de 15 entretiens réalisés avec les personnes travaillant au sein de ces différentes autorités. Le cas illustre la difficulté et le faible engagement de prévenir les risques autrement que par l’approche de réduction de l’exposition aux risques imposée par la Politique de protection des rives, du littoral et des plaines inondables (PPRLPI). Toutefois, après les inondations de 2017 et de 2019, des approches alternatives propres aux contextes territoriaux ont été envisagées par différentes organisations. Celles-ci devraient davantage être documentées et mises en débat afin d’envisager un régime provincial de la gestion des risques plus flexible et ouvert à leur coexistence. Uniformed and centralized model of Quebec's flood prevention policies have been recently debated. Integrated approach to flood risk prevention is now put forward, which focus more on vulnerability and foster an active participation of local authorities. Local declinations of the approach are relatively unknown in Quebec. This study presents different local approaches to flood risk prevention and raise issues they pose from the perspective of local authorities involved. It is based on the authority’s concerns by Lac des Deux Montagnes flooding (Outaouais and Montreal hydrographic region). Combining a political sociology approach to policy instruments and a pragmatic approach, we focus on risk regulation regimes, practices and risk reduction strategies. Three sources of data were used: an analysis of flood risk regulation regimes, an inventory of prevention practices deployed by local authorities and 15 interviews conducted with professionals among these authorities. Results show the difficulty and low commitment to implement local distinct approaches apart from prohibiting and discouraging exposure to flood risk enforced by the Protection Policy for Lakeshores, Riverbanks, Littoral Zones and Floodplains. However, after the floods of 2017 and 2019, alternative strategies specific to different territorial contexts were considered. These should be better documented and debated in order to consider a more flexible and coexistence provincial policy.
Keywords: Site_internet_RIISQ

Disrupting the riskscapes of inequities: a case study of planning for resilience in Canada’s Metro Vancouver region - Yumagulova, Lilia (Cambridge Journal of Regions, Economy and Society, 2020)
Abstract The analysis across spatial, temporal and governance scales shows an inequitable distribution of risk across Canada’s Metro Vancouver region. For First Nation communities in this region, this risk is rooted in the colonial history of land dispossession. This article makes a contribution by expanding our understanding of historic creation of riskscapes and a discussion of its implications as a multiscale governance issue that persists across space and time. This article also situates the impacts of projected sea level rise on Indigenous communities in the context of regional, provincial and federal settler-colonial flood risk management regime.

Justice and Resilience in Flood Risk Management: What Are the Socio-Political Implications? - Thaler, Thomas (2021)
Flood risk management requires to comprehensively assess how policy strategies may affect individuals and communities. However, policy development and implementation often downplay or even increase social inequality. Analysis of the social and societal implications of strategies and implementation projects to manage flood hazards is still in its infancy. To close this gap, this chapter critically questions the roles of social justice and their political implications for flood risk management with regard to resilience. The chapter discusses and argues how different theoretical concepts as well as different perspectives on justice (e.g. social, environmental and climate justice) and resilience in flood risk management are related. There is a strong need to have a broader and more in-depth discussion about the role of justice in the current resilience debate. Finally, the chapter presents the outline of a future research agenda.

Dependence of tropical cyclone damage on maximum wind speed and socioeconomic factors - Ye, Mengqi; Wu, Jidong; Liu, Wenhui; He, Xin; Wang, Cailin (Environmental Research Letters, 2020)
© 2020 The Author(s). Published by IOP Publishing Ltd.Tropical cyclones (TCs) have devastating impacts and are responsible for significant damage. Consequently, for TC-induced direct economic loss (DEL) attribution all factors associated with risk (i.e. hazard, exposure and vulnerability) must be examined. This research quantifies the relationship between TC-induced DELs and maximum wind speed, asset value and Gross Domestic Product (GDP) per capita using a regression model with TC records from 2000 to 2015 for China's mainland area. The coefficient of the maximum wind speed term indicates that a doubling of the maximum wind speed increases DELs by 225% [97%, 435%] when the other two variables are held constant. The coefficient of the asset value term indicates that a doubling of asset value exposed to TCs increases DELs by 79% [58%, 103%]; thus, if hazard and vulnerability are assumed to be constant in the future, then a dramatic escalation in TC-induced DELs will occur given the increase in asset value, suggesting that TC-prone areas with rapid urbanization and wealth accumulation will inevitably be subject to higher risk. Reducing the asset value exposure via land-use planning, for example, is important for decreasing TC risk. The coefficient of GDP per capita term indicates that a doubling in GDP per capita could decrease DELs by 54% [39%, 66%]. Because accumulated assets constantly increase people's demand for improved security, stakeholders must invest in risk identification, early warning systems, emergency management and other effective prevention measures with increasing income to reduce vulnerability. This research aims to quantitatively connect TC risk (expected DELs, specifically) to physical and socioeconomic drivers and emphasizes how human dimensions could contribute to TC risk. Moreover, the model can be used to estimate TC risk under climate change and future socioeconomic development in the context of China.

Risk and Resilience: A Case of Perception versus Reality in Flood Management - Agrawal, Nirupama; Elliott, Mark; Simonovic, Slobodan P. (Water, 2020)
Canada’s vast regions are reacting to climate change in uncertain ways. Understanding of local disaster risks and knowledge of underlying causes for negative impacts of disasters are critical factors to working toward a resilient environment across the social, economic, and the built sectors. Historically, floods have caused more economical and social damage around the world than other types of natural hazards. Since the 1900s, the most frequent hazards in Canada have been floods, wildfire, drought, and extreme cold, in terms of economic damage. The recent flood events in the Canadian provinces of Ontario, New Brunswick, Quebec, Alberta, and Manitoba have raised compelling concerns. These include should communities be educated with useful knowledge on hazard risk and resilience so they would be interested in the discussion on the vital role they can play in building resilience in their communities. Increasing awareness that perceived risk can be very different from the real threat is the motivation behind this study. The main objectives of this study include identifying and quantifying the gap between people’s perception of exposure and susceptibility to the risk and a lack of coping capacity and objective assessment of risk and resilience, as well as estimating an integrated measure of disaster resilience in a community. The proposed method has been applied to floods as an example, using actual data on the geomorphology of the study area, including terrain and low lying regions. It is hoped that the study will encourage a broader debate if a unified strategy for disaster resilience would be feasible and beneficial in Canada.

L’acceptabilité sociale : trajectoire d’une nouvelle norme d’action publique - Simard, Louis (Politique et Sociétés, 2021)
La notion d’acceptabilité sociale est devenue incontournable dans plusieurs secteurs de l’action publique. Au coeur des grands projets d’aménagement et d’urbanisme, énergétiques, d’extraction des ressources, ou qui concernent l’environnement en général, cette nouvelle norme publique apparaît comme un traceur de changements importants en matière de décision tant sur le plan substantif que processuel. Comment comprendre cette notion ? Comment l’étudier et quelle trajectoire a-t-elle connu au Québec ? Dans cet article nous proposons dans un premier temps un cadre théorique pour étudier cet objet : l’approche par les instruments d’action publique, en la considérant comme un instrument de type normatif visant à favoriser la coordination, la coopération et la prévisibilité dans un environnement complexe, par la recherche d’un ajustement négocié sur des bases scientifiques et politiques. Nous présentons ensuite les principales composantes pour bien définir l’acceptabilité sociale. Enfin nous proposons d’étudier la trajectoire de cette norme sur plus de 40 ans au Québec à travers l’étude des rapports du Bureau d’audiences publiques sur l’environnement, le Chantier sur l’acceptabilité sociale (2014-2015) et deux jugements des tribunaux (Cour supérieure du Québec en 2017 et Cour d’appel du Québec en 2020). Nous constatons une montée en importance de l’acceptabilité sociale au cours des décennies, pour devenir le critère ultime de décision en plus de s’institutionnaliser jusqu’à être confirmée dans sa portée juridique et pouvant apparaître comme le chaînon manquant entre démocratie participative et démocratie représentative. , The notion of social acceptability has become unavoidable in many areas of public policy. At the heart of major planning and urban planning projects, energy, resource extraction, or the environment in general, this new public standard appears to be a tracer of significant decision-making changes, both substantive and procedural. How is this notion understood? How can it be studied and what was its trajectory in Quebec? We first propose a theoretical framework for studying this object, that is, the approach by public policy instruments as a normative instrument aimed at promoting coordination, cooperation, and predictability in a complex environment, through the search for a negotiated adjustment based on scientific and political grounds. We then present the main components for a definition of social acceptability. Finally, we propose to study the trajectory of this standard over more than forty years in Quebec through the study of the reports of the Office of Public Hearings on the Environment, the governmental workshop on social acceptability (2014-2015), and two court judgments (2017 and 2020). We found an increase in importance of social acceptability over the decades, to the point of becoming the ultimate criterion of decision and institutionalizing, and being confirmed in its legal scope; it may appear to be the missing link between participatory democracy and representative democracy.
Keywords: Ouvrage_Collectif_Numéro1

Scenarios of Human Responses to Unprecedented Social‐Environmental Extreme Events - Rusca, Maria; Messori, Gabriele; Di Baldassarre, Giuliano (Earth's Future, 2021)
Abstract In a rapidly changing world, what is today an unprecedented extreme may soon become the norm. As a result, extreme‐related disasters are expected to become more frequent and intense. This will have widespread socio‐economic consequences and affect the ability of different societal groups to recover from and adapt to rapidly changing environmental conditions. Therefore, there is the need to decipher the relation between genesis of unprecedented events, accumulation and distribution of risk, and recovery trajectories across different societal groups. Here, we develop an analytical approach to unravel the complexity of future extremes and multiscalar societal responses—from households to national governments and from immediate impacts to longer term recovery. This requires creating new forms of knowledge that integrate analyses of the past—that is, structural causes and political processes of risk accumulation and differentiated recovery trajectories—with plausible scenarios of future environmental extremes grounded in the event‐specific literature. We specifically seek to combine the physical characteristics of the extremes with examinations of how culture, politics, power, and policy visions shape societal responses to unprecedented events, and interpret the events as social‐environmental extremes. This new approach, at the nexus between social and natural sciences, has the concrete advantage of providing an impact‐focused vision of future social‐environmental risks, beyond what is achievable within conventional disciplinary boundaries. In this paper, we focus on extreme flooding events and the societal responses they elicit. However, our approach is flexible and applicable to a wide range of extreme events. We see it as the first building block of a new field of research, allowing for novel and integrated theoretical explanations and forecasting of social‐environmental extremes. , Key Points We conceptualize unprecedented extremes as social‐environmental processes shaped by institutional, political, and economic change As social‐environmental extremes become more frequent, there is an urgency to unravel their genesis and the possible societal responses This approach is the first building block of a new field of research in social‐environmental extreme event forecasts , Plain Language Summary The world is seeing increases in a range of extreme events, and this increase may continue or even accelerate in the future, due to anthropogenic climate change. Furthermore, it is often those who are already vulnerable that experience the biggest impacts from these extremes. Yet, there is little understanding of the possible societal responses to unprecedented events. This underscores the urgency of creating innovative approaches to develop plausible scenarios of societal responses and, in turn, mitigate hazards and reduce vulnerability and exposure to extreme events. In this commentary, we develop a truly interdisciplinary conceptual approach to better understand how different societal groups might interact with and respond to future unprecedented extreme events. We combine social science theories describing how different societal groups are affected by, and recover from, extreme events with projections from the literature identifying plausible areas at risk of unprecedented occurrences and local analyses of past extreme events. We see this as the first building block of a new field of research in forecasting social‐environmental extremes that could support governments, civil protection agencies, and civil society organizations to ensure a fairer, improved response to future events.

Modeling the Impacts of Urban Flood Risk Management on Social Inequality - Moulds, Simon; Buytaert, Wouter; Templeton, Michael R.; Kanu, Ishmael (Water Resources Research, 2021)
Abstract The exposure of urban populations to flooding is highly heterogeneous, with the negative impacts of flooding experienced disproportionately by the poor. In developing countries experiencing rapid urbanization and population growth a key distinction in the urban landscape is between planned development and unplanned, informal development, which often occurs on marginal, flood‐prone land. Flood risk management in the context of informality is challenging, and may exacerbate existing social inequalities and entrench poverty. Here, we adapt an existing socio‐hydrological model of human‐flood interactions to account for a stratified urban society consisting of planned and informal settlements. In the first instance, we use the model to construct four system archetypes based on idealized scenarios of risk reduction and disaster recovery. We then perform a sensitivity analysis to examine the relative importance of the differential values of vulnerability, risk‐aversion, and flood awareness in determining the relationship between flood risk management and social inequality. The model results suggest that reducing the vulnerability of informal communities to flooding plays an important role in reducing social inequality and enabling sustainable economic growth, even when the exposure to the flood hazard remains high. Conversely, our model shows that increasing risk aversion may accelerate the decline of informal communities by suppressing economic growth. On this basis, we argue for urban flood risk management which is rooted in pro‐poor urban governance and planning agendas which recognize the legitimacy and permanence of informal communities in cities. , Key Points The distribution of flood risk in urban areas is uneven, with the negative impacts experienced disproportionately by the urban poor Our model shows that reducing the vulnerability of informal residents to flooding can reduce inequality, even when their exposure is high Based on the model results, we argue that urban flood risk management should be rooted in pro‐poor urban governance and planning agendas

Les facteurs ayant facilité l’intervention sociale auprès de sinistrés lors des inondations de 2019 : point de vue de gestionnaires et d’intervenants sociaux - Maltais, Danielle; Hamel, Ariane; Lansard, Anne-Lise (INTERVENTION 2024, 2024)

Flood occurrence and impact models for socioeconomic applications over Canada and the United States - Grenier, Manuel; Boudreault, Mathieu; Carozza, David A.; Boudreault, Jérémie; Raymond, Sébastien (Natural Hazards and Earth System Sciences, 2024)
Abstract. Large-scale socioeconomic studies of the impacts of floods are difficult and costly for countries such as Canada and the United States due to the large number of rivers and size of watersheds. Such studies are however very important for analyzing spatial patterns and temporal trends to inform large-scale flood risk management decisions and policies. In this paper, we present different flood occurrence and impact models based upon statistical and machine learning methods of over 31 000 watersheds spread across Canada and the US. The models can be quickly calibrated and thereby easily run predictions over thousands of scenarios in a matter of minutes. As applications of the models, we present the geographical distribution of the modelled average annual number of people displaced due to flooding in Canada and the US, as well as various scenario analyses. We find for example that an increase of 10 % in average precipitation yields an increase in the displaced population of 18 % in Canada and 14 % in the US. The model can therefore be used by a broad range of end users ranging from climate scientists to economists who seek to translate climate and socioeconomic scenarios into flood probabilities and impacts measured in terms of the displaced population.
Keywords: Infolettre; Infolettre_Decembre_2024

Interregional imbalance in the Yellow River Basin: Insights from flood-sediment transport, socioeconomic, and environmental subsystems - Hu, Hao; Tian, Guiliang; Adamowski, Jan F.; Albano, Raffaele; Liu, Yixue; Jing, Xiaodong; Zhao, Qiuya (Journal of Environmental Management, 2024)
Keywords: Infolettre; Infolettre_Decembre_2024

Intersectoral approaches: the key to mitigating psychosocial and health consequences of disasters and systemic risks - Gousse-Lessard, Anne-Sophie; Gachon, Philippe; Lessard, Lily; Vermeulen, Valérie; Boivin, Maxime; Maltais, Danielle; Landaverde, Elsa; Généreux, Mélissa; Motulsky, Bernard; Le Beller, Julien (Disaster Prevention and Management: An International Journal, 2023)
Purpose The current pandemic and ongoing climate risks highlight the limited capacity of various systems, including health and social ones, to respond to population-scale and long-term threats. Practices to reduce the impacts on the health and well-being of populations must evolve from a reactive mode to preventive, proactive and concerted actions beginning at individual and community levels. Experiences and lessons learned from the pandemic will help to better prevent and reduce the psychosocial impacts of floods, or other hydroclimatic risks, in a climate change context. Design/methodology/approach The present paper first describes the complexity and the challenges associated with climate change and systemic risks. It also presents some systemic frameworks of mental health determinants, and provides an overview of the different types of psychosocial impacts of disasters. Through various Quebec case studies and using lessons learned from past and recent flood-related events, recommendations are made on how to better integrate individual and community factors in disaster response. Findings Results highlight the fact that people who have been affected by the events are significantly more likely to have mental health problems than those not exposed to flooding. They further demonstrate the adverse and long-term effects of floods on psychological health, notably stemming from indirect stressors at the community and institutional levels. Different strategies are proposed from individual-centered to systemic approaches, in putting forward the advantages from intersectoral and multirisk researches and interventions. Originality/value The establishment of an intersectoral flood network, namely the InterSectoral Flood Network of Québec (RIISQ), is presented as an interesting avenue to foster interdisciplinary collaboration and a systemic view of flood risks. Intersectoral work is proving to be a major issue in the management of systemic risks, and should concern communities, health and mental health professionals, and the various levels of governance. As climate change is called upon to lead to more and more systemic risks, close collaboration between all the areas concerned with the management of the factors of vulnerability and exposure of populations will be necessary to respond effectively to damages and impacts (direct and indirect) linked to new meteorological and compound hazards. This means as well to better integrate the communication managers into the risk management team.
Keywords: Boivin_Maxime; Gachon_Philippe; Gousse-Lessard_Anne-Sophie; Généreux_Mélissa; Infolettre; Infolettre_Fevrier_2023; Lessard_Lily; Site_internet_RIISQ

Intersectoral research and multi-risk approaches in Québec: systemic risk management and its psychosocial consequences - Gousse-Lessard, Anne-Sophie; Gachon, Philippe; Lessard, Lily; Vermeulen, Valérie; Boivin, Maxime; Maltais, Danielle; Landaverde, Elsa; Généreux, Mélissa; Motulsky, Bernard; Le Beller, Julien (Contribution paper to the Global Assessment Report on Disaster Risk Reduction, 2022)
Purpose The current pandemic and ongoing climate risks highlight the limited capacity of various systems, including health and social ones, to respond to population-scale and long-term threats. Practices to reduce the impacts on the health and well-being of populations must evolve from a reactive mode to preventive, proactive and concerted actions beginning at individual and community levels. Experiences and lessons learned from the pandemic will help to better prevent and reduce the psychosocial impacts of floods, or other hydroclimatic risks, in a climate change context. Design/methodology/approach The present paper first describes the complexity and the challenges associated with climate change and systemic risks. It also presents some systemic frameworks of mental health determinants, and provides an overview of the different types of psychosocial impacts of disasters. Through various Quebec case studies and using lessons learned from past and recent flood-related events, recommendations are made on how to better integrate individual and community factors in disaster response. Findings Results highlight the fact that people who have been affected by the events are significantly more likely to have mental health problems than those not exposed to flooding. They further demonstrate the adverse and long-term effects of floods on psychological health, notably stemming from indirect stressors at the community and institutional levels. Different strategies are proposed from individual-centered to systemic approaches, in putting forward the advantages from intersectoral and multirisk researches and interventions. Originality/value The establishment of an intersectoral flood network, namely the InterSectoral Flood Network of Québec (RIISQ), is presented as an interesting avenue to foster interdisciplinary collaboration and a systemic view of flood risks. Intersectoral work is proving to be a major issue in the management of systemic risks, and should concern communities, health and mental health professionals, and the various levels of governance. As climate change is called upon to lead to more and more systemic risks, close collaboration between all the areas concerned with the management of the factors of vulnerability and exposure of populations will be necessary to respond effectively to damages and impacts (direct and indirect) linked to new meteorological and compound hazards. This means as well to better integrate the communication managers into the risk management team.
Keywords: Boivin_Maxime; Gachon_Philippe; Gousse-Lessard_Anne-Sophie; Généreux_Mélissa; Lessard_Lily; Site_internet_RIISQ

From Science to Policy and Practice: A Critical Assessment of Knowledge Management before, during, and after Environmental Public Health Disasters - Généreux, Mélissa; Lafontaine, Marc; Eykelbosh, Angela (International Journal of Environmental Research and Public Health, 2019)
Canada regularly faces environmental public health (EPH) disasters. Given the importance of evidence-based, risk-informed decision-making, we aimed to critically assess the integration of EPH expertise and research into each phase of disaster management. In-depth interviews were conducted with 23 leaders in disaster management from Canada, the United States, the United Kingdom, and Australia, and were complemented by other qualitative methods. Three topics were examined: governance, knowledge creation/translation, and related barriers/needs. Data were analyzed through a four-step content analysis. Six critical success factors emerged from the analysis: blending the best of traditional and modern approaches; fostering community engagement; cultivating relationships; investing in preparedness and recovery; putting knowledge into practice; and ensuring sufficient human and financial resources. Several promising knowledge-to-action strategies were also identified, including mentorship programs, communities of practice, advisory groups, systematized learning, and comprehensive repositories of tools and resources. There is no single roadmap to incorporate EPH expertise and research into disaster management. Our findings suggest that preparation for and management of EPH disaster risks requires effective long-term collaboration between science, policy, and EPH practitioners at all levels in order to facilitate coordinated and timely deployment of multi-sectoral/jurisdictional resources when and where they are most needed.
Keywords: Généreux_Mélissa

Psychosocial Management Before, During, and After Emergencies and Disasters—Results from the Kobe Expert Meeting - Généreux, Mélissa; Schluter, Philip J.; Takahashi, Sho; Usami, Shiori; Mashino, Sonoe; Kayano, Ryoma; Kim, Yoshiharu (International Journal of Environmental Research and Public Health, 2019)
Emergencies and disasters typically affect entire communities, cause substantial losses and disruption, and result in a significant and persistent mental health burden. There is currently a paucity of evidence on safe and effective individual- and community-level strategies for improving mental health before, during, and after such events. In October 2018, the World Health Organization (WHO) Centre for Health Development (WHO Kobe Centre) convened a meeting bringing together leading Asia Pacific and international disaster research experts. The expert meeting identified key research needs in five major areas, one being “Psychosocial management before, during, and after emergencies and disasters”. Experts for this research area identified critical gaps in observational research (i.e., the monitoring of long-term psychological consequences) and interventional research (i.e., the development and evaluation of individual- and community-level interventions). Three key research issues were identified. First, experts underscored the need for a standardized and psychometrically robust instrument that classified the mental health/psychosocial risk of people within both a clinical and community setting. Then, the need for a standardization of methods for prevention, screening, diagnosis, and treatment for affected people was highlighted. Finally, experts called for a better identification of before, during, and after emergency or disaster assets associated with greater community resilience.
Keywords: Généreux_Mélissa

Article introductif – L’acceptabilité sociale, une question de démocratie participative ? - Friser, Alice; Yates, Stéphanie (Revue internationale de psychosociologie et de gestion des comportements organisationnels, 2021)
La construction de l’acceptabilité sociale, conçue comme le jugement collectif des populations à l’endroit d’une politique ou d’un projet donné, s’appuie parfois sur la participation des acteurs sociaux concernés aux discussions éclairant la prise de décision publique. Les instances de démocratie intermédiaires où sont déployés divers dispositifs participatifs jouent ainsi un rôle de premier plan quant à l’émergence de l’acceptabilité. Or, la question des effets des processus participatifs sur les dynamiques d’acceptabilité sociale demeure aujourd’hui peu étudiée, que ce soit par les travaux sur l’acceptabilité sociale ou ceux portant sur la participation publique. À partir de projets soulevant des préoccupations de nature environnementale, ce numéro spécial puise à l’intersection de ces deux champs théoriques en vue d’analyser l’impact des dispositifs de démocratie participative sur la prise de décision et la construction de l’accessibilité sociale. Les contributions permettent ainsi de réfléchir à la façon dont les instances de démocratie intermédiaires contribuent ou non à l’acceptabilité sociale. De manière plus spécifique, elles explorent l’institutionnalisation du concept comme nouvelle norme de gestion publique, les effets des processus participatifs déployés dans ces instances sur l’acceptabilité d’un projet donné, de même que les effets sur les décisions finales. En somme, la réflexion proposée dans ce numéro permet de voir dans quelle mesure les dispositifs participatifs offrent les conditions d’un débat constructif permettant de mieux canaliser les conflits sociétaux que suscitent certains projets industriels ou politiques publiques, en vue de construire des compromis qui se projettent dans une vision d’avenir du développement.
Keywords: Ouvrage_Collectif_Numéro1

Assessing social vulnerability and identifying spatial hotspots of flood risk to inform socially just flood management policy. - Chakraborty, Liton; Thistlethwaite, Jason; Scott, Daniel; Henstra, Daniel; Minano, Andrea; Rus, Horatiu A. (Risk Analysis, 2022)
This study presents the first nationwide spatial assessment of flood risk to identify social vulnerability and flood exposure hotspots that support policies aimed at protecting high-risk populations and geographical regions of Canada. The study used a national-scale flood hazard dataset (pluvial, fluvial, and coastal) to estimate a 1-in-100-year flood exposure of all residential properties across 5721 census tracts. Residential flood exposure data were spatially integrated with a census-based multidimensional social vulnerability index (SoVI) that included demographic, racial/ethnic, and socioeconomic indicators influencing vulnerability. Using Bivariate Local Indicators of Spatial Association (BiLISA) cluster maps, the study identified geographic concentration of flood risk hotspots where high vulnerability coincided with high flood exposure. The results revealed considerable spatial variations in tract-level social vulnerability and flood exposure. Flood risk hotspots belonged to 410 census tracts, 21 census metropolitan areas, and eight provinces comprising about 1.7 million of the total population and 51% of half-a-million residential properties in Canada. Results identify populations and the geographic regions near the core and dense urban areas predominantly occupying those hotspots. Recognizing priority locations is critically important for government interventions and risk mitigation initiatives considering socio-physical aspects of vulnerability to flooding. Findings reinforce a better understanding of geographic flood-disadvantaged neighborhoods across Canada, where interventions are required to target preparedness, response, and recovery resources that foster socially just flood management strategies.

La réforme Barrette et sa mise en oeuvre dans les services sociaux : perceptions des travailleuses sociales - Bourque, Mélanie; Barbe, Mylène; Leroux, Maxime; Grenier, Josée; St-Amour, Nathalie (Intervention, 2024)
Cet article vise à partager les résultats préliminaires du projet de recherche « Les travailleuses sociales cinq ans après l’implantation de la réforme Barrette : standardisation de la pratique ou nouvelles normes locales des établissements? ». Ce projet de recherche a pour but de mieux comprendre la mise en oeuvre de la réforme du système de santé et des services sociaux de 2015 au Québec. De juin à décembre 2022, près de 60 personnes participantes ont accepté de répondre à un entretien semi-dirigé. La très grande majorité d’entre elles détiennent plus de dix ans d’expérience, ce qui permet de comprendre l’avant et l’après réforme Barrette et de saisir les effets de cette réforme sur les équipes de travail, mais aussi sur la prestation des services fournis à la population. L’analyse initiale des données met en lumière la poursuite, voire l’accentuation, de la perspective descendante (top down) du processus décisionnel, de la reddition de comptes par le biais de mesures quantitatives et de l’harmonisation des services s’illustrant en standardisation des pratiques, en dépit des particularités territoriales inhérentes aux différentes régions du Québec. Par rapport à notre recherche précédente, force est de constater que les méthodes de la nouvelle gestion publique se sont accentuées au sein du réseau de la santé et des services sociaux, qualifié de « maison des fous » par plusieurs personnes participantes.
Keywords: StAmour_Nathalie

L’épreuve d’acceptabilité sociale, ou la composition disputée du collectif - Barbier, Rémi (Revue internationale de psychosociologie et de gestion des comportements organisationnels, 2021)
Parfois contestée, faiblement théorisée, la notion d’acceptabilité sociale tend néanmoins à s’imposer dans divers secteurs d’activité. Face à ce constat, cet article fait le pari qu’il peut être pertinent de la conserver et de l’utiliser comme « locution frontière » permettant de communiquer avec de nombreux acteurs. Mais cette concession est redoublée par une ambition de consolidation théorique de la notion, et par un souci de symétrisation de la charge d’acceptabilité d’un projet : celle-ci ne peut reposer uniquement sur un social récalcitrant à éduquer et à convaincre, elle doit également remettre en jeu le design du projet. L’article prend appui pour ce faire sur l’analyse des conflits spatialisés autour des équipements d’environnement. Il s’inscrit au croisement des approches STS et pragmatistes : ce cadre conceptuel est retenu car il permet d’étudier la composition d’un collectif (le monde social étendu à sa matérialité constitutive) sans présupposer d’asymétrie entre négociations sociales et techniques. L’épreuve d’acceptabilité porte plus précisément sur la compatibilité problématique entre deux ensembles rendus provisoirement indéterminés par le conflit : un dispositif sociotechnique d’un côté, un ou plusieurs milieux concernés de l’autre. L’article interprète cette épreuve d’acceptabilité en tant que régulation civique d’un projet technique, complétant la régulation de base dont il est normalement l’objet. Il prolonge enfin l’usage de cette notion avec une perspective opérationnelle, en proposant des pistes permettant à un éventuel tiers arbitre de piloter cette épreuve et d’en tirer démocratiquement les leçons.
Keywords: Ouvrage_Collectif_Numéro1

Limite à vie sur les inondations successives : vers un nouveau pacte social ? - Boudreault, Mathieu; Bourdeau-Brien, Michaël (Assurances et gestion des risques / Insurance and Risk Management, 2020)
Après les nombreuses crues printanières qui ont affecté le sud du Québec depuis 2011, le gouvernement du Québec a annoncé en avril 2019 une refonte importante de son programme d’aide financière aux sinistrés. Le programme introduit désormais une couverture limitée à vie de 100 000 $ pour les inondations successives, une mesure unique au Canada. L’objectif de cet article est d’analyser le coût des inondations successives et les impacts financiers de cette limite de couverture pour les ménages.
Keywords: Bourdeau-Brien_Michael; Ouvrage_Collectif_Numéro1; Site_internet_RIISQ

Mental health and retirement savings: Confounding issues with compounding interest - Bogan, Vicki L.; Fertig, Angela R. (Health Economics, 2018)
Summary The questionable ability of the U.S. pension system to provide for the growing elderly population combined with the rising number of people affected by depression and other mental health issues magnifies the need to understand how these household characteristics affect retirement. Mental health problems have a large and significant negative effect on retirement savings. Specifically, psychological distress is associated with decreasing the probability of holding retirement accounts by as much as 24 percentage points and decreasing retirement savings as a share of financial assets by as much as 67 percentage points. The magnitude of these effects underscores the importance of employer management policy and government regulation of these accounts to help ensure households have adequate retirement savings.
Keywords: Ouvrage_Collectif_Numéro1

Un cadre de gouvernance collaboratif dédié à l’appréciation des risques des systèmes essentiels dans un contexte de changements climatiques - Robert, Benoît; Hémond, Yannick; Baril, Geneviève; Therrien, Marie-Christine (Canadian Journal of Emergency Management, 2022)
The fall 2021 climate events in British Columbia raise questions about the resiliency of communities, but also of critical systems, with respect to the allocation of roads, telecommunications, drinking water, electricity, etc. The interdependence of these systems can quickly generate serious consequences for populations and socio-economic activities that local and regional authorities must manage. The diversity and number of stakeholders require these authorities to coordinate well. How then can the risks to which they are exposed be better assessed? How can we ensure coherence in the measures put in place in terms of planning, preparation and response? The concepts and results presented in this article are the result of an action-research project carried out with the participation of numerous partners, particularly, but not exclusively, from municipal milieus in two regions of Quebec (Argenteuil and Brome-Missisquoi MRCs). This active collaboration with these regional partners has made it possible to propose an approach for implementing a collaborative governance framework combined with a risk assessment process. The tools and mechanisms associated with this approach will allow regional authorities to better understand the impact of climate change on the territory and to ensure consistency in the risk management actions of the various stakeholders. , Les événements climatiques de l’automne 2021 en Colombie-Britannique soulèvent des questions sur la résilience des communautés, mais aussi des systèmes essentiels, en regard de l’affectation des réseaux routiers, de télécommunication, d’eau potable, d’électricité, etc. L’interdépendance de ces systèmes génère rapidement des conséquences graves pour la population et les activités socioéconomiques que les autorités locales et régionales doivent gérer. La diversité des intervenants ainsi que leur nombre exigent de ces autorités de bien se coordonner. Comment alors peut-on mieux apprécier les risques auxquels ils sont exposés ? Comment s’assurer d’une cohérence dans les mesures mises en place autant dans la planification, la préparation que l’intervention ? Les concepts et résultats présentés dans cet article sont issus d’un projet de recherche-action réalisé avec la participation de nombreux partenaires, particulièrement, mais non exclusivement du milieu municipal dans deux régions du Québec (MRC d’Argenteuil et de Brome-Missisquoi). Cette collaboration active avec ces partenaires régionaux permet de proposer une démarche pour mettre en place un cadre de gouvernance collaboratif combiné à un processus d’appréciation des risques. Les outils et mécanismes associés à cette démarche permettront, alors, aux autorités régionales de mieux comprendre l’impact des changements climatiques sur le territoire et d’assurer une cohérence dans les actions de gestion des risques des différentes parties prenantes.
Keywords: Hémond_Yannick

Multicriteria Decision Analysis to Assist in the Selection of Coastal Defence Measures: Involving Coastal Managers and Professionals in the Identification and Weighting of Criteria - Sauvé, Philippe; Bernatchez, Pascal; Glaus, Mathias (Frontiers in Marine Science, 2022)
Coastal socio-ecological systems are complex adaptive systems with nonlinear changing properties and multi-scale dynamics. They are influenced by unpredictable coastal hazards accentuated by the effects of climate change, and they can quickly be altered if critical thresholds are crossed. Additional pressures come from coastal activities and development, both of which attracting stakeholders with different perspectives and interests. While coastal defence measures (CDMs) have been implemented to mitigate coastal hazards for centuries, a lack of knowledge and tools available to make informed decision has led to coastal managers favouring the choice of seawalls or rock armours with little consideration for socio-ecological systems features, and stakeholders’ priorities. Though it is not currently widely applied in coastal zone management, multicriteria decision analysis (MCDA) is a tool that can be useful to facilitate decision making. PROMETHEE, an outranking method, was chosen to support the multicriteria decision analysis for the evaluation of CDMs in the context of four study sites characterized by distinct environmental features. The aim was to determine the relevance and benefits of a MCDA by integrating coastal zone stakeholders in a participatory decision-making process in order to select CDMs that are better adapted to the whole socio-ecological system. First, in a series of five workshops, stakeholders were asked to identify and weigh criteria that were relevant to their local conditions. Second and third, CDMs were evaluated in relation to each criterion within the local context, then, hierarchized. Initial results show that vegetation came first in three of the four sites, while rock armour ranked first in the fourth site. A post-evaluation of the participatory process indicated that the weighting phase is an effective way to integrate local knowledge into the decision-making process, but the identification of criteria could be streamlined by the presentation of a predefined list from which participants could make a selection. This would ensure criteria that are standardized, and in a format that is compatible with the MCDA. Coupled with a participatory process MCDA proved to be a flexible methodology that can synthetize multiple aspects of the problem, and contribute in a meaningful way to the coastal engineering and management decision-making process.
Keywords: Infolettre; Infolettre_Juillet_2022; Site_internet_RIISQ

Gouvernance régionale et stratégies d’adaptation aux inondations en contexte de changements climatiques : une étude de cas, la MRC de Vaudreuil-Soulanges - Thivierge, Caroline (2021)
L’objectif de cette recherche est d’identifier les stratégies d’adaptation qui sont requises et du ressort d’une municipalité régionale de comté face aux inondations. Le réchauffement global des températures soulève plusieurs inquiétudes quant à la modification du cycle hydrologique. Les inondations figurent en tête de liste des enjeux de sécurité civile des municipalités riveraines. Au Québec, on prévoit une augmentation des précipitations printanières, automnales et hivernales, ainsi que des débits hivernaux plus élevés et un devancement des crues printanières. Des projections qui peuvent influencer l’approche de gestion des barrages, bien que le contrôle des niveaux d’eau ne soit pas une panacée vis-à-vis des inondations. Il suppose une gestion intégrée de l’eau parfois complexe. Aussi, les administrations locales ne siègent pas toujours aux comités responsables de la régularisation des cours d’eau. Celles-ci se retrouvent sur la ligne de front sans pour autant avoir le pouvoir et les ressources financières pour y faire face. Les crues exceptionnelles de 2017 et 2019 ont conduit la Municipalité régionale de comté de Vaudreuil-Soulanges à mettre à jour ses plans d’urgence et à mettre en place une cellule de crise. Elle applique une stratégie d’adaptation correspondant aux 4 axes du Plan de protection du territoire face aux inondations du ministère des Affaires municipales et de l’Habitation. Ces outils enrichissent leur capacité d’adaptation par l’acquisition de nouvelles connaissances et d’une nouvelle cartographie des zones inondables. Les vulnérabilités qui résultent de contraintes liées à l’aménagement du territoire, ainsi que d’enjeux réglementaires posent un défi pour le développement du territoire et la relocalisation de résidences inondées. Il convient de sonder la population sur sa vision de la résilience afin d’assurer une meilleure acceptabilité sociale des décisions à venir. Une vulnérabilité importante réside dans les écarts de perception du risque entre les municipalités et entre les individus ; ce qui engendre des enjeux de sécurité, de communication et de gouvernance. Les instances locales peuvent miser sur leurs habiletés de mobilisation pour réunir la communauté autour du développement d’un plan d’adaptation aux changements climatiques et ainsi harmoniser les perceptions. Finalement, l’épuisement des ressources humaines des municipalités inondées à répétition est à considérer. Il appert qu’il est essentiel d’identifier et de mettre en place les outils et ressources pour les soutenir.
Keywords: Ouvrage_Collectif_Numéro1

Gray Zones: The Everyday Practices and Governance of Water beyond the Network - Truelove, Yaffa (Annals of the American Association of Geographers, 2019)
Keywords: Ouvrage_Collectif_Numéro1

A review of the flood risk management governance and resilience literature - Morrison, A.; Westbrook, C.J.; Noble, B.F. (Journal of Flood Risk Management, 2018)
The environmental management literature suggests that resilience is key to managing complex systems and reducing vulnerability resulting from uncertainty and unexpected change. Yet, flood risk management (FRM) has emerged largely from a culture of resistance. This paper takes the pulse of the current state of FRM research, with a focus on how the scholarly community has approached governance for flood resilience. Our analysis of the FRM journal literature identified 258 articles addressing governance and flooding, resilience and adaptation. Five main research themes emerged from these articles, addressing a variety of issues, but mostly lacking the degree of integration needed to address the social‐ecological complexity of FRM. Overall, research supporting the governance of FRM for resilience lacks integration, and methods of mitigating this lack of integration are poorly studied. We conclude with a discussion about the nature and scope of FRM research for resilience, and identify opportunities for more integrative FRM research that is more tightly coupled with policy and practice.
Keywords: Ouvrage_Collectif_Numéro1

Aménagement du territoire et gestion des zones inondables : enjeux de gouvernance et d’encadrement réglementaire - Gauthier, Mario; Biron, Pascale; Buffin-Belanger, Thomas (Les inondations au Québec : risques, aménagement du territoire, impacts socioéconomiques et transformation des vulnérabilités, 2022)
Keywords: Chapitre_Ouvrage_Collectif_Numero1

Gouvernance régionale et leviers mobilisables d’une gestion intégrée de l’eau : le cas de Vaudreuil-Soulanges - Létourneau, Alain; Thivierge, Caroline (Les inondations au Québec : risques, aménagement du territoire, impacts socioéconomiques et transformation des vulnérabilités, 2022)
Keywords: Chapitre_Ouvrage_Collectif_Numero1

Improving flood resilience through governance strategies: Gauging the state of the art - Matczak, Piotr; Hegger, Dries (WIREs Water, 2021)
Abstract There has been an upsurge in studies of flood risk governance (FRG): steering and decision‐making by public and private actors as a complement to risk assessments and technical management options. The scholarly debate is, however, highly fragmented, complicating the production of cumulative insights. To address this knowledge gap, we used six governance strategies for achieving flood resilience that previously have been put forward as a conceptual framework to review 121 articles published between 2016 and 2019, complemented with insights contained in recent overview articles, to gauge the state‐of‐the‐art in FRG literature: to (a) diversify flood risk management strategies; (b) align the strategies; (c) adequately involve private actors, including citizens; (d) put an adequate rule system in place; (e) cater for sufficient monetary and non‐monetary resources; (f) inspire an open and inclusive normative debate. We found, first, that literature is producing insights on increasingly technically advanced risk assessments and agent‐based models but societal debate on justice in flood risk governance is getting attention. A clearly emerging topic is that of citizen engagement in flood risk governance. Second, the geographical focus of the studies is still skewed toward the Global North. To make progress in understanding flood risk governance for better resilience more systematic and comparative empirical assessments of flood risk governance in order to derive generalizable lessons while better taking into account the context‐specificity of FRG. Testing flood risk governance solutions against comparative cases, by balancing the geographical scope of research efforts, and enhancing interdisciplinary and transdisciplinary working is a way to deliver knowledge for more resilience. This article is categorized under: Human Water > Water Governance Engineering Water > Planning Water
Keywords: Ouvrage_Collectif_Numéro1

Collaborative governance of essential systems risk assessment approach - Lépine, C.; Baril, G.; Therrien, M.-C.; Hémond, Yannick; Robert, Benoît (Canadian Association for Programs in Public Administration Annual Research Conference in Public Administration, Policy, and Management, Montréal, 2019)
Keywords: Hémond_Yannick

Réchauffement planétaire de 1,5 °C, Rapport spécial du GIEC sur les conséquences d’un réchauffement planétaire de 1,5 °C par rapport aux niveaux préindustriels et les trajectoires associées d’émissions mondiales de gaz à effet de serre, dans le contexte du renforcement de la parade mondiale au changement climatique, du développement durable et de la lutte contre la pauvreté - Groupe d’experts intergouvernemental sur l’évolution du climat (GIEC) (Organisation météorologique mondiale, 2018)
Keywords: Ouvrage_Collectif_Numéro1

Resilience in the Anthropocene: governance and politics at the end of the world - Chandler, David; Grove, Kevin; Wakefield, Stephanie (Routledge research in the Anthropocene, 2020)
"This book offers the first critical, multi-disciplinary study of how the concepts of resilience and the Anthropocene have combined to shape contemporary thought and governmental practice. Faced with the climate catastrophe of the Anthropocene, theorists and policymakers are increasingly turning to 'sustainable', 'creative' and 'bottom-up' imaginaries of governance. The book brings together cutting-edge insights from leading geographers, international relations scholars and philosophers to explore how the concepts of resilience and the Anthropocene challenge and transform prevailing understandings of Earth, space, time and knowledge, and how these transformations reshape governance, ethics and critique today. This book examines how the Anthropocene calls into question established categories through which modern societies have tended to make sense of the world and engage in critical reflection and analysis. It also considers how resilience approaches attempt to re-stabilize these categories - and the ethical and political effects that result from these resilience-based efforts. Offering innovative insights into the problem of how environmental change is known and governed in the Anthropocene, this book will be of interest to students in fields such as geography, international relations, anthropology, science and technology studies, sociology, and the environmental humanities"--
Keywords: Nobert_Sebastien

Methodological approach for mapping the flood physical vulnerability index with geographical open-source data: an example in a small-middle city (Ponferrada, Spain) - Tascón-González, Laura; Ferrer-Julià, Montserrat; García-Meléndez, Eduardo (Natural Hazards, 2024)
Abstract To increase the resilience of communities against floods, it is necessary to develop methodologies to estimate the vulnerability. The concept of vulnerability is multidimensional, but most flood vulnerability studies have focused only on the social approach. Nevertheless, in recent years, following seismic analysis, the physical point of view has increased its relevance. Therefore, the present study proposes a methodology to map the flood physical vulnerability and applies it using an index at urban parcel scale for a medium-sized town (Ponferrada, Spain). This index is based on multiple indicators fed by geographical open-source data, once they have been normalized and combined with different weights extracted from an Analytic Hierarchic Process. The results show a raster map of the physical vulnerability index that facilitates future emergency and flood risk management to diminish potential damages. A total of 22.7% of the urban parcels in the studied town present an index value higher than 0.4, which is considered highly vulnerable. The location of these urban parcels would have passed unnoticed without the use of open governmental datasets, when an average value would have been calculated for the overall municipality. Moreover, the building percentage covered by water was the most influential indicator in the study area, where the simulated flood was generated by an alleged dam break. The study exceeds the spatial constraints of collecting this type of data by direct interviews with inhabitants and allows for working with larger areas, identifying the physical buildings and infrastructure differences among the urban parcels.

Trajectoires de la vulnérabilité aux inondations dans les bassins versants des rivières Cascapédia et Petite Cascapédia à l'est du Québec - Tomety, Yaovi Djivenou (Université du Québec à Rimouski, 2022)
RÉSUMÉ : Les inondations dans la MRC de Bonaventure, à l'instar des inondations de 2017 et de 2019 aux Québec, amènent à repenser les politiques de gestion préventive des inondations dans les municipalités mais il est nécessaire de revisiter le passé pour mieux anticiper le futur. A l'heure actuelle, aucune étude dans la MRC de Bonaventure n'a abordé la trajectoire de la vulnérabilité aux inondations. Le projet de recherche avait pour objectif d'évaluer l'évolution spatio-temporelle de la vulnérabilité aux inondations dans la MRC de Bonaventure plus précisément dans les bassins versants des rivières Cascapédia et petite Cascapédia. Cette recherche s'est particulièrement intéressée à : - 1) - identifier les indicateurs de vulnérabilité aux inondations les plus pertinents et leurs interactions et - 2) - comprendre la trajectoire de la vulnérabilité aux inondations dans le temps. La méthode indicielle a permis de calculer les indices de vulnérabilité par addition d'indicateurs pondérés dans l'analyse de la trajectoire de la vulnérabilité pour les années 1986, 1996, 2006 et de 2016 à partir de 43 indicateurs sélectionnés, adaptés au contexte de la zone d'étude et validés par la MRC de Bonaventure. L'évaluation de la trajectoire de la vulnérabilité aux inondations révèle que les variables socio-économiques sont les plus importantes contribuant à faire varier la vulnérabilité dans le temps dans les corridors fluviaux des rivières Cascapédia et petite Cascapédia. Cette étude expose le caractère dynamique, temporel et transformationnel de la vulnérabilité. Les cartographies de vulnérabilité générées en maillages de 200 m x 200 m et les enquêtes sur le terrain ont permis de mieux appréhender les changements globaux qui ont contribué à l'évolution de la vulnérabilité aux inondations et de comprendre la nature de la vulnérabilité aux inondations. Cette analyse permettra aux décideurs d'anticiper le futur pour une planification concrète de l'adaptation et des mesures de prévention. La trajectoire de la vulnérabilité se présente alors comme un outil de prévention et de prospection pour les décideurs. Elle permet d'appréhender la vulnérabilité du passé, comprendre la vulnérabilité du présent et anticiper sur la vulnérabilité du futur. -- Mot(s) clé(s) en français : Trajectoire, vulnérabilité, inondation, indice de vulnérabilité, gestion préventive. -- ABSTRACT : The floods in the MRC of Bonaventure, like the floods of 2017 and 2019 in Quebec, lead to a rethink of the preventive flood management policies in the municipalities, but it is necessary to revisit the past to better anticipate the future. At present, no study in the MRC of Bonaventure has addressed the trajectory of vulnerability to flooding. The objective of the research project was to assess the spatio-temporal evolution of vulnerability to flooding in the MRC of Bonaventure, more specifically in the watersheds of the Cascapedia and Petite Cascapedia rivers. This research was particularly interested in: - 1) - identifying the most relevant flood vulnerability indicators and their interactions and - 2) - understanding the trajectory of flood vulnerability over time. The index method made it possible to calculate the vulnerability indices by adding weighted indicators in the analysis of the trajectory of vulnerability for the years 1986, 1996, 2006 and 2016 from 43 selected indicators, adapted to the context of the study area and validated by the MRC of Bonaventure. The evaluation of the trajectory of vulnerability to flooding reveals that socio-economic variables are the most important contributing to varying vulnerability over time in the fluvial corridors of the Cascapedia and Petite Cascapedia rivers. This study exposes the dynamic, temporal and transformational character of vulnerability. The vulnerability maps generated in 200 m x 200 m grids and the field surveys have made it possible to better understand the global changes that have contributed to the evolution of vulnerability to floods and to understand the nature of vulnerability to floods. This analysis will allow decision-makers to anticipate the future for concrete planning of adaptation and prevention measures. The trajectory of vulnerability is then presented as a prevention and prospecting tool for decision-makers. It makes it possible to apprehend the vulnerability of the past, to understand the vulnerability of the present and to anticipate the vulnerability of the future. -- Mot(s) clé(s) en anglais : Trajectory, vulnerability, flooding, vulnerability index, preventive management.

Spatial Analysis of Social Vulnerability to Floods Based on the MOVE Framework and Information Entropy Method: Case Study of Katsushika Ward, Tokyo - Lianxiao; Morimoto, Takehiro (Sustainability, 2019)
Tokyo is located in a lowland area that is vulnerable to flooding. Due to global climate change, the scalability and frequency of flooding is increasing. On the other hand, population aging and family structural changes, as well as the lack of adaptation measures, would accelerate flooding vulnerability. The key factors involved in social vulnerability must be studied to reduce the risk of flooding. In this study, we refer to the MOVE framework (a disaster vulnerability assessment framework) and analyze it from three perspectives: Exposure to social vulnerability, susceptibility, and resilience. We subsequently develop an index system to complete the evaluation using 11 indicators. The collected data will help reveal social vulnerability to floods in the Katsushika Ward, Tokyo, using the information entropy method and GIS. We found that the western region of the Katsushika Ward is at more risk than the eastern region during flooding. Additionally, the possibility of a serious crisis erupting is greater in the southwestern region than in the northwestern region. Consequently, we conclude that the spatial distribution of flooding varies in the region. The results of this study will help in understanding social vulnerability, in selecting and combining adaptation measures suited to the characteristics of the area, and in the effective and efficient implementation of these measures by the local government’s disaster department.

Mapping Urban Risk: Flood Hazards, Race, & Environmental Justice In New York" - Maantay, Juliana A.; Maroko, Andrew R. (Applied Geography, 2009)
Abstract This paper demonstrates the importance of disaggregating population data aggregated by census tracts or other units, for more realistic population distribution/location. A newly developed mapping method, the Cadastral-based Expert Dasymetric System (CEDS), calculates population in hyper-heterogeneous urban areas better than traditional mapping techniques. A case study estimating population potentially impacted by flood hazard in New York City compares the impacted population determined by CEDS with that derived by centroid-containment method and filtered areal-weighting interpolation. Compared to CEDS, 37% and 72% fewer people are estimated to be at risk from floods city-wide, using conventional areal weighting of census data, and centroid-containment selection, respectively. Undercounting of impacted population could have serious implications for emergency management and disaster planning. Ethnic/racial populations are also spatially disaggregated to determine any environmental justice impacts with flood risk. Minorities are disproportionately undercounted using traditional methods. Underestimating more vulnerable sub-populations impairs preparedness and relief efforts.

What can be said about risks, vulnerabilities, and adaptation to climate change in Caribbean small island developing states (SIDS)? The case of Dominica. A qualitative study - Cooper, Sarah; Abraham, Christiana; Ravaliere, Terrilia; Harris-Glenville, Fiona; McPherson, Nickez; Cloos, Patrick (2023)
IntroductionCaribbean Small island developing states (SIDS) are generally qualified as disproportionately vulnerable to climate change, including extreme weather events like hurricanes. While many studies already documented the impacts of climate change on health in the wealthiest countries, there is little knowledge in this field in Caribbean SIDS. Our study aims to discuss health risks and vulnerabilities in a Caribbean context to inform future adaptation measures to climate change.MethodsOur paper is based on a qualitative study that was conducted in Dominica, a Caribbean SIDS. The data come from semi-structured interviews organized between March 2020 and January 2021 with people internally displaced following an extreme climate event, either tropical storm Erika (2015) or Hurricane Maria (2017), and with some people who migrated to Guadeloupe after Hurricane Maria. Interview guides were based on conceptual frameworks on climate change, migration and health, and vulnerability to climate change. Data were analyzed deductively based on frameworks and inductively to allow new codes to emerge.ResultsOur findings suggest that current knowledge of climate change by those who have been displaced by an extreme climate event varied greatly depending on the education level, class, and socioeconomic condition of the participant. Participants experienced various negative consequences from a storm or hurricane such as increased risk of relocation, lack of access to healthcare, and food, job, and water insecurities – all circumstances know to correlate with mental health issues. Participants suggested stronger dwellings, community preparedness committees to act sooner, and climate change sensitization and awareness campaigns to foster community unity and solidarity.ConclusionThese findings contribute to the perspectives and knowledge of climate change, highlighting that existing extreme climate event committees and government officials need to address structural and social barriers that can potentially increase social inequalities and lead to maladaptation to climate change with potential consequences on public health.
Keywords: Cloos_Patrick

Flood risk quantification and mapping: An integrated vulnerability-based approach at the local scale in New Brunswick, Canada - Duhamel, Francis; Germain, Daniel; Fortin, Guillaume (International Journal of Disaster Risk Reduction, 2022)
This paper explores the risk approach, considering both the physical and human dimensions of the phenomenon in order to produce a more realistic and spatial analysis of risk. Exposure and vulnerability were combined and evaluated multidimensionally, considering individual, socio-economic, and structural (building-related) aspects. These risk factors were then integrated in a multi-criteria analysis in order to produce a comprehensive risk index that could be visualized at the building scale. The relative importance of the indicators was determined through a participatory process involving local and national experts on civil security and flooding. Particular attention was paid to individual vulnerability, including perception and preparedness for flood risk, which were explored directly with local people using a questionnaire. Qualitative and quantitative analyses of the responses allowed for a better understanding of the perception and preparedness of populations exposed to flooding. These data should help to improve risk communication between the authorities concerned and the populations at risk, as well as encouraging implementation of appropriate measures and a bottom-up participatory management approach. The integration of data in a geographic information system enables the visualization and spatialization of risk, but also each of its components.
Keywords: Infolettre; Infolettre_Fevrier_2023

Physical Vulnerability and Local Responses to Flood Damage in Peri-Urban Areas of Dhaka, Bangladesh - Fatemi, Nawrose; Okyere, Seth Asare; Diko, Stephen Kofi; Kita, Michihiro; Shimoda, Motoki; Matsubara, Shigeki (Sustainability, 2020)
In Eastern Dhaka, perennial flood remains a constant threat to people and livelihoods. Learning from the micro-level experiences of the poor in the peri-urban areas of Dhaka provides insights on the intersections between physical vulnerability, flood response strategies, and adaptive capacity. Through a convergent mixed method, this study examines the physical vulnerability of residential buildings, flood damages, and local physical responses in three neighborhoods of Eastern Dhaka. Results show that the level of damage to buildings is the most important predictor of physical vulnerability to floods. Buildings that are older than 20 years old and built with natural materials are likely to experience high flood damages compared to buildings that are less than 10 years and constructed with durable materials. The study concludes that in addition to socio-economic interventions, a targeted and people-centered flood management regime that pays attention to age, material composition, and structural quality of houses is necessary to build residents’ adaptive capacities and long-term resilience to flooding. This study contributes to the emerging work on grassroots responses to flood vulnerabilities with practical insights for urban planners and disaster management professionals on particular interventions needed to improve the performance of local responses to flood risks and vulnerabilities.

Combining hazard, exposure and social vulnerability to provide lessons for flood risk management - Koks, Elco; Jongman, Brenden; Husby, Trond; Botzen, W. J. Wouter (Environmental Science & Policy, 2015)
Flood risk assessments provide inputs for the evaluation of flood risk management (FRM) strategies. Traditionally, such risk assessments provide estimates of loss of life and economic damage. However, the effect of policy measures aimed at reducing risk also depends on the capacity of households to adapt and respond to floods, which in turn largely depends on their social vulnerability. This study shows how a joint assessment of hazard, exposure and social vulnerability provides valuable information for the evaluation of FRM strategies. The adopted methodology uses data on hazard and exposure combined with a social vulnerability index. The relevance of this state-of-the-art approach taken is exemplified in a case-study of Rotterdam, the Netherlands. The results show that not only a substantial share of the population can be defined as socially vulnerable, but also that the population is very heterogeneous, which is often ignored in traditional flood risk management studies. It is concluded that FRM measures, such as individual mitigation, evacuation or flood insurance coverage should not be applied homogenously across large areas, but instead should be tailored to local characteristics based on the socioeconomic characteristics of individual households and neighborhoods.

Integrating social vulnerability into federal flood risk management planning - Cutter, S.L.; Emrich, C.T.; Morath, D.P.; Dunning, C.M. (Journal of Flood Risk Management, 2013)
Abstract While flood risk management planning in the U nited S tates has focused on flood control structures designed to protect the economic value of property, it has consistently undervalued other social impacts associated with flooding. The US A rmy C orps of E ngineers ( USACE ) recently initiated research aimed at understanding how to incorporate social characteristics into the measures currently utilised in flood control project evaluation and consideration. This paper proposes a methodology for incorporating a known measure of social vulnerability, the S ocial V ulnerability I ndex ( SoVI ), into USACE civil works planning. Using the USACE S outh A tlantic D ivision as the study area, this paper evaluates eight different variations of the social vulnerability metric and their potential deployment in USACE projects. Each formulation is compared with the original‐computed SoVI as a means to test its spatial and statistical sensitivity, including an assessment of each variant's robustness, reducibility, scalability, and transferability. Results indicate that while it is possible to create simplified, yet robust, versions of SoVI for individual places, such ‘lite’ metrics tend to fall short in areas of scalability and transferability in relation to the original SoVI formulation.